Anthropogenic nutrient discharge and microbial community shifts associated with typhoon-driven runoff in an artificial coastal lake - Seung-Hee Kim; Keonhee Kim; Min-Seob Kim; Dong-Hun Lee; Eun-Ji Won; Kyung-Hoon Shin (Marine Pollution Bulletin, 2026)

Behavioral effects of chronic PFHxA exposure on spatial memory function - Dong Hun Lee; BaDa Cho; Jieun Seo; Yun Hee So; Hyun Seung Shin; Dohyo Lim; Inho Hwang; Eun-Hee Lee; Beum-Soo An; Eui-Man Jung (Toxicology, 2026)

Comparative genomics and phenotypes of Listeria monocytogenes isolated from enoki mushrooms in South Korea and China - Wen Si Hu; So Hyeon An; Dong Woo Kim; Hyeong Uk Im; Seung Hun Lee; Yu Bao Li; Zi Xuan Liu; Zhi Wei Wang; A Ram Lee; Ui In Kim; Hyeon Ji Je; Yeon Ju Seo; et al. (Food Microbiology, 2026)

EPB41L3 suppresses epithelial-mesenchymal transition and proliferation by attenuating TGF beta signaling pathways - Min Kyung Kim; Byoung-Whui Choi; Hun Gyu Hwang; Hun Soo Chang; Choon-Sik Park; Jong-Uk Lee (Tissue and Cell, 2026)

Physiologically based pharmacokinetic modeling of propofol: Impact of liver cirrhosis on systemic exposure and model-informed dose optimization according to Child–Pugh classification - Hee-Yeong Jeong; Chi-Ho Lee; Ji-Hun Jang; Seung-Hyun Jeong (Toxicology and Applied Pharmacology, 2026)

Combined toxicity of pyrethroid insecticides and azole fungicides in honey bee larvae - Minju Choi; Kyongmi Chon; Juyeong Kim; Hui-Yeon Ahn; Bo-Seon Kim; Bala Murali Krishna Vasamsetti; Chang-Young Yoon; Sojeong Hwang; Kyeong-Hun Park; Ji-Hoon Lee (Environmental Pollution, 2026)

Exciplex strength as a design principle for high-performance organic light-emitting diodes - Al Amin; Jee-Hun Jang; Woo-Sam Kim; Hanbeen Lee; Jaeho Lee; Rino Choi; Jeong-Hwan Lee (Chemical Engineering Journal, 2026)

Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

A mechanistic evaluation of sodium channel modulators in hiPSC-derived cardiomyocytes using fluorescence-based sodium flux imaging - Su-Bin Kim; Jaehun Lee; Jieun An; Ara Cho; Kun Hee Lee; Eunho Kim; Hwan Choi; Jina Ryu; Ki-Suk Kim; Choongseong Han; Dong-Hun Woo (Biotechnology Letters, 2026)

Quantifying wave-induced fuel consumption and CO2 emissions: a high-fidelity free-running CFD approach - Daejeong Kim; Chybyung Park; Sung-Ji Kim; Heeseok Kim; Jong-Hun Im; Sang-Deuk Lee; Seungcheol Kwon; Yoonwon Choi; Chulhyun Hong; Mukyeong Kang; Soonseok Song; Tahsin Tezdogan (Ocean Engineering, 2026)

Modulation of starch ordering by cold storage and microwave reheating alters starch digestibility and glycemic response in cooked rice - Dong-Hwa Cho; Mingyo Ha; Felicia Irawan; Ju Hun Lee; Jiyoung Park; Hyun-Jung Chung (Food Research International, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

surfaceChemistryFoam: An OpenFOAM-based library for detailed surface chemistry in reacting flow simulations - Danh Nam Nguyen; Jae Hun Lee; Hae Won Seo; Hyung Jun Ahn; Chun Sang Yoo (Computer Physics Communications, 2026)

Phase behavior and ANN modeling of Poly(l-lactide-co-caprolactone-co-glycolide) in supercritical solvent–cosolvent systems - Hyeon Choe; Chang-Woo Lee; Hun-Soo Byun (Chemical Engineering Journal, 2026)

Anode-free solid-state batteries: Interfacial engineering across solid electrolyte classes toward practical implementation - Seung-Bo Hong; Yerin Park; Jeewoo Lim; Jieun Lee; Hun-Gi Jung (Chemical Engineering Journal, 2026)

Air mass factor sensitivity to a priori profiles in GEMS formaldehyde retrieval during the ASIA-AQ campaign - Gitaek T. Lee; Rokjin J. Park; Hyeong-Ahn Kwon; Jaein I. Jeong; Seungun Lee; Eunjo S. Ha; Yoonbae Chung; Cheol-Hee Kim; Soontae Kim; Chul H. Song; Chang-Keun Song; Jung‐Hun Woo; et al. (Atmospheric Environment, 2026)

Establishing PM2.5 conversion factors for South Korea at provincial level - Jasper Madalipay; Kyung Man Han; Chul H. Song; Greg Yarwood; Ross Beardsley; Swen Metzger; Jung-Hun Woo; Dogyeong Lee (Atmospheric Pollution Research, 2026)

Lithium Recovery From Lithium Phosphate Using Acid-based Leaching With Additives - Sohyun Park; Kung-Won Choi; Ziqiao Liao; Ju-Hyeok Kwon; Sunjae Lee; Bikram Basak; Soon Woong Chang; Jaeyoung Choi; Byong-Hun Jeon; Yongtae Ahn (Water, Air, & Soil Pollution, 2026)

Linking biogeochemical signatures to archaeal community structure at active methane seeps in the Tatar trough, far eastern Russia - Dong-Hun Lee; Jung-Hyun Kim; Yung Mi Lee; Alina Stadnitskaia; Helge Niemann; Carme Huguet; Young-Keun Jin; Hirotsugu Minami; Akihiro Hachikubo; Kyung-Hoon Shin (Marine Chemistry, 2026)

Co-hydrothermal carbonization of biopolymer and biomass wastes: Sustainable valorization into solid fuel and thermal filler - Jung-Hun Kim; Zambaga Otgonbayar; Thu-Huong Le; Juwon Kang; Seungmook Jung; Jaewon Cha; Suk Jekal; Jiwon Kim; Hyungseok Nam; Chang-Min Yoon; Doyeon Lee (Journal of Environmental Management, 2026)

Efficient nutrient recovery from source-separated urine via a hybrid Membrane Bioreactor and Electrodialysis (MBR-ED) system - Hanwei Yu; Weonjung Sohn; Sherub Phuntsho; Youngjin Kim; June-Seok Choi; Jong-Hun Lee; Youngkwon Choi; Ho Kyong Shon (Desalination, 2026)

Carbon-negative footprint in syngas production through aquatic plant pyrolysis - Youngju Kim; Jung-Hun Kim; Doyeon Lee; Man Sig Lee; Eilhann E. Kwon (Chemical Engineering Journal, 2026)

Applicability of conventional genotoxicity test guidelines to mRNA vaccines: a four-battery assessment of a SARS-CoV-2 mRNA vaccine candidate - Jae-Hun Ahn; Yun-Soon Kim; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Seo-Hyeon Bae; Jisun Lee; Jae-Hwan Nam; Byeong-Cheol Kang (Toxicological Research, 2026)
mRNA vaccine formulations are generally considered to pose a lower genotoxic risk than conventional small-molecule pharmaceuticals; however, long-term data regarding their potential genotoxicity remain limited. Furthermore, to date, no standardized genotoxicity testing guidelines specifically tailored to the unique characteristics of mRNA vaccines have been formally established. In this study, we conducted a comprehensive genotoxicity assessment of a SARS-CoV-2 Omicron variant mRNA vaccine candidate using a four-test battery, following a modified regimen that accounted for the unique characteristics of mRNA vaccines while adhering to OECD test guidelines: bacterial reverse mutation test (OECD TG 471), in vitro chromosomal aberration test (OECD TG 473), in vitro micronucleus test (OECD TG 487), and in vivo erythrocyte micronucleus test in mice (OECD TG 474). No significant genotoxic effects of the mRNA vaccine candidate were observed in any of the four assays. However, during the design and conduct of this study in accordance with existing genotoxicity guidelines, ambiguity arose as to whether test concentrations should be determined according to the mRNA component or the LNP component. In addition, we observed that, unlike the LNP administered alone, the mRNA vaccine candidate was associated with a reduction in the proportion of PCEs in the in vivo micronucleus assay. Although our mRNA vaccine candidate showed no significant evidence of genotoxicity, the experimental design and dosing regimen highlight the need to refine current regulatory testing guidelines for mRNA vaccines. We anticipate that our findings will contribute to the development of more appropriate genotoxicity guidelines for advanced therapy medicinal products (ATMPs), including mRNA vaccines.

Heat shock-induced zinc efflux repurposes Arabidopsis E3 ligase EMR as a molecular chaperone - Ho Byoung Chae; Su Bin Bae; Joung Hun Park; Seol Ki Paeng; Seong Dong Wi; Meiai Zhao; Min Gab Kim; Woe-Yeon Kim; Sang Yeol Lee (Molecular Plant, 2026)

Reusable composite adsorbent for aqueous solutions and soils multi-contaminated with As(V), Cd(II), Pb(II), and diesel - Jong Cheol Lee; Hailu Fu; Muhammad Kashif Irshad; Hun Ho Lee; Dong Hwan Shin; Sang Soo Lee (Journal of Water Process Engineering, 2026)

Effect of excess and restricted inorganic carbon on biokinetics, nitrous oxide emissions, and microbial community in a full-nitrification bioreactor - Seongbong Heo; Jong Hun Jeon; Sungman Lee; Hyeongju Park; Meng Wang; Jung-Hyun Lee; Young Mo Kim (Environmental Research, 2026)

Associations between environmental metal mixture exposure and urinary DNA adduct biomarkers of oxidative and alkylative damage in adults - Jang-Hun Jeong; Bo-Ri Kim; Jeong-Kyu Ji; Hyemi Lee; Kyung-Hwa Choi; Yong Min Cho; Woo Jin Kim; Young-Seoub Hong; Heon Kim; Yong-Dae Kim; Sang-Yong Eom (Environmental Research, 2026)

Physiologically based pharmacokinetic modeling of caffeine in patients with liver cirrhosis: Implications for exposure-guided dose adjustment - Se-In Lee; Chi-Ho Lee; Ji-Hun Jang; Seung-Hyun Jeong (Environmental Toxicology and Pharmacology, 2026)

SBR-free high-loading anodes enabled by lithium-substituted CNT/CMC adhesive conductive networks for fast-charging lithium-ion batteries - Min Gi Kang; Hyun Jun Song; Hye Seon Kim; Sihyung Lee; Jaeho Kim; Ji Hun Lim; Jeong Yoon Kim; Hyejeong Jeong; Junyoung Park; Junghyun Nam; Chan-Hwa Chung; Pil J. Yoo (Chemical Engineering Journal, 2026)

Osteological development of the larvae and juveniles of Thryssa kammalensis (Clupeiformes: Engraulidae) from the Southwestern Coasts of Korea - Hyeon-Jun Ryu; Se Hun Myoung; Sang-Chul Yoon; Jeong-Hoon Lee; Jin-Koo Kim (Zoomorphology, 2026)

Integrating high-fidelity hiPSC-cardiomyocytes with AI-driven modeling for enhanced proarrhythmic risk assessment - Su-Bin Kim; Jaehun Lee; Jieun An; Ara Cho; Kun Hee Lee; Hwan Choi; Choongseong Han; Muhammad Adnan Pramudito; Ki Moo Lim; Dong-Hun Woo (Archives of Toxicology, 2026)
Cardiotoxicity remains the leading driver of drug attrition; however, its prediction remains suboptimal when conventional hERG assays and animal models are used. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) offer a human-relevant alternative that aligns with the CiPA initiative and ICH E14/S7B guidelines. This study validated an integrated platform that combines high-purity hiPSC-CMs with Artificial Intelligence (AI) to enhance the accuracy of predicting drug-induced proarrhythmic risk. Phenotypic characterization of the hiPSC-CMs demonstrated high cardiac differentiation efficiency (cTnT + > 95%) and a predominant ventricular-like identity (MLC-2 V + , 78–84%), ensuring biological relevance for ventricular arrhythmia assessment. Electrophysiological data from 28 CiPA reference compounds were collected via Multielectrode Array (MEA) to train multiple machine learning models. The Artificial Neural Network outperformed the other architectures, achieving a superior ROC-AUC of 0.982. The utility of the platform was evaluated using 12 anticancer agents. Although most drugs showed dose-dependent reductions in impedance-based viability, four compounds (Idarubicin, Erlotinib, Sunitinib, Cyclophosphamide) did not exhibit overt structural cytotoxicity. However, MEA analysis revealed significant functional perturbations, including FPDcF prolongation, in sunitinib- and erlotinib-treated samples after long-term treatment. The AI model subsequently classified these two agents as high-to-intermediate risk for Torsades de Pointes (TdP), thereby quantifying their time-dependent proarrhythmic liabilities. These findings show the platform’s ability to detect hidden functional cardiotoxicity, often missed by standard viability assays. The AI-hiPSC-CM system offers a high-throughput, early-stage safety screening tool that bridges in vitro data and clinical outcomes with a standardized risk assessment framework.

Seasonal Variation in Ichthyoplankton Assemblage Structure in Yeongil Bay, Korea - Se Hun Myoung; Hwan-Sung Ji; Hyo-Jae Yu; Sang Chul Yoon; Jeong-Hoon Lee (Fishes, 2026)
Ichthyoplankton communities provide important information on spawning dynamics and early life-history processes of fish populations. This study investigated the species composition and seasonal occurrence of fish eggs and larvae in Yeongil Bay, in the East Sea of Korea, from January to December 2023. Samples were collected at seven stations and identified based on morphological characteristics and molecular analysis using mitochondrial DNA (COI and 16S rRNA). Thirty-six egg taxa (676 ± 739 eggs 1000 m−3) and 42 larval taxa (28 ± 35 larvae 1000 m−3) were identified. The dominant egg species were Engraulis japonicus (23.3%), Pseudopleuronectes herzensteini (11.8%), and Sardinops sagax (9.8%), while the dominant larval species were Sebastes inermis (29.7%), Sillago japonica (20.7%), and Sebastiscus marmoratus (5.5%). Egg abundance increased from spring and reached a peak in July, whereas larval abundance showed seasonal peaks in January and August. nMDS ordination showed seasonal variation in assemblage structure. Egg assemblages showed seasonal grouping patterns that corresponded with seasonal variation in surface water temperature and salinity, whereas larval assemblages showed relatively more complex seasonal patterns and were characterized by higher species richness and more extended seasonal occurrence. These results suggest that ichthyoplankton assemblages in Yeongil Bay exhibited seasonal variation in species composition during the study period, with E. japonicus eggs comprising the dominant component of the summer ichthyoplankton assemblage. Furthermore, the combined use of morphological and molecular identification improved species-level resolution and provided baseline information for understanding seasonal variation in ichthyoplankton assemblages in this coastal ecosystem.

Comparison of 18S rRNA gene fragments and reference databases for assessing bovine Eimeria diversity using the Illumina platform - Subin Lee; So Youn Youn; Min-Goo Seo; Mi-Sun Yoo; Hyang-Sim Lee; Yun Sang Cho; Dongmi Kwak; Seung-Hun Lee (Veterinary Parasitology, 2026)

Nonclinical safety evaluation strategies for mRNA/LNPs platform agents: Evidence from comprehensive animal toxicity studies - Jae-Hun Ahn; Na-Young Lee; Hee-Jin Bae; Jooil Kim; Jina Kwak; Euna Kwon; Gahyun Roh; Seo-Hyeon Bae; Soo-Yeon Lee; Il Kwon Hwang; Jisun Lee; Hyo-Jung Park; et al. (Toxicology Letters, 2026)

Benchmarking living-zone plans with mobility community detection: Evidence from Seoul's mobile-phone-based mobility data - Jongha Park; Sunyong Eom; Myeong-Hun Lee (Journal of Transport Geography, 2026)

Population pharmacokinetic modeling–based human health risk assessment of di-isodecyl phthalate using biomonitoring-driven reverse dosimetry - Ji-Hun Jang; Chen Zhou; Chi-Ho Lee; Seung-Hyun Jeong (Journal of Hazardous Materials, 2026)

Synergistic effects of seaweed powder and rheology modifiers on the reaction mechanism and pore architecture of geopolymer - Hyun-Soo Lee; Joo-Young Kim; Jae-Suk Ryou; Byeong-Hun Woo; Hong-Gi Kim (Journal of Cleaner Production, 2026)

Alkaline-compatible Nb18W16O93/NiHPO4 complementary electrochromic devices for solar heat regulation - Kwang-Mo Kang; Young-Hun Kim; Ji-Hyeong Lee; Woo-Seok Choi; Mina Ryu; Seong-Jong Hwang; Yoon-Chae Nah (Chemical Engineering Journal, 2026)

Tailored medium-entropy Si alloy anodes with multi-element Fe-site substitution for high-performance Li-ion batteries - Byeong Guk Kim; Jung-Hyeok Park; Jihyeon Ryu; Kyungmin Do; Dong Gyun Hong; Tae-Hyun Kwon; Oh Sung Kwon; Insung Jang; Jaeik Hyun; Geon-Hyoung An; Youngoh Kim; Geon-Woong Lee; et al. (Chemical Engineering Journal, 2026)

Simultaneous bioelectricity generation and selective copper recovery via controlled two-step discharge strategy in a two-chamber microbial fuel cell using an unbuffered copper catholyte - Jun Hyun Kim; Hyeong Jae Kim; Dong Hun Lee; Sunghyun Kim (Bioresource Technology, 2026)

Trait–environment diagnosis of ecological instability in Korean streams using benthic diatoms and machine learning: a UMAP–CDI framework - Jun-Ho Lee; Hyo Gyeom Kim; Byeong-Hun Han; In-Hwan Cho; Ha-Kyung Kim; Eun-A. Hwang; Su-Ok Hwang; Baik-Ho Kim (Aquatic Sciences, 2026)

Targeting the fibrosis-inflammation-oxidative stress axis: multifaceted mechanisms of salidroside in chronic organ fibrosis - Ai-Qian Liu; Jongwon Byun; Nan Nan Yu; Mei-Hua Jin; Ying-Hao Han; Dong Seok Lee; Dong-Hun Lee; Hu-Nan Sun (Apoptosis, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

Simplified analytical method for dropped object assessment in offshore and new fueled ship - Jung Kim; JongWon Kim; Hoki Lee; Jung-Kwan Seo; Jong-Hun Woo (Ocean Engineering, 2026)

Polystyrene nanoplastic-encapsulated extracellular vesicles promote blood–brain barrier breakdown and accumulate in the brain - Min Jae Kim; Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Jae-Eon Lee; Hyeon-Gu Kang; DongJoo Joung; Eui-Man Jung; Beum-Soo An (Journal of Hazardous Materials, 2026)

Impact of ionomer-free anode electrodes on mass transport and durability of proton exchange membrane water electrolyzer - T.B. Ngoc Huynh; Hanjin Lee; Jihyeok Song; Doan Van Hong Thien; Yong-Hun Cho; Oh Joong Kwon (Chemical Engineering Journal, 2026)

Citrate-enabled process intensification reinforces energy and redox metabolism for sustainable bioproduction using Corynebacterium glutamicum - KwangYoung Park; Hoe-Suk Lee; Dong Young Lee; June-Ho Choi; Yunhee Jeong; SunJoo Park; Yunjeong Song; Jiyoung Park; Chan-Duck Jung; Hoyong Kim; Sung-Hyun Jo; Yun-Gon Kim; et al. (Bioresource Technology, 2026)

Lactobacillus Plantarum Q180 Attenuates Hepatic Lipid Accumulation and Regulates Energy Metabolism in High-Fat Diet-Induced Obese Mice - Minseo Cho; Hyunchae Joung; Hyunsoo Jang; Yeon-Woo Kim; Jaeryang Chu; Yoo Jin Kwon; Chang Hun Shin; Jung-Heun Ha; Jisu Lee (Probiotics and Antimicrobial Proteins, 2026)

Weathered plastic particles negatively affect mouse primary neurons and glial cells - Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Yunsoo Chang; Min Jae Kim; DongJoo Joung; BuHyun Youn; Eun-Hee Lee; Eui-Man Jung (Archives of Toxicology, 2026)

Translating human biomonitoring data into quantitative exposure and risk estimates for chloromethylisothiazolinone and methylisothiazolinone using a population pharmacokinetic model - Ji-Hun Jang; Chi-Ho Lee; Yong Joo Park; Kyu Hyuck Chung; Byoungcheun Lee; Yong-Wook Baek; Seung-Hyun Jeong (Archives of Toxicology, 2026)

A Flow Analysis Modeling Study on the Performance Characteristics of LNG-Fueled Gas Valve Unit - Jung-Wook Lee; Kyeong-Ju Kong; Do-Yeong Jeong; Seung-Hun Han (Journal of Marine Science and Engineering, 2026)
As climate change and air pollution problems become more serious around the world, regulations to reduce greenhouse gas emissions are being tightened. The International Maritime Organization (IMO) has adopted measures to limit sulfur oxides and nitrogen oxides generated by ships. Due to the continuous use of fossil fuels, carbon dioxide emissions are increasing rapidly, which is acting as a major cause of global warming and climate change. Currently, the carbon neutrality policy to reduce greenhouse gases emitted by ships is expanding, and the use of alternative energy from marine fuels is increasing worldwide. The shipbuilding industry is actively introducing eco-friendly ships that use liquefied natural gas (LNG) fuels, and the importance of equipment such as the Fuel Gas Supply System (FGSS), which can supply eco-friendly energy, is growing. In this study, we designed a Gas Valve Unit (GVU), one of the FGSS components, and analyzed the internal flow of the GVU by performing computational fluid dynamics (CFD) simulations.

Plant life form, biomass allocation, and belowground structure shape depth-dependent soil organic carbon accumulation as blue carbon sources in vegetated tidal flats - Jae-Hoon Park; Yeo-Bin Park; Ji-Won Park; Sang-Pil Lee; Do-Hun Ryu; Seung-Jun Lee; Jun-Mo Kim; Ji-Su Ko; Eui-Joo Kim; Yoon-Seo Kim; Young-Han You (Science of The Total Environment, 2026)

Rare earth elements as tracers of anthropogenic sources and the influence of land-based aquaculture effluent on trace elements in coastal waters of Jeju Island, Korea - Ijin Lim; Jumi Kim; Wonjin Choi; Jiwoo Kim; Seongha Kim; Seung-Hee Kim; Dong-Hun Lee; Seok Jin Oh; Chulin Sun; Sung-Eun Park; Weol Ae Lim; Taejin Kim (Regional Studies in Marine Science, 2026)

Methanotrophic community structure and metabolic potential in the sulfate–methane transition zone of the ARAON mounds, Arctic Chukchi Sea - Jehyun Jeon; Dong-Hun Lee; Ji-Hoon Kim; Yeonjin Choi; Young Keun Jin; Jong Kuk Hong; Yung Mi Lee (Marine Environmental Research, 2026)

DTLreactingFoam: An efficient CFD tool for laminar reacting flow simulations using detailed chemistry and transport with time-correlated thermophysical properties - Danh Nam Nguyen; Jae Hun Lee; Chun Sang Yoo (Computer Physics Communications, 2026)

Synergistic recruitment of exogenous and endogenous stem cells by an SDF1-mimetic peptide–loaded click-crosslinked hyaluronic acid dressing for enhanced wound healing - Yejin Lee; Young Hun Kim; Sangdun Choi; Moon Suk Kim (Chemical Engineering Journal, 2026)

Oligomeric strategy for ether-free multiblock copolymer anion exchange membranes with ordered ionic channels for efficient alkaline water electrolysis - Jin Hyuk Kim; Eun Woo Lee; Hyuk Jin Roh; Jae Hun Lee; Jong Hak Kim (Chemical Engineering Journal, 2026)

Publisher Correction: Synoptic-Scale Environment for Heavy Rainfall Over the Korean Peninsula During the Changma (late June through mid-July) and August - Sang-Hun Park; Uju Shin; Sehyun Lee; Tae-Young Lee (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Multimodal Graphical Network Analysis of Small-for-Gestational-Age in Preterm Infants: Integrating Neonatal Brain Volume, Structural Connectivity, and Early Neurodevelopmental Outcome - Se Hyun Lee; Yong Hun Jang; Hyuna Kim; Gang Yi Lee; Hyun Ju Lee; Hyun Ho Kim (Annals of Biomedical Engineering, 2026)
Purpose Infants born Small-for-gestational-age (SGA) face heightened risks for cognitive and language impairments. The neurobiological mechanisms underlying these deficits remain unclear. This study aimed to identify multimodal neuroimaging biomarkers associated with fetal growth restriction and to characterize network-level associations linking SGA to early neurodevelopmental vulnerability using a data-driven graph-based framework. Methods In this prospective cohort of 186 preterm infants, near-term brain magnetic resonance imaging (MRI) and Bayley-III developmental assessments were analyzed. Multimodal imaging features—including volumetric indices from T2-weighted MRI and diffusion metrics from diffusion tensor imaging—were integrated with perinatal data. A sparse partial-correlation network was estimated using the Graphical Lasso algorithm (λ optimized via cross-validation) to infer conditional dependencies among features. Variables directly connected to birthweight Z-scores were identified as candidate biomarkers and validated for SGA classification and developmental outcomes using logistic regression and correlation analyses. Results Network analysis identified eight neuroanatomical correlates of birthweight Z-scores, including increased cerebrospinal fluid (CSF) volume; elevated axial, mean, and radial diffusivity in the left inferior longitudinal fasciculus (ILFL); higher axial diffusivity in the inferior fronto-occipital fasciculus; and altered degree centrality in the right precentral and posterior cingulate cortices (PCC). Logistic regression revealed CSF volume and ILFL diffusivity as independent predictors of SGA. Infants with language delay showed trend-level increases in ILFL diffusivity and reduced PCC centrality after FDR correction, suggesting possible associations between microstructural and connectomic alterations and language vulnerability. Conclusion By integrating volumetric and diffusion MRI with graph-based modeling, this study uncovers latent neurobiological markers of SGA and provides clinically interpretable biomarkers for early risk stratification and individualized intervention.

Quantitative Assessment of Third Molar Extraction Difficulty and Nerve Injury Risk Using Artificial Intelligence and Image Processing - Jihyeong Ko; Sasi Sooksatra; Seungmin Kim; Shaohua Tang; Jung-Eun Ha; Dong-Hun Han; Kyu Hwan Lee; Young-jin Jung; Min-Ji Kim (Annals of Biomedical Engineering, 2026)

Protective effects of a 1:1 mixture of 7,17-dihydroxy-DHA and 10,17-dihydroxy-DHA (SF) against blue light-induced retinal damages in A2E-laden ARPE-19 Cells - Seung-Yub Song; Sung-Ho Lee; Jin-Woo Park; Han-Kyu Lim; Jeong-Woo Seo; Dae-Hun Park; Seung-Sik Cho (Tissue and Cell, 2026)

Sustainable production of high-yield torch ginger nanocellulose using a one-step H2SO4/H2O2 method - Herman Marius Zendrato; Nanang Masruchin; Siti Nikmatin; Nam Hun Kim; Seung Hwan Lee; Nyoman Jaya Wistara (Biomass and Bioenergy, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Motion Prediction of Moored Platform Using CNN–LSTM for Eco-Friendly Operation - Omar Jebari; Chungkuk Jin; Byungho Kang; Seong Hyeon Hong; Changhee Lee; Young Hun Jeon (Journal of Marine Science and Engineering, 2026)
Predicting the motion of ships and floating structures is essential for ensuring economical and environmentally friendly operations in the ocean. In this study, we propose a hybrid encoder–decoder Convolutional Neural Network–Long Short-Term Memory (CNN–LSTM) architecture to predict motions of a moored Floating Production Storage and Offloading (FPSO) vessel under varying sea conditions. The model integrates a CNN for spatial wave-field feature extraction and an LSTM encoder–decoder to capture temporal dependencies in vessel motion. Synthetic datasets were generated using mid-fidelity dynamics simulations of a coupled FPSO–mooring–riser system subjected to wave excitations. Five sea states ranging from calm to severe were considered to evaluate the model’s robustness. A key preprocessing step involved determining the optimal spatial domain for wave field input, and a wave field size of 600 m × 600 m was identified as the most cost-effective configuration while maintaining accuracy. The model was validated using the Root Mean Square Error (RMSE) or relative RMSE (RRMSE). Despite low RRMSE values in low sea states, predictions were noisier due to high-frequency, low-amplitude responses. In contrast, higher sea states yielded more stable predictions despite higher RRMSE values. The proposed method offers high-resolution motion forecasting capability, which can enhance operational safety and energy efficiency of offshore platforms, particularly when integrated with stereo camera-based wave monitoring systems.

Age-related increase of NLRC4 inflammasome and TGF-β1 signaling exacerbates airway inflammation and remodeling in asthma - Jin-Hwa Kim; Hyun-Tae Kim; Jeong-Won Kim; Ji-Soo Jeong; Su-Ha Lee; Kwan-Hoo Kim; Na-Young Kim; Young-Hun Kim; Je-Won Ko; Tae-Won Kim (GeroScience, 2026)

Environmental factors on microalgal resuspension and dynamics in tidal flats on the west coast of Korea - Hosang Kim; Junghyun Lee; Hun Jun Ha; Sun Min Choi; Yangrae Rho; Jinsoon Park; Ho Kyung Ha; Bong-Oh Kwon; Jong Seong Khim (Marine Pollution Bulletin, 2026)

A systematic review of consumer responses to meat alternative labeling - Jeong-Hun Ji; Sang Hyeon Lee (Appetite, 2026)

Dual-function of nitrogen removal and autoinducer-2 quorum quenching improves MBR performance in treating TMAH-containing wastewater - Hyunjung Kim; Seung-Hun Baek; Gyeongho Choi; Jinju Han; Chang Hyun Nahm; Kibaek Lee (Journal of Hazardous Materials, 2026)

Translational toxicokinetics of chloromethylisothiazolinone/methylisothiazolinone: Radioactivity-associated materials-physiologically based toxicokinetic modeling and human dose extrapolation - Ji-Hun Jang; Chi-Ho Lee; Yong Joo Park; Kyu Hyuck Chung; Hye-Jin Kim; Haewon Kim; Seung-Hyun Jeong (Environmental Research, 2026)

Long-Term Variability and Ecological Structure of Macrobenthic Polychaete Communities in Korean Coastal Waters: A 30-Year (1993–2022) Data-Based Assessment - Geon Kim; Kyeong Hun Lim; Jung Ho Lee; Sung Wan Park; Hyun Chool Shin (Ocean Science Journal, 2026)

Effect of Foliar Treatment with Organic Acids and Inorganic Nutrients on Yield Retention and Secondary Metabolite Profiles under Heat Stress in Soybean - Hakyung Kwon; Hong-Ju Lee; Dong Yeol Song; Sang Hun Kim; Chan Hui Lee; Kyung-Hee Kim; Byung-Moo Lee; Sung Don Lim; Jungmin Ha (Journal of Plant Growth Regulation, 2026)
Foliar application of inorganic nutrients and organic acids can affect the metabolic profile of soybean leaves and enhance soybean productivity. In this study, we investigated whether foliar application of 12 inorganic nutrients [N, P, K (10 g L −1 each); Ca, Mg, B, Zn, Fe, Cu, Mo, Si (200 g L −1 each); Se (20 g L −1 )] and five organic acids [acetic, ascorbic, citric, formic, and malic acids (200 mM each)] could alter secondary metabolite pathways and improve yield under heat stress. Treatment with Fe, Ca, and Mg induced accumulation of 3,4-dihydroxybenzoic acid, with subsequent increases in downstream isoflavones, while application of Se, Mo, Zn, P, and acetic acid led to a decrease in biochanin A, along with correlated changes in other metabolites including caffeic acid and daidzin. N and Si treatment independently increased cinnamic acid content. Ca and P treatment enhanced the accumulation of glycitin and genistein, while acetic acid treatment increased the accumulation of glycitin and daidzin. Treatment significantly altered secondary metabolite profiles in soybean leaves and alleviated yield loss under heat stress, although individual metabolite concentrations showed no significant correlations with this effect. Heat-stress tolerance mediated by metabolites appears to arise from comprehensive changes in the metabolic profile rather than the effect of a single metabolite. Overall, foliar applications reshaped leaf metabolite networks and improved yield retention under heat stress, with the largest profile shifts under P, Ca, and Mg. Follow-up physiological and enzymatic assays are recommended to establish causality for heat stress mitigation and metabolite enhancement. These findings suggest soybean leaves as a valuable source of beneficial secondary metabolites and indicate new options for soybean use and cultivation value.

Evolution and spread of H8Nx avian influenza viruses from wild birds in East Asia, 2019-2024 - Sae-hyeon Park; Sun-Hak Lee; Ye-Ram Seo; Dong-Ju Kim; Young-Jae Si; Hyesung Jeong; Suwoong Lee; Chang-Seon Song; Dong-Hun Lee (Archives of Virology, 2026)

Exosomal microRNA profiling reveals candidate biomarkers and regulatory signatures associated with paratuberculosis disease status in goats - Eun-Yeong Bok; Tae Yoon Kim; Sang-Young Seo; Han-Gyu Lee; Young-Hun Jung; Seong Hwan Bae; Nam Su Oh; Tae Jin Cho; Hyeon Woo Park; Eui Cheol Shin; Jae Kyeom Kim (The Veterinary Journal, 2026)

Polydeoxyribonucleotides isolated from the food fermentation strain Enterococcus faecium mitigate neuroinflammation via MAPK-mediated BMP/SMAD/Wnt regulation under neuro-oxidative stress - Da Hye Song; Yu-Rim Lee; Seung Min Yu; Soo Youn Lee; Sae-Hun Kim; Jeung Hee An (Food Bioscience, 2026)

Atypical humidity-enhanced NO2 sensing in WO3 via Zn doping and visible-light activation: Mechanistic elucidation and application to breath analysis - Nguyen Thao Trinh Do; Byeong-Hun Yu; Sang-Won Lee; Yeon-Tae Yu; Ji-Wook Yoon (Chemical Engineering Journal, 2026)

Targeting antifungal therapy with Dectin-1-coated solid lipid nanoparticles in a rat model of spinal fungal infection - Gi-Beom Ju; Gong Ho Han; Seong Jun Kim; Daye Lee; Min Je Kim; Seung Hun Sheen; Min Jai Cho; Seil Sohn (Chemical Engineering Journal, 2026)

Single-tube total analysis system for ratiometric detection of exosomal miRNAs in breast cancer diagnosis - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Ha Rim Ahn; Young Jo Kim; Jeong-Woo Choi; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2026)

Valorization of pine bark extracts for microporous biochar production and enhanced diazinon adsorption performance - Yoon Park; Eun-Ju Lee; Jeong-Yong Cho; Seung-Hun Chae; Jae-Won Lee (Biomass and Bioenergy, 2026)

Pilot-scale assessment of slag reactors for manganese removal from mine drainage - Dae-Gyu Im; Duk-Min Kim; Hye-Lim Kwon; Joon-Hak Lee; Oh-Hun Kwon; Seong-Taek Yun (Environmental Geochemistry and Health, 2026)

Synoptic-Scale Environment for Heavy Rainfall Over the Korean Peninsula During the Changma (late June through mid-July) and August - Sang-Hun Park; Uju Shin; Sehyun Lee; Tae-Young Lee (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Erythropoietin-derived Non-erythropoietic Peptides Conferring Oxidative Stress Resistance to Keratinocytes and Fibroblasts - Min Ae Han; Janbolat Ashim; Youngheum Ji; Eunho Kang; Minchan Jeong; Sung Jae Kim; Wookyung Yu; Jin Hae Kim; Cheil Moon; Chang-Hun Lee (Cell Biochemistry and Biophysics, 2026)

Semantic segmentation of plastic greenhouse frames and its application to finite element model reconstruction for structural response assessment - Byung-hun Seo; Sangik Lee; Jong-hyuk Lee; Yejin Seo; Dongwoo Kim; Yerim Jo; Jeongmin Lee; Won Choi (Computers and Electronics in Agriculture, 2026)

Magma fractionation and the magmatic-meteoric fluids mixing drive the sequential deposition of cassiterite to lepidolite in the Uljin prospects, South Korea - Ha Hyun Park; Jung Hun Seo; Bum Han Lee; Chul-Ho Heo; Marcel Guillong (Journal of Geochemical Exploration, 2026)

Integrated MEA for polymer electrolyte membrane fuel cells enabled by freeze–casting and direct membrane deposition - Hyeon-Seung Jung; Seung Tae Lee; Seung-Hyeon Moon; Chanho Pak; Jae-Hun Kim (Chemical Engineering Journal, 2026)

Stack effect in high-rise buildings: A comprehensive review on theoretical mechanisms, impacts, and evaluation methods - Jiajun Jing; Dong-Seok Lee; Jae-Hun Jo (Building and Environment, 2026)

Development of a Polycyclic Aromatic Hydrocarbons (PAHs) emission inventory in Korea - Min-Young Choi; Jinseok Kim; Hyejung Hu; Jiyi Lee; Ahn Lee; Jaeyoon Lee; Younha Kim; Jung-Hun Woo (Atmospheric Environment, 2026)

Environmental Risk Assessment of Dinoseb in Freshwater, Sediment, and Soil Media in Korea - Inhye Lee; Daeyeop Lee; Hun-Je Jo; Hyun Soo Kim; Kyung Sook Woo; Kyunghee Ji (Bulletin of Environmental Contamination and Toxicology, 2026)

Pharmacokinetic distinctions between small molecules and biologics in treating rheumatoid arthritis: implications for personalized therapeutic strategies and formulation development - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2026)

Necessity of considering sex factors in the clinical application of transdermal formulations - Seung-Hyun Jeong; Se-Jin Ko; Hyeon-Hee Eom; Eon-Ji Han; Ji-Hun Jang; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2026)

Field‐Usable Lateral Flow Immunochromatographic Assay for Rapid Detection of Infectious Haematopoietic Necrosis Virus ( IHNV ) - Choon‐Sup Kim; Kyoung‐Hui Kong; Sung‐Hun Lee; Wi‐Sik Kim (Journal of Fish Diseases, 2026)
A lateral flow immunochromatographic assay (LFIA) was developed for the rapid detection of infectious haematopoietic necrosis virus (IHNV, genogroups JRt‐N and JRt‐S) in rainbow trout ( Oncorhynchus mykiss ). The assay utilises the monoclonal antibody (mAb) IHNV‐3, which serves as both the detector antibody in a colloidal gold‐mAb conjugate and the capture antibody on the test line. The LFIA strip demonstrated a detection limit ranging from 10 5.05 to 10 5.8 TCID 50 /100 μL for six IHNV isolates (genogroups JRt‐N and JRt‐S) and showed no cross‐reactivity with other fish viruses. Field validation using spleen samples from 81 IHNV‐infected and 102 non‐infected rainbow trout revealed a specificity of 100%, a sensitivity of 97.5%, and an overall diagnostic effectiveness of 98.9%. These results highlight the LFIA strip as a reliable tool for the rapid (within 10 min) on‐site detection of IHNV in rainbow trout at aquaculture facilities.

Long-range transport of short-lived nitrogen dioxide in East Asia - Seung-Hee Baek; Hyo-Jung Lee; Hyun-Young Jo; Cheol-Hee Kim; Min-Jun Park; Jong-Min Kim; Juseon Bak; Hanlim Lee; Yeonjin Jung; Junsung Park; Jung-Hun Woo; Jinseok Kim; et al. (Science of The Total Environment, 2025)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

Locking of dendrites in potassium metal batteries: A potassiophilic 3D host discovered with machine learning screening - Jimin Park; Min-Gi Jeong; Muhammad Hilmy Alfaruqi; Muhamad Kurniawan; Shizhao Xiong; Shivam Kansara; Hyerim Kim; Hyeona Park; Jaekook Kim; Chan-Woo Lee; Hun-Gi Jung; Jang-Yeon Hwang (Chemical Engineering Journal, 2025)

Synergistic improvement of biohydrogen yield from food wastewater using Clostridium puniceum and magnetite-biochar - Jinok Oh; Yebin Han; Gaeun Lim; Shashi Kant Bhatia; Yun-Gon Kim; Sang-Ho Lee; Jae-Seok Kim; Yung-Hun Yang (Bioresource Technology, 2025)

Differential Effects of Murine Stroke Models on Dopaminergic Neurons, Glial Responses, and Neurobehavioral Outcomes - Sidra Tabassum; Heng Hu; Silin Wu; Shuning Huang; Bosco Seong Kyu Yang; Chang-Hun Lee; Aaron W. Gusdon; Xuefang S. Ren (Translational Stroke Research, 2025)

Heat-killed Lactiplantibacillus plantarum WB3813 and Lactiplantibacillus plantarum WB3814 Alleviate LPS-Induced Inflammatory Damage and Apoptosis in A549 Cells - Ji-Yeon Baek; Ji Hun Kim; Na-Kyoung Lee; Hyun-Dong Paik (Probiotics and Antimicrobial Proteins, 2025)

Enhancing cell growth and EPA production in the marine microalga Pavlova lutheri via phytohormone treatment and LED light modulation - So Hee Kim; Ui Hun Lee; Sang Baek Lee; Gwi-Taek Jeong (Journal of Applied Phycology, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Photoreceptors and Circadian Clock Regulators Control Growth and Flowering Under Ionizing Radiation Stress - Sung Won Cho; Wonbok Lee; Seung Sik Lee; Jeong-Il Kim; Young Hun Song (Journal of Plant Biology, 2025)
Plants have evolved mechanisms to optimize flowering time in response to adverse environments, ensuring reproductive success and survival. Although diverse regulatory networks controlling flowering have been identified, the molecular mechanisms by which environmental stresses influence flowering remain poorly understood. In particular, little is known about the impact of ionizing radiation (IR) such as γ-rays. Here, we show that photoreceptors and circadian clock components are crucial for growth and flowering regulation of Arabidopsis thaliana under IR stress. Exposure to 125 Gy of γ-radiation accelerated flowering in wild-type plants, primarily through elevated expression of the floral activator FT , rather than its upstream regulator CO . Plants lacking the blue-light photoreceptor FKF1 exhibited heightened sensitivity to IR. At the same time, the cry1 cry2 mutant, in which a different type of blue light photoreceptor is impaired, exhibited promotion of flowering by IR, although weaker than that observed in fkf1 . Unlike fkf1 and cry1 cry2 , the cry1 cry2 fkf1-2 mutant showed an IR-insensitive flowering phenotype. Similarly, the flowering time of ZTL mutant and overexpression plants was unaffected by IR. The cca1 lhy mutant lost IR-induced flowering promotion and accumulated high H 2 O 2 levels, implicating ROS regulation in IR-responsive flowering. Interestingly, the phyA-211 mutant exhibited extreme growth sensitivity, with severe retardation and anthocyanin accumulation. In contrast to phyA-211 , the phyB-9 mutant showed no significant differences in growth or anthocyanin accumulation compared with the wild type. These findings reveal distinct roles of photoreceptors and circadian clock regulators in coordinating flowering and growth under IR, providing insights into plant adaptation to radiation stress.

Regulation of Autonomic Motility in Human Gastric Muscle and the Gastroepiploic Artery by Stretch and pH - Dae Hoon Kim; Seung Myoung Son; Woong Choi; Chan Hyung Kim; Hun Sik Kim; Ki Bae Kim; Wen-Xie Xu; Sang Jin Lee; Young Chul Kim; Hyo-Yung Yun (Journal of Muscle Research and Cell Motility, 2025)

Application of multi-element isotopes for assessing sedimentary quality within aquaculture systems - Chung-Sook Kim; Young-Shin Go; Min-Seob Kim; Weol-Ae Lim; Dong-Hun Lee (Marine Environmental Research, 2025)

Intranasal nanophotosensitizer enables safe and broad-spectrum photodynamic inactivation of respiratory viruses - Sunmi Han; Assel Seitkazina; Jeongyun Heo; Se-young Kim; SuJin Kim; Sung-Ho Jeon; Yung Hun Park; Taehun Lim; Bohyeon Kim; Shivani Rajoriya; Quy Son Luu; Youngbok Lee; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Infection protective biomimetic wearable strain sensor for laryngeal and articular movement monitoring inspired by epidermal protection and dermal motion detection - Dae Yang Oh; Mun Hwan Lee; Byung Ku Jung; Hyung Jin Choi; Taesung Park; Sang Yeop Lee; Young Kyun Choi; Yoonji Yang; Awais Ali; Seongkeun Oh; Junhyeok Park; Hanseok Seo; et al. (Chemical Engineering Journal, 2025)

New insights into the olfactory development disrupted by 4-tert-Octylphenol in offspring mice - Dong Hun Lee; Hyun Seung Shin; Yun Hee So; Seung Hyun Lee; Jin Yeop Kim; BuHyun Youn; Eun-Hee Lee; Eui-Man Jung (Journal of Hazardous Materials, 2025)

Arsenic removal using foundry dust: Characterization, adsorption mechanisms, and application in acid mine drainage treatment - Hyunsoo Kim; Bum-jun Kim; Myoung-soo Ko; Oh-hun Kwon; Soonjae Lee; Nagchoul Choi; Kanghee Cho (Environmental Research, 2025)

Advances in electrochemical recovery of valuable metals: A focus on lithium - Linitho Suu; Joowan Lim; Jong-Hun Lee; Youngkwon Choi; June-Seok Choi (Desalination, 2025)

Green solvent-based highly permeable PES membranes for virus filtration in bioprocesses - Chang-Hun Kim; Eunwoo Jung; In-Chul Kim; Mi-Hee Ryu; Jung-Hyun Lee; Youngbin Baek; Young Hoon Cho (Chemical Engineering Journal, 2025)

Heat-Killed Lactilactobacillus sakei WB2305 and Lactiplantibacillus plantarum WB2324 Inhibited LPS-Induced Inflammation in Human Airway Epithelial Cells - Ji Hun Kim; Cho Eun Kang; Na-Kyoung Lee; Hyun-Dong Paik (Probiotics and Antimicrobial Proteins, 2025)

Toward new clinical evaluation models for skin longevity: the need for predictive and accelerated approaches - Diala Haykal; Frédéric Flament; Rawad Abdayem; Dong Hun Lee (GeroScience, 2025)

Asymmetric evolution of incised-valley deposits in response to sea-level changes since the Penultimate Glacial Maximum, southeastern Korea - Seok-Hwi Hong; Dong-Geun Yoo; Woo Hun Ryang; Jin Cheul Kim; Gwang-Soo Lee (Quaternary Science Reviews, 2025)

Lacuna-mimic human-derived nasal septal chondrocyte clusters encapsulated in click chemistry-based hydrogel for in vivo cartilage regeneration - Jung Ho Jeon; Seo Young Cheon; Sun Hwa Park; Hyunji Lee; Seung-Yeon Yoo; Min Young Ahn; Donghyun Lee; Man Soo Kim; Jeong Hun Park; Scott J. Hollister; Heebeom Koo; Sung Won Kim (Chemical Engineering Journal, 2025)

Mangano-philic surface formation aided by alkaline-earth metal element for long lasting manganese based zinc aqueous batteries - Junehyuk Son; Orynbay Zhanadilov; Yauhen Aniskevich; Hyeon-Ji Shin; Hun-Gi Jung; Jinhong Park; Kwang Heo; Kyuwook lhm; Kug-Seung Lee; Jae-Hong Lim; Seung-Taek Myung (Chemical Engineering Journal, 2025)

Advanced catalytic support materials featuring polymeric short-side chains for PEM water electrolysis anodes - Jae-Hun Kim; Hye Jin Lee; Soo Youn Lee; Min Su Noh; Eun Jeong Shin; Hwi Jong Jung; Yuri Kim; Hee-Young Park; Hee Soo Kim; Jiye Lee; Eunjik Lee; Eunsung Kan; et al. (Chemical Engineering Journal, 2025)

Exposure and health effects follow-up study of residents near a former smelter site - Young-Hun Kim; Da-Som Lee; Jung-Eum Lee; Heon Kim; Yong-Dae Kim; Young-Seoub Hong; Jung-Duck Park; Byung-Sun Choi (Toxicological Research, 2025)

FDA-hydrolysis activity: A pre-screening tool for optimizing compost selection in standardized plastic biodegradation testing - Hyuni Jung; Sohyeon Park; Seul-A Park; Hyeri Kim; Minkyung Lee; Cheol Hun Park; Jonggeon Jegal; Giyoung Shin; Hyo Jeong Kim (Waste Management, 2025)

Molecular characterization and evolutionary analysis of human adenovirus type 55, related to febrile respiratory illness in the South Korean military - Se Hun Gu; Seung-Ho Lee; Daesang Lee; Dong Hyun Song (Virus Genes, 2025)

Fungal-bacterial interactions leading to increased insect mortality: Trichoderma xixiacum enhances the pathogenicity of Serratia marcescens in Protaetia brevitarsis larvae - Abdelaziz Mansour; Taeho Jeong; Duyoung Lee; Jeong-Hun Song; Eunsun Kim; Dae-Weon Lee; Mohamed Mannaa; Young-Su Seo (Journal of Invertebrate Pathology, 2025)

Genome-wide association mapping of scuticociliatosis resistance in a vaccinated population of olive flounder (Paralichthys olivaceus) - Yasara Kavindi Kodagoda; Gaeun Kim; D.S. Liyanage; W.K.M. Omeka; Cheonguk Park; Jeongeun Kim; Ji Hun Lee; H.A.C.R. Hanchapola; M.A.H. Dilshan; D.C.G. Rodrigo; David B. Jones; Cecile Massault; et al. (Fish & Shellfish Immunology, 2025)

Legacy and emerging persistent organic pollutants in sea turtles from Korean waters: Levels, profiles, and interspecies differences - Yelim Moon; Won Joon Shim; Sung Yong Ha; Gi Myung Han; Mi Jang; Il-Hun Kim; Hae-Rim Lee; Sang Hee Hong (Environmental Research, 2025)

Seasonal variation of groundwater quality and potential risks in U-bearing formations revealed from hydrogeological-microbiological investigation - Jaeyeon Kim; Ye Ji Kim; Suh-Ho Lee; Jiyoon Kim; Won-Tak Joun; Seung-Wook Ha; Sanghoon Lee; Ji-Hun Ryu; Sung-Wook Jeen; Kang-Kun Lee (Environmental Research, 2025)

Saturable intercalation doping enables scalable and selective graphene gas sensors on plastic - Bitnuri Kwon; Jung Hun Lee; Sae Byeok Jo; Jinhyun Hwang; Donggeun Lee; Jonghyun Cha; Soomook Lim; Ji Won Suk; Wi Hyoung Lee (Chemical Engineering Journal, 2025)

Corneal Endothelium Regeneration with Decellularized Porcine Corneal Extracellular Matrix Scaffolds - Cha Yeon Kim; Cholong Jeong; Hun Lee; Changmo Hwang (Tissue Engineering and Regenerative Medicine, 2025)

Integrated source identification of particulate and dissolved organic matter related to anthropogenic activities in an artificial lake system - Seung-Hee Kim; Min-Seob Kim; Jin Hur; Dong-Hun Lee; Kyung-Hoon Shin (Marine Pollution Bulletin, 2025)

Thermochemical conversion of grape marc into carbon-negative syngas - Jung-Hun Kim; Taewoo Lee; Yiu Fai Tsang; Wei-Hsin Chen; Eilhann E. Kwon (Journal of Environmental Management, 2025)

Explainable AI-based risk assessment for pluvial floods over South Korea - Eunmi Lee; Young-Wook You; Young-Hun Jung; Jonghun Kam (Journal of Environmental Management, 2025)

Comprehensive life cycle assessment of powder- vs. granule-form L-lysine production: Evaluating climate impact and sustainability - Danbee Park; Hyunwoo Kim; Sangmin Park; Jina Lee; Dong Hun Kwak; Kwang Soo Shin; Yongchan Lee; Hyaekyoung Kim; Jun-Woo Kim; Wangyun Won (Chemical Engineering Journal, 2025)

Molecular engineering of redox electrolytes for size-matched interfacial coupling with microporous carbon in redox-enhanced electrochemical capacitors - Young Hun Cho; Jinhwan Byeon; Gunwoo Lee; Tae Pyeong Eom; Xiulei Ji; Seung Joon Yoo (Chemical Engineering Journal, 2025)

Evaluation of biohydrogen production potential in sludge by phospholipid fatty acid analysis of microbial communities - Jeong Hyeon Hwang; Suwon Kim; Yeda Lee; Yuni Shin; Suhye Choi; Jinok Oh; Sang-Hyoun Kim; Jeong-Hoon Park; Shashi Kant Bhatia; Yung-Hun Yang (Biomass and Bioenergy, 2025)

Angelica gigas Nakai hot water extracts alleviate IL-6-induced ulcerative colitis by restoring intestinal barrier function - Ye Jin Yang; Min Jung Kim; Ji Woong Heo; Han Nim Choi; Dongbin Lee; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Prevalence and virulence profiles of ESBL-producing Escherichia coli in urinary and blood infections in South Korea - Jong-Hun Ha; Jeong-Ih Shin; Kyu-Min Kim; Jeong-Gyu Choi; Minh Phuong Trinh; Won Jun Anh; Kyung-Min Kang; Hyung-Lyun Kang; Jung-Hyun Byun; Wongwarut Boonyanugomol; Kee Woong Kwon; Myung Hwan Jung; et al. (Folia Microbiologica, 2025)

Conversion of N-doped biochar from carotenoid-extracted Tetraselmis suecica and its application to produce supercapacitors - Se Hun Lee; Kang Hyun Lee; Sang-hwa Lee; Soo Kweon Lee; Ok Sung Jeon; Young Pyo Jeon; Dongpyo Hong; Young Joon Yoo; Sang Yoon Park; Hah Young Yoo (Journal of Environmental Sciences, 2025)

Hourglass-inspired total analysis system for the sensitive colorimetric detection of exosomal miRNA using the CRISPR-Cas12a system with isothermal amplification - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Jeong-Woo Choi; Ha Rim Ahn; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2025)

Rational electrode design for balanced and enhanced ionic and electronic conduction in high-loading all-solid-state batteries - Yunho Lee; Jaecheol Choi; Seok Hun Kang; Young-Gi Lee; Joonwon Lim; Hyeong Min Jin; Ju Young Kim (Chemical Engineering Journal, 2025)

Strategic ligand-induced electronic structure modulation for enhanced nitrogen reduction reaction selectivity in transition metal phthalocyanines - Jae Hun Seol; Seong Chan Cho; Chi Ho Lee; Sang Uck Lee (Chemical Engineering Journal, 2025)

Multi-index-dependent decellularization processes for scalable tissue-specific bioink production - Hye Jin Kim; Ikbum Park; Yoo-mi Choi; Hwanyong Choi; Seong Hun Jeong; Jungbin Yoon; Daekeun Kim; Bo Ram Lee; Jinah Jang (Chemical Engineering Journal, 2025)

Fundamental modeling of microbial electrosynthesis system using porous electrodes for CO2-to-acetate conversion - Minji Kim; Jiin Yoo; Minsoo Kim; Ji Hun Kim; Yonghyun Lee; Huiwon Lee; Hyoung-il Kim; Jungho Jae; Jung Rae Kim; Sang Hwan Son (Bioresource Technology, 2025)

Synergistic effects of synoptic and quasi-biweekly timescale atmospheric circulation patterns on PM2.5 concentration in South Korea - Seyeong Lee; Jeong-Hun Kim; Maeng-Ki Kim; Sang-Hyun Lee; Cheol-Hee Kim (Atmospheric Environment, 2025)

Classification and Key Factors for the Snowfall over the Eastern Part of the Korean Peninsula - Byeong-Hun Hwang; Soojin Yoo; Eun-Chul Chang; Francisco J. Tapiador; Kwonil Kim; GyuWon Lee (Asia-Pacific Journal of Atmospheric Sciences, 2025)

The Use of Surrogate Matrix for Calibrators in the Analysis of Dried Blood Samples – A Feasibility Study - Dong Hun Lee; Iris Xie; Matthew Solomon; Ming Wang; Linlin Luo; Eric Woolf (The AAPS Journal, 2025)

Correction: Angelica gigas Nakai hot water extracts alleviate IL-6-induced ulcerative colitis by restoring intestinal barrier function - Ye Jin Yang; Min Jung Kim; Ji Woong Heo; Han Nim Choi; Dongbin Lee; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Comparative and interface tailoring investigation of solution-processed sulfur/carbon cathode for high-performance liquid and solid-state Li-S batteries - Murugesan Karuppaiah; JeongWoo Bae; ChanSik Son; Hun-Gi Jung; Jong Seong Bae; Jung Kyoo Lee (Chemical Engineering Journal, 2025)

Effects of dietary mineral level and creep feed provision on lactating sows during heat stress - Sang Hun Ha; Min Ju Kim; Jun Young Mun; Abdolreza Hosseindoust; Tajudeen Habeeb Temitope; So Dam Choi; Seon Ah Park; Priscilla Neves Silvestre; Sang Sik Lee; Jin Soo Kim (Tropical Animal Health and Production, 2025)

Efficacy of Human-Induced Pluripotent Stem Cell-Derived Neural Progenitor Cell Replacement Therapy in a Vascular Dementia Animal Model - Jang Hun Kim; Ho-Young Kang; Jihun Lee; Jong-Hoon Kim; Dongho Geum; Dong-Hyuk Park (Tissue Engineering and Regenerative Medicine, 2025)
Background Cell replacement therapy is the only treatment that restores or repairs the function of impaired tissues in neurodegenerative diseases, including vascular dementia (VaD); however, current VaD treatments focus on slowing or mitigating the underlying small vessel disease progression. We aimed to verify the improvement in neurocognition after administering human-induced pluripotent stem cell (hiPSC)-derived neural progenitor cells (NPCs) from in a VaD animal model. Methods After anesthesia, 10–12-week-old male C5BL/6 mice underwent sham or bilateral carotid artery stenosis (BCAS) surgeries. For BCAS, 0.18-mm micro-coils were wound around the bilateral common carotid arteries to induce chronic vascular insufficiency in the global brain. One day after surgery, the mice were administered phosphate buffer solution or NPC from hiPSCs via the tail vein for 15 d, and divided into sham (n = 6), VEH (n = 6), and NPC (n = 7) groups. Three months after the surgery, neurobehavioral tests including the Y-maze test (YMT), passive avoidance test (PAT), and novel object recognition test (NORT) were performed. Finally, mice brains were sectioned for evaluating microglia (Iba-1), astrocyte (GFAP) activation, and myelin (MBP) degeneration through immunohistochemistry (IHC). Results PAT latency ( p = 0.01) and discrimination index in the NORT ( p = 0.043) increased considerably in the NPC group than in the VEH group. However, alterations in YMT were not considerably higher in the NPC group than in the VEH group ( p = 0.65). IHC tests revealed that the GFAP- and IBA-1-positive cell number was remarkably lower in the NPC group than in the VEH group ( p < 0.05). Moreover, MBP density was higher in the NPC group. Conclusion hiPSC-derived NPCs have therapeutic potential in cerebral hypoperfusion VaD mice; it improves the working memory of VaD animals by diminishing inflammatory reactions and protecting them from demyelination.

Effect of temperature and seedling cultivation period on the quality of plug seedlings of four medicinal plant - Eun Won Park; Jeong Hun Hwang; Hee Sung Hwang; Ji Hye Yun; So Yeong Hwang; Jin Yu; Hyeong Eun Choi; Jeong Kil Koo; Eun Song Lee; Kyung Sook Han; Young Ho Yoon; Seung Jae Hwang (Horticulture, Environment, and Biotechnology, 2025)

The Roles of MYC2 Transcription Factor in JA-Signaling Pathway in Plants - Young-Hun Kim; Chan-Woo Park; Kwang Min Lee; Chang-Oh Hong; Hong-Joo Son; Keun Ki Kim; Hyeon Cheal Park; Yu-Jin Kim (Journal of Plant Biology, 2025)

Coupled simulation for pin-wise reactor core analysis using subchannel analysis code CUPID and fuel performance code GIFT - Yeong Hun Lee; Jangkeun Park; Youyeon Choi; Kyuseok Sim; Youho Lee; Hyoung Kyu Cho (Annals of Nuclear Energy, 2025)

Correction to: Development of a lateral flow immunochromatographic assay for the detection of Lactococcus garvieae in grey mullet (Mugil cephalus) - Choon-Sup Kim; Sung-Hun Lee; Myoung Sug Kim; Kyoung-Hui Kong; Hwi-Jin Kim; Gee-Wook Shin; Wi-Sik Kim (Aquaculture International, 2025)

Influence of temperature on growth and reproduction of keystone species, Crangon hakodatei (Caridea, Crangonidae) in the East Sea of Korea - In Ok Lee; Hyeong-Gi Kim; Junsung Noh; Jong Hun Na; Chul-Woong Oh; Jong Seong Khim (Marine Pollution Bulletin, 2025)

Corrigendum to “Spatiotemporal patterns of water volume and total organic carbon concentration of agricultural reservoirs over South Korea” [Water Research, Volume 256, 1 June 2024, 121610] - Kwang-Hun Lee; Jonghun Kam (Water Research, 2025)

Expression profiling and functional role of cyclooxygenase-2 in the immune and inflammatory responses of red-spotted grouper (Epinephelus akaara) - Yasara Kavindi Kodagoda; H.A.C.R. Hanchapola; D.C.G. Rodrigo; Chaehyun Lim; D.S. Liyanage; W.K.M. Omeka; G.A.N.P. Ganepola; M.A.H. Dilshan; Jeongeun Kim; Ji Hun Lee; Taehyug Jeong; Qiang Wan; et al. (Fish & Shellfish Immunology, 2025)

Biofilm comes back: Controlling regrowth by mitigating the cell-matrix interaction - Yu-Heng Deng; Joo Hun Lee; Myung-Joo Kim; Hyunjoon Kong (Chemical Engineering Journal, 2025)

Significance of the relationship between the alkyl side-chain lengths of diketopyrrolopyrrole-based polymers and their thermoelectric properties - Su Hyeon Cho; Jong-Woon Ha; Chang Eun Song; Young Hun Kang; Mijeong Han; Sangwook Lee; Byoungwook Park (Chemical Engineering Journal, 2025)

Combined Treatment of Metformin and Resveratrol Promotes Myogenesis Through Increased Irisin Release in C2C12 Cells - Eun Ji Seong; Yejin Kim; Zheng-Yuan Su; Hee-Taik Kang; Jong Hun Lee (Pharmaceutical Research, 2025)

Ecological risk assessment of p-toluidine in freshwater, sediment, and soil media - Inhye Lee; Daeyeop Lee; Hun-Je Jo; Hyun Soo Kim; Kyung Sook Woo; Kyunghee Ji (Ecotoxicology, 2025)

Single-cell nanoencapsulation enables fabrication of probiotics-loaded hydrogel dressing with improved wound healing efficacy in vivo - Jung Suk Kim; Beom Jin Kim; Sang Min Lee; Insung S. Choi; Ji Hun Park; Han-Gon Choi; Sung Giu Jin (Journal of Pharmaceutical Investigation, 2025)

Stiffness evaluation of semi-rigid connection using steel clamps in plastic greenhouse structure - Sangik Lee; Jong-hyuk Lee; Byung-hun Seo; Dong-su Kim; Dongwoo Kim; Yerim Jo; Won Choi (Biosystems Engineering, 2025)

Water and gas geochemistry of springs in Ulleungdo volcano, South Korea: Implications for degassing of upper mantle-derived volatiles in Northeast Asia - Wonhee Lee; Hyunwoo Lee; Heejun Kim; Jung-Hun Song; Jungpyo Hong; Jonghoon Park; Hyejung Jung; Jeonghoon Lee; Naoto Takahata; Yuji Sano; Tobias P. Fischer (Journal of Hydrology, 2025)

Common-mode noise separation in distributed acoustic sensing vertical seismic profile data: A self-supervised deep learning approach with enhanced blind network - Yeonghyeon Son; Byoungjoon Yoon; Kitaek Hong; Myung-hun Lee; Juan Lee; Sang-Jin Choi (Journal of Applied Geophysics, 2025)

Effects of long-term treatment with low concentration butylparaben on prostate organoids - Yujin Hwang; Yejin Kim; Dongkyu Choi; Jong Hun Lee (Environmental Pollution, 2025)

Impact of administration routes and dose frequency on the toxicology of SARS-CoV-2 mRNA vaccines in mice model - Jae-Hun Ahn; Jisun Lee; Gahyun Roh; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Kang-Min Han; Ji-Eun Kim; Hyo-Jung Park; Soyeon Yoo; Sung Pil Kwon; Eun-Kyoung Bang; et al. (Archives of Toxicology, 2025)
The increasing use of SARS-CoV-2 mRNA vaccines has raised concerns about their potential toxicological effects, necessitating further investigation to ensure their safety. To address this issue, we aimed to evaluate the toxicological effects of SARS-CoV-2 mRNA vaccine candidates formulated with four different types of lipid nanoparticles in ICR mice, focusing on repeated doses and administration routes. We conducted an extensive analysis in which mice received the mRNA vaccine candidates intramuscularly (50 μg/head) twice at 2-week intervals, followed by necropsy at 2 and 14 dpsi (days post-secondary injection). In addition, we performed a repeated dose toxicity test involving three, four, or five doses and compared the toxicological outcomes between intravenous and intramuscular routes. Our findings revealed that all vaccine candidates significantly induced SARS-CoV-2 spike protein-specific IgG and T cell responses. However, at 2 dpsi, there was a notable temporary decrease in lymphocyte and reticulocyte counts, anemia-related parameters, and significant increases in cardiac damage markers, troponin-I and NT-proBNP. Histopathological analysis revealed severe inflammation and necrosis at the injection site, decreased erythroid cells in bone marrow, cortical atrophy of the thymus, and increased spleen cellularity. While most toxicological changes observed at 2 dpsi had resolved by 14 dpsi, spleen enlargement and injection site damage persisted. Furthermore, repeated doses led to the accumulation of toxicity, and different administration routes resulted in distinct toxicological phenotypes. These findings highlight the potential toxicological risks associated with mRNA vaccines, emphasizing the necessity to carefully consider administration routes and dosage regimens in vaccine safety evaluations, particularly given the presence of bone marrow and immune organ toxicity, which, though eventually reversible, remains a serious concern.

Development of a lateral flow immunochromatographic assay for the detection of Lactococcus garvieae in grey mullet (Mugil cephalus) - Choon-Sup Kim; Sung‑Hun Lee; Myoung Sug Kim; Kyoung-Hui Kong; Hwi-Jin Kim; Gee-Wook Shin; Wi-Sik Kim (Aquaculture International, 2025)

Role of factors controlling diurnal variation of cold-season formaldehyde during Satellite Integrated Joint Monitoring of Air Quality 2021 campaign - Lim-Seok Chang; Soi Ahn; Min-Suk Bae; Seung-Myung Park; Junsu Gil; Kwang-Rae Kim; Gangwoong Lee; Taehyoung Lee; Jung-Hun Woo; Rokjin Park; Hyeong-Ahn Kwon; Gyo-Hwang Choo; et al. (Science of The Total Environment, 2025)

Symmetric and asymmetric non-fullerene acceptors cooperate synergistically for ternary optoelectronic devices - Minyoung Lim; Xiaoling Ma; Yelim Kang; Min Hun Jee; Soonyong Lee; Sang Young Jeong; Tae Hyuk Kim; Jae Won Shim; Fujun Zhang; Han Young Woo (Chemical Engineering Journal, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Thermochemical processing for the sustainable disposal of spent filter waste - Taewoo Lee; Jung-Hun Kim; Jaewon Lee; Eilhann E. Kwon (Chemosphere, 2024)

Apportioning sources of natural and anthropogenic organic matter in sediment from Lake Shihwa: An integrated approach using molecular ratios and compound-specific stable-isotope analysis - Rincheon Jeon; Seung-Hee Kim; Dong-Hun Lee; Yusang Cho; Youngnam Kim; Seongjin Hong; Kyung-Hoon Shin (Marine Pollution Bulletin, 2024)

Maternal exposure to 4-tert-octylphenol causes alterations in the morphology and function of microglia in the offspring mouse brain - Seung Hyun Lee; Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Beum-Soo An; Geun-Shik Lee; Eui-Man Jung (Journal of Hazardous Materials, 2024)

Inter-annual changes in transboundary air quality from KORUS-AQ 2016 to SIJAQ 2022 campaign periods and assessment of emission reduction strategies in Northeast Asia - Min-Jun Park; Seung-Hee Baek; Hyo-Jung Lee; Hyun-Young Jo; Cheol-Hee Kim; Jin-Seok Kim; Jung-Hun Woo; Rokjin Park; Jong-Jae Lee; Chang-Keun Song; Jung-Woo Yoo; Lim-Seok Chang; et al. (Environmental Pollution, 2024)

Optimizing active chilled beam systems in the South Korean Climate: Comparative analysis of cooling energy and thermal comfort by set-point temperature - Jun Kyu Park; Sang Hun Yeon; Chul Ho Kim; Yeobeom Yoon; Jin Woo Moon; Kwang Ho Lee (Energy and Buildings, 2024)

Effects of horizontal resolution and updated surface data on simulated low-level winds for the aviation safety over Incheon International Airport - Hyeon-Ji Lee; Hyeyum Hailey Shin; Kyo-Sun Sunny Lim; Sang-Hun Park (Atmospheric Research, 2024)

Discriminative characteristics of hydrochemical components and sedimentary organic matter in Korean coastal aquaculture systems during summer - Seung-Hee Kim; Sung-Eun Park; Chung-Sook Kim; Dong-Hun Lee (Frontiers in Marine Science, 2024)
Understanding the spatial distribution and sources of sedimentary organic matter (OM) in coastal environments is crucial for effective water quality management and the preservation of ecosystem health. Although extensive research has been conducted on OM dynamics, there remains a gap in understanding the ongoing biogeochemical processes in Korean coastal aquaculture zones, particularly during the summer season. To address this gap, we investigated the spatial variation of water chemical properties and isotopic composition of sedimentary OM to trace the composition, source, and reactivity of mixed OM in aquaculture systems along the Korean coast during the summer season. The isotopic approach was applied to surface sediments from five sections: western (W)-1, W-2, southern (S)-1, S-2, and eastern (E)-1. With respect to increased nutrients (mainly nitrate; 1.2 ± 0.6 mg/L) by dam-water discharge near W sections, our isotopic signatures revealed that a substantial fraction of sedimentary OM might dominantly originated from autochthonous OM source (algae; 36.5%) related to the increase of terrestrial nutrients. Simultaneously, the deposition of allochthonous OM (aquacultural feces; 44%) was predominant in the S-2 sections. The 34 S-depleted patterns (approximately -7.2‰) in the S-2 section was indicative of active sulfate reduction occurring at the sedimentary boundary. Therefore, together with the precise determination of ongoing OM, our isotopic results provide valuable insights for effectively managing water-sedimentary qualities under the increase of anthropogenic contamination.

Hydrogen-bonded QSEBS/ZrO2 mixed matrix anion exchange membranes for water electrolyzer - Ji Eun Kim; Young Hwa Yun; Hyeonjung Park; Justin Albers; Gisu Doo; Sechan Lee; Jongsu Seo; Changsoo Lee; MinJoong Kim; Hyun-Seok Cho; Sang-Kyung Kim; Jae Hun Lee; et al. (Fuel, 2024)

Nanometer-scale tunable mesopores in silica fillers for facile enhancement of epoxy adhesion - Chae Yeon Lee; Min Jeong Kim; Sun Hwan Jeong; Dai-Hwan Kim; Jennifer Kezia Soegijopranoto; Hui Hun Cho; Jun Hyuk Heo; Jung Heon Lee (Chemical Engineering Journal, 2024)

Ground Salicornia herbacea Powder Suppresses AOM/DSS-induced Colon Cancer by Inhibiting Wnt/β-catenin Signaling and Nrf2 - Yeonoh Cho; Ji Hyeon Cha; Yujin Hwang; Hee-Taik Kang; Jong Hun Lee (Pharmaceutical Research, 2024)

Exploring gender differences in pharmacokinetics of central nervous system related medicines based on a systematic review approach - Seung-Min Lee; Ji-Hun Jang; Seung-Hyun Jeong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)

Removal of livestock odor gas ammonia, hydrogen sulfide, methanethiol by electron beam in a continuous flow system - Dong-Woo Kim; Sang-Hee Jo; Jieun Son; Seungho Yu; Tae-Hun Kim; Meehye Lee; Tak-Hyun Kim (Journal of Environmental Chemical Engineering, 2024)

Purification, identification and molecular docking studies of antioxidant and anti-inflammatory peptides from Edible Bird's Nest - Chia Hau Lee; Norfadilah Hamdan; Bemgba Bevan Nyakuma; Syie Luing Wong; Keng Yinn Wong; Huiyi Tan; Haryati Jamaluddin; Ting Hun Lee (Food Chemistry, 2024)

Prediction of food materials for the management of respiratory symptoms targeting PDE4B and NMDAR via machine learning approach - Jihyeon Jung; Seo Hyun Shin; Jong Hun Kim; Jung Han Yoon Park; Ki Won Lee (Food Bioscience, 2024)

Advancement of biocrude valorization to fuels: A comprehensive review - Jung-Hun Kim; Minyoung Kim; Gyeongnam Park; Jee Young Kim; Jechan Lee; Eilhann E. Kwon (Chemical Engineering Journal, 2024)

Enhancing flood wave modelling of reservoir failure: a comparative study of structure-from-motion based 2D and 3D methodologies - Jong-hyuk Lee; Sang-ik Lee; Youngjoon Jeong; Byung-hun Seo; Dong-su Kim; Ye-jin Seo; Younggu Her; Won Choi (Natural Hazards, 2024)
Predicting flood wave propagation from reservoir failures is critical to practical flood hazard assessment and risk management. Flood waves are sensitive to topography, channel geometry, structures, and natural features along floodplain paths. Thus, the accuracy of flood wave modelling depends on how precisely those features are represented. This study introduces an enhancing approach to flood wave modelling by accurately representing three-dimensional objects in floodplains using the structure-from-motion (SfM). This method uses an unmanned aerial vehicle to capture topographic complexities and account for ground objects that impact flood propagation. Using the three-dimensional volume of fluid numerical approach significantly improves an enhanced representation of turbulent flow dynamics and computational efficiency, especially in handling large topography datasets. Reproductions from this enhanced three-dimensional approach were validated against recent reservoir failure observations and contrasted with traditional two-dimensional models. The results revealed that the suggested three-dimensional methodology achieved a significant 84.4% reproducibility when juxtaposed with actual inundation traces. It was 35.5%p more accurate than the two-dimensional diffusion wave equation (DWE) and 17.1%p more than the shallow water equation (SWE) methods in predicting flood waves. This suggests that the reproducibility of the DWE and SWE decreases compared to the three-dimensional approach when considering more complex floodplains. These results demonstrate that three-dimensional flood wave analysis with the SfM methodology is optimal for effectively minimising topographic and flood wave reproduction errors across extensive areas. This dual reduction in errors significantly enhances the reliability of flood hazard assessments and improves risk management by providing more precise and realistic predictions of flood waves.

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

Dual suppressive effect of p-coumaric acid on pigmentation in B16F10 cells - Sohee Jang; Chang-Woo Ha; Sung-Hyeok Kim; Jung Hun Choi; Seung Namkoong; Sungsil Hong; Hyun Jung Koo; Youn-Kyu Kim; Mediana Hadiwidjaja; Sung Ryul Lee; Eun-Hwa Sohn (Molecular & Cellular Toxicology, 2024)

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

Functional use of carbon dioxide for the sustainable valorization of orange peel in the pyrolysis process - Jung-Hun Kim; Taewoo Lee; Yiu Fai Tsang; Deok Hyun Moon; Jechan Lee; Eilhann E. Kwon (Science of The Total Environment, 2024)

Conversion of toxic pyrogenic products into syngas through catalytic pyrolysis of insulation material waste under the presence of CO2 - Jung-Hun Kim; Taewoo Lee; Jaewon Lee; Hyeseung Choi; Eilhann E. Kwon (Journal of Hazardous Materials, 2024)

Different diversity patterns of butterfly and moth assemblages between deciduous and evergreen broad-leaf forests - Na-Hyun Ahn; Sang-Hun Lee; Sang-Hak Han; Sei-Woong Choi (Journal of Asia-Pacific Entomology, 2024)

A new integrated framework to fault detection and diagnosis of air handling unit: Emphasizing the impact of symptoms - Jae Hwan Cha; Jun Kyu Park; Chang Hyeon Chi; Sang Hun Yeon; Chul Ho Kim; Jin Woo Moon; Kwang Ho Lee (Energy and Buildings, 2024)

Single atom catalyst induced by redox reaction between iron ion and aniline monomer - Yeongeun Choi; T.B. Ngoc Huynh; Seungmin Lee; Jongmin Lee; Yung-Eun Sung; Hyukjae Choi; Yong-Hun Cho; Seunghoe Koo; Kyeongtae Kim; Oh Joong Kwon (Chemical Engineering Journal, 2024)

Breakthrough innovations in carbon dioxide mineralization for a sustainable future - Ramesh Kumar; Woo Jin Chung; Moonis Ali Khan; Moon Son; Young-Kwon Park; Sang Soo Lee; Byong-Hun Jeon (Reviews in Environmental Science and Bio/Technology, 2024)

Enhanced oxidation of parabens in an aqueous solution by air-assisted cold plasma - Hee-Jun Kim; Tae-Hun Lee; Youngpyo Hong; Jae-Cheol Lee; Hyun-Woo Kim (Chemosphere, 2024)

Efficient two-way fluid–structure interaction simulation for performance prediction of pressure-compensating emitter - Byung-hun Seo; Sangik Lee; Jong-hyuk Lee; Dong-su Kim; Ye-jin Seo; Dong-woo Kim; Won Choi (Biosystems Engineering, 2024)

Exploring green solvents for the sustainable fabrication of bio-based polylactic acid membranes using nonsolvent-induced phase separation - Tunmise Ayode Otitoju; Chang-Hun Kim; Mihee Ryu; Jaesung Park; Tae-Kyung Kim; Youngmin Yoo; Hosik Park; Jung-Hyun Lee; Young Hoon Cho (Journal of Cleaner Production, 2024)

Valorization of battery manufacturing wastewater: Recovery of high-value metal ions through reaction-enhanced membrane cascade - Jeong Han Shin; Seung Hwan Kim; Cheol Hun Yoo; Ho Jun Lee; Bao Tran Duy Nguyen; Go Gi Lee; Jeong F. Kim; Jong Suk Lee (Chemical Engineering Journal, 2024)

Animal-free scaffold from brown algae provides a three-dimensional cell growth and differentiation environment for steak-like cultivated meat - Heejae Lee; Dasom Kim; Kyeong Hun Choi; Sangmin Lee; Minguk Jo; Song-Yi Chun; Yebin Son; Jong Ha Lee; Kwanhyeong Kim; TaeByung Lee; Joonho Keum; Min Yoon; et al. (Food Hydrocolloids, 2024)

Investigating the impact of control strategies on the sulfur dioxide emissions of South Korean industrial facilities using an aircraft mass balance approach - Gracie Wong; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; Beom-Keun Seo; et al. (Atmospheric Environment, 2024)

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

In silico identification and expression analysis of superoxide dismutases in Tenebrio molitor - Ho Am Jang; Hyeonjun Shin; Seo Jin Lee; Sung Min Ku; Jae Hui Kim; Dong Woo Kang; So Yeon Choi; Sang Mok Jung; Hyun Woung Shin; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Spatiotemporal patterns of water volume and total organic carbon concentration of agricultural reservoirs over South Korea - Kwang-Hun Lee; Jonghun Kam (Water Research, 2024)

Hydrophobicity and membrane distillation performance of glass fiber membranes modified by dip coating of pure PDMS - Minsu Pyo; Sanghyun Jeong; Jae Hun Kim; Min Jung Jeon; Eui-Jong Lee (Journal of Environmental Chemical Engineering, 2024)

A sustainable bioprocessing system leveraging gas fermentation and bipolar membrane electrodialysis system for direct recovery of acetic acid - Mungyu Lee; Jae-Hun Kim; Muhammad Yasin; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2024)

Algal biomass-based zero-waste biorefinery for producing optically pure (R)-γ-valerolactone and carbonaceous electrodes applicable for energy storage devices - Jaehyun Cha; Chang-Hun Lim; Jeongmi Lee; Jin-Kyu Lim; Minyoung Kim; Won-Kun Park; Changmin Sung; Hyun-Kyung Kim; Kyoungseon Min (Chemical Engineering Journal, 2024)

Photo-crosslinking and layer-by-layer processed organic photodetectors with remarkably suppressed dark current - Min Hun Jee; Byoungwook Park; Ah Young Lee; Seunghyun Rhee; Minyoung Lim; Jung Min Ha; Nayoung Kim; Fujun Zhang; Jong‐Woon Ha; Hyungju Ahn; Jong H. Kim; Mijeong Han; et al. (Chemical Engineering Journal, 2024)

Approaching high rate All-Solid-State Lithium-Sulfur batteries via promoted sulfur conversion with nickel oxide nanoparticle electrocatalyst - Seok Hun Kang; Won-Gwang Lim; Liangliang Xu; Donghyeok Son; Young-Gi Lee; Jinwoo Lee (Chemical Engineering Journal, 2024)

Population pharmacokinetic modeling of levodropropizine: extended application to comparative analysis between commercial formulations and exploration of pharmacokinetic effects of diet - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Impact of typhoons on anthropogenic nitrogen sources in Lake Sihwa, South Korea - Seung-Hee Kim; Min-Seob Kim; Dong-Hun Lee; Kyung-Hoon Shin (Marine Pollution Bulletin, 2024)

Improvement of the anthropogenic emission rate estimate in Ulaanbaatar, Mongolia, for 2020–21 winter - Hyung-Min Lee; Eunlak Choi; Yong Pyo Kim; Tseren-Ochir Soyol-Erdene; Amgalan Natsagdorj; Zhijun Wu; Mijung Song; Changhyuk Kim; Kyoung-Soon Jang; Junyoung Ahn; Atsushi Matsuki; Esmatullah Torabi; et al. (Environmental Pollution, 2024)

Selective in-situ water removal by polybenzoxazole hollow fiber membrane for enhanced CO2 methanation - Eun-Young Kim; Myeong-Hun Hyeon; Hyun Wook Hwang; Ji Young Lee; Seok Ki Kim; Youn-Sang Bae; Su-Young Moon (Chemical Engineering Journal, 2024)

In silico identification and expression analyses of peroxidases in Tenebrio molitor - Ho Am Jang; Sung Min Ku; Jae Hui Kim; Sang Mok Jung; Jongdae Lee; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Adsorption effects of electron scavengers and inorganic ions on catalysts for catalytic oxidation of sulfamethoxazole in radiation treatment - Kang Lee; Tae-Hun Kim; Sang-Hee Jo; Seungho Yu (Chemosphere, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Atomic-level insights into bioinspired Fe/Ni bimetallic active sites on carbon nitrides for electrocatalytic O2 evolution - Yunseok Shin; Seong Chan Cho; Gilsoo Park; Jae Hun Seol; Dongwook Lim; Subin Choi; Changbum Jo; Sung Hyeon Baeck; Jongwoo Lim; Sang Uck Lee; Sungjin Park (Chemical Engineering Journal, 2024)

Evaluation of acute, 28-day, 13-week repeated dose oral toxicity and genotoxicity of a herbal extract (HemoHIM G) from Angelica sinensis, Ligusticum chuanxiong, and Peaonia lactiflora - Su-Bin Bak; Hansol Choi; Gyoung-Deuck Kim; Ju Gyeong Kim; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2024)
HemoHIM G is a functional food ingredient composed of a triple herbal combination of Angelica sinensis , Ligusticum chuanxiong , and Paeonia lactiflora , to improve impaired immune function. Considering the pharmacological benefits of its constituent herbal components, HemoHIM G is anticipated to have various health benefits; however, its toxicity has not been thoroughly evaluated. Here, we conducted a comprehensive study to assess the safety of HemoHIM G in terms of acute oral toxicity, 13-week repeat-dose toxicity, and genotoxicity. In the oral acute toxicity study, Sprague–Dawley rats were orally administered a single dose of HemoHIM G at 5000 mg/kg/day, the limit dose for the acute study. No abnormal findings or adverse effects were observed in this study, as confirmed by gross pathology. A 13-week repeated-dose toxicity study was conducted with HemoHIM G at doses of 1250, 2500, and 5000 mg/kg/day to examine the subchronic toxicity in both male and female rats after 28 days of dose-range finding study. No test substance-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology were within normal ranges, further supporting the safety of HemoHIM G. Therefore, the NOAEL of HemoHIM G was considered to be at 5000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronuclei test were conducted to identify the potential genotoxicity of HemoHIM G. HemoHIM G is non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence for the safe use of HemoHIM G as a functional food ingredient.

Pharmacological effects of pentacyclic triterpenoids isolated from Centella asiatica - Dong-Hyun Min; Young-Beom Yu; Tae-Hun Kim; Hoon Kim; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2024)
Centella asiatica (CA) is one of the most popular traditional herbal medicines worldwide. It has been used for centuries in many countries, especially for curing skin damage, and is now applied to treat various human diseases. There are various types of triterpenoids from Centella asiatica , with four pentacyclic triterpenoids with the main properties being shown by four pentacyclic triterpenoids: asiaticoside, madecassoside, asiatic acid, and madecassic acid. These terpenoids have similar structures, however each has a slightly different properties. Asiaticoside, madecassoside, asiatic acid, and madecassic acid are synthesized through the isoprenoid pathway known as mevalonate pathway to produce hydrophobic triterpenoid structures (aglycone) which contain hydrophilic sugar chains (glycone). Furthermore, asiaticoside and madecassoside are distinguished by a glycone, and asiatic acid and madecassic acid are distinguished by a aglycone. These pentacyclic triterpenoids have a wide spectrum of beneficial effects and have been used as anti-inflammatories, skin wound treatments, scar treatments, and cosmetics agents. This review aimed to provide a description of the four compounds, of their structure, pharmacological properties, applications in the treatment of various diseases, known mechanisms of action, and commentary on industrial applications.

Enhanced mono-aromatics production by the CH4-assisted pyrolysis of microalgae using Zn-based HZSM-5 catalysts - Abid Farooq; Gwang Hoon Rhee; Haneul Shim; Behzad Valizadeh; Jechan Lee; MoonisAli Khan; Byong-Hun Jeon; Seong-Ho Jang; Yong Jun Choi; Young-Kwon Park (Chemosphere, 2024)

Corrigendum to “Optimizing an airborne mass-balance methodology for accurate emission rate quantification of industrial facilities: A case study of industrial facilities in South Korea” [Sci. Total Environ. vol. 912, 169204] - Gracie Wong; Hui Wang; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; et al. (Science of The Total Environment, 2024)

Arctic/North Atlantic atmospheric variability causes Severe PM10 events in South Korea - Jeong-Hun Kim; Maeng-Ki Kim; Seong-Joong Kim; Joo-Hong Kim; Sang-Wook Yeh; Sang-Hyun Lee; Youngseok Lee (Science of The Total Environment, 2024)

Urinary metabolite biomarkers of pregnancy complications associated with maternal exposure to particulate matter - Sunwha Park; Minki Shim; Gain Lee; Young-Ah You; Soo Min Kim; Young Min Hur; Hyejin Ko; Mi Hye Park; Sung Hun Na; Young-Han Kim; Geum Joon Cho; Jin-Gon Bae; et al. (Reproductive Toxicology, 2024)

Seasonal and geographical variations in the community structure of environmentally-transmitted symbiotic bacteria in Riptortus pedestris (Hemiptera: Alydidae) - Joo-Young Kim; Do-Hun Gook; Minhyung Jung; Doo-Hyung Lee (Journal of Asia-Pacific Entomology, 2024)

Wearable ion gel based pressure sensor with high sensitivity and ultra-wide sensing range for human motion detection - Ji Eun Hyun; Taehwan Lim; Seong Hun Kim; Joo Hyung Lee (Chemical Engineering Journal, 2024)

Positive effect of phasin in biohydrogen production of non polyhydroxybutyrate-producing Clostridium acetobutylicum ATCC 824 - Jeong Hyeon Hwang; Hyun Joong Kim; Suwon Kim; Yeda Lee; Yuni Shin; Suhye Choi; Jinok Oh; Sang-Hyoun Kim; Jeong-Hoon Park; Shashi Kant Bhatia; Yun-Gon Kim; Kyoung-Soon Jang; et al. (Bioresource Technology, 2024)

Estimating three-dimensional current fields in the Yeosu Bay using coastal acoustic tomography system - Yerin Hwang; Eun-Joo Lee; Hajin Song; Byoung-Nam Kim; Ho Kyung Ha; Yohan Choi; Jae-Il Kwon; Jae-Hun Park (Frontiers in Marine Science, 2024)
Observation of current speeds in coastal seas is crucial because it can provide useful information for ship operations, fishing activities, and rapid responses to marine disasters. Coastal acoustic tomography (CAT) is a technology that can continuously monitor environmental changes such as current velocity and water temperature using reciprocal acoustic signals between CAT stations in coastal seas. This technology is different from traditional pointwise or intermittent sectional observations in that it can produce time-varying two- or three-dimensional current fields. The results of previous studies using CAT systems have been limited to reproducing horizontal maps of depth-averaged two-dimensional current fields. Utilizing results from a high-resolution coastal ocean model, this study developed a novel technique for estimating three-dimensional (3-D) current fields by combining the inverse method with an artificial intelligence (AI) model. Following three steps are the procedure for the test of estimating the 3-D current fields. First, utilizing the ray tracing model ‘Bellhop,’ reciprocal travel times among five CAT stations using the coastal ocean model outputs are computed. These five stations correspond to the locations where in-situ CAT systems were established for continuous monitoring of current changes in Yeosu Bay, Korea. Subsequently, the range-averaged currents at the five layers were estimated by incorporating this travel time difference data into an AI model trained using the same coastal ocean model outputs. Finally, the inverse method is applied to each layer to estimate the 3-D current fields. The validation results revealed that the newly developed method performed well in both summer and winter. Time-varying two-layer-like current fields were reasonably produced, occasionally revealing an out-of-phase relationship between the upper and lower layers depending on the tidal phases. This method yielded average root-mean-squared errors of less than 4 cm/s on six simulation paths for acoustic signal propagation. Furthermore, when the same method was applied to in-situ CAT observations, the average correlation coefficient (R) of the along-channel current of each layer was found to be approximately 0.9 or higher. These results suggest that this novel method can be effectively applied to the continuous monitoring of 3-D current fields in coastal seas using a CAT system.

Sex differences in 4-tert-octylphenol toxicokinetics: Exploration of sex as an effective covariate through an in vivo modeling approach - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Toxicology, 2024)

Ellagic acid treatment during in vitro maturation of porcine oocytes improves development competence after parthenogenetic activation and somatic cell nuclear transfer - Han-Bi Lee; Seung-Eun Lee; Min-Jee Park; Dong-Hun Han; Eun-Seo Lim; Bokyeong Ryu; Eun-Young Kim; Se-Pill Park (Theriogenology, 2024)

Optimizing an airborne mass-balance methodology for accurate emission rate quantification of industrial facilities: A case study of industrial facilities in South Korea - Gracie Wong; Hui Wang; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; et al. (Science of The Total Environment, 2024)

Acid-site control of ZSM-5 zeolites using quaternary ammonium hydroxides for shale gas dehydroaromatization - Yangho Jeong; Yong Hyun Lim; Eun Ji Choi; Hae Won Ryu; Jangeon Roh; Susung Lee; Minkee Choi; Do Heui Kim; Jong Hun Kang (Chemical Engineering Journal, 2024)

Atelocollagen Scaffold Enhances Cartilage Regeneration in Osteochondral Defects: A Study in Rabbits - Ji-Chul Yoo; Man Soo Kim; Sueen Sohn; Sang Hun Woo; Yu Ri Choi; Andrew S. Kwak; Dong Shin Lee (Tissue Engineering and Regenerative Medicine, 2024)

Correction: Improvement and Analysis for Accuracy of Baseflow Using SWAT-CUP Premium in the Yongjeon Stream, South Korea - Jong-Tae Kim; Chang-Hun Lee; Namjoo Lee (Pure and Applied Geophysics, 2024)

Modeling population pharmacokinetics of morniflumate in healthy Korean men: extending pharmacometrics analysis to niflumic acid, its major active metabolite - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effects of repetitive transcranial magnetic stimulation on improving cerebral blood flow in patients with middle cerebral artery steno-occlusion - Kisoo Pahk; Sang-Hun Lee (Acta Neurologica Belgica, 2024)

Predicting rapid intensification of tropical cyclones in the western North Pacific: a machine learning and net energy gain rate approach - Sung-Hun Kim; Woojeong Lee; Hyoun-Woo Kang; Sok Kuh Kang (Frontiers in Marine Science, 2024)
In this study, a machine learning (ML)-based Tropical Cyclones (TCs) Rapid Intensification (RI) prediction model has been developed by using the Net Energy Gain Rate Index ( NGR ). This index realistically captures the energy exchanges between the ocean and the atmosphere during the intensification of TCs. It does so by incorporating the thermal conditions of the upper ocean and using an accurate parameterization for sea surface roughness. To evaluate the effectiveness of NGR in enhancing prediction accuracy, five distinct ML algorithms were utilized: Decision Tree, Logistic Regression, Support Vector Machine, K-Nearest Neighbors, and Feed-forward Neural Network. Two sets of experiments were performed for each algorithm. The first set used only traditional predictors, while the second set incorporated NGR . The outcomes revealed that models trained with the inclusion of NGR exhibited superior performance compared to those that only used traditional predictors. Additionally, an ensemble model was developed by utilizing a hard-voting method, combining the predictions of all five individual algorithms. This ensemble approach showed a noteworthy improvement of approximately 10% in the skill score of RI prediction when NGR was included. The findings of this study emphasize the potential of NGR in refining TC intensity prediction and underline the effectiveness of ensemble ML models in RI event detection.

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Impact of Typhoon Nanmadol (2011) on the propagation of nonlinear internal waves in the South China Sea - Chanhyung Jeon; Kang-Nyeong Lee; Qiang Li; Jae-Hun Park (Frontiers in Marine Science, 2024)
In situ measurements from an array of pressure-equipped inverted echo sounders (PIESs), numerical simulation results using a non-hydrostatic model (SUNTANS) that does not account for mesoscale variability, and a ray-tracing method are used to investigate the behavior of nonlinear internal waves (NLIWs) in the South China Sea, focusing on period of Typhoon Nanmadol passage. Unusual significant differences in NLIWs arrival time occur between the PIES observation and SUNTANS simulation results after Typhoon Nanmadol passage; i.e., the observed NLIWs show a delay of 0.5–1.5 h at the westernmost PIES sites compared to the simulated ones in the SUNTANS. A data-assimilated ocean model outputs in addition to satellite altimetry reveal that the passage of Typhoon Nanmadol alters the oceanic environments remarkably, creating thermocline shoaling of ~80 m, which can slow down the wave propagation speed. We account for the delay of NLIWs using ray-tracing simulations. Our results demonstrate that typhoon-induced changes in mesoscale structure can significantly impact the fate of NLIWs in the South China Sea, which have potential on ocean mixing and biogeochemical systems.

Development of a duplex qPCR assay for the detection of coinfection in eels by Japanese eel endothelial cell-infecting virus and Anguillid herpesvirus-1 - Hyoun Joong Kim; S.D.N.K. Bathige; Hyung-Bae Jeon; Seung-Hyeon Kim; Chen Yu; Woonchul Kang; Kangrae Noh; Eunil Lee; Byeong Seong Lim; Dong Hun Shin (Aquaculture, 2024)

Remote impacts of low-latitude oceanic climate on coastal upwelling in a marginal sea of the Northwestern Pacific - Seongho Lee; Jeong-Yeob Chae; Jae-Hun Park; Young Taeg Kim; Boonsoon Kang; Chang-Woong Shin; Ho Kyung Ha (Regional Studies in Marine Science, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

Reliable AI models can reveal key processes of heat recovery steam generator operation in air pollutant emission - Seunghui Choi; Kwang-Hun Lee; Jae-Hong Park; Seungjae Jeon; Hyung Joo Lee; Phil-Goo Kang; Jonghun Kam (Journal of Cleaner Production, 2024)

Learning to predict sustainable aviation fuel properties: A deep uncertainty quantification viewpoint - Ji-Hun Oh; Anna Oldani; Alex Solecki; Tonghun Lee (Fuel, 2024)

Rapid and facile preparation of freestanding dense polymer membranes from high-boiling-point solvents for anion exchange membrane water electrolyzers - Du Ru Kang; Gi Hyo Sim; So Youn Lee; Jae Hun Lee; Ki Chul Kim; Jong Hak Kim (Chemical Engineering Journal, 2024)

A stress-adaptive interlinked 3D network binder for silicon anodes via tailored chemical bonds and conformation of functionalized poly(vinylidene fluoride) (PVDF) terpolymers - Young Je Kwon; Ji-Oh Kim; E. Vivek; Eunji Kim; Se Hun Kim; Taekyun Kwon; Eunyoung Lim; Seongwook Chae; Minjoon Park; Youngho Eom; Ji-Hoon Baik; Jin Hong Lee; et al. (Chemical Engineering Journal, 2024)

Improvement and Analysis for Accuracy of Baseflow Using SWAT-CUP Premium in the Yongjeon Stream, South Korea - Jong-Tae Kim; Chang-Hun Lee; Namjoo Lee (Pure and Applied Geophysics, 2024)
Here, the results of Soil and Water Assessment Tool (SWAT) simulation are calibrated and validated using SWAT-CUP Premium, and the R 2 (coefficient of determination) values of simulated and observed flows are compared. According to the SWAT analysis of the Cheongsong Yongjeon stream basin, low accuracy of 0.40 was the R 2 value for simulated and observed flows, and the baseflow was calculated at an annual average of 46.659 m 3 /s. During the same period, after calibration and validation using SWAT-CUP Premium, the R 2 value of simulated and observed flows was improved to 0.71, and the evaluation indexes showed 0.51 for Nash–Sutcliffe efficiency (NS), 37.1 for percent bias (PBIAS), 0.73 for P-factor, and 0.33 for R-factor, indicating that the relationship between observed and simulated flows was improved. In addition, after calibration and validation, the baseflow was 56.951 m 3 /s, which was a more accurate value than the one before calibration and validation.

Water-rock interactions of uranium deposits: A field investigation and laboratory batch experiment - Hakyung Cho; Jaeyeon Kim; Seong-Sun Lee; Kang-Kun Lee; Jaeguk Jo; Dongbok Shin; Ji-Hun Ryu; Sung-Wook Jeen (Applied Geochemistry, 2024)

The role of pattern recognition receptors in crustacean innate immunity - Bharat Bhusan Patnaik; Snigdha Baliarsingh; Arup Sarkar; A. S. Sahul Hameed; Yong Seok Lee; Yong Hun Jo; Yeon Soo Han; Jyotirmaya Mohanty (Reviews in Aquaculture, 2024)
Crustacean species are among the most valued seafood with socioeconomic and ecological implications in the global fisheries sector. Microbial infections to the farming stock due to continued expansion and aquaculture puts global crustacean production at risk. Understanding and reviewing the complex innate immune system of crustaceans would be pivotal in formulating informed decisions for the control and management of epidemic diseases, thus making the global crustacean aquaculture industry sustainable. Under the purview of innate immunity in crustaceans, pattern recognition receptors (PRRs) represent the sensors capable of discriminating non‐self pathogenic modules and invoking the activation of immune responses. The immunity to infections can be manifested at cellular (via phagocytosis, apoptosis, nodulation and encapsulation) and humoral (effected by prophenoloxidase cascade, lectins, antimicrobial proteins) levels leading to the elimination of pathogens or subversion of the pathogenic implications. In this review, we discuss the participatory role of 12 types of PRRs identified from crustacean species with an exhaustive focus on structural and functional specificities in binding to pathogens and possible execution of the immune activity. Moreover, we have elaborated on the PRRs‐associated or possible signalling cascades (Toll‐NFκB, IMD‐NFκB and JAK‐STAT) in crustacean species that could bridge our understanding of the resistance or susceptibility of the host to varied pathogenic infections thus providing clues to the regulatory mechanisms involved in pathogenesis of infectious diseases and mechanisms of immunity.

Micro-grinding–based production for sulforaphene-enriched radish seeds extract via facilitating glucosinolates-myrosinase reaction, and evaluation of its anti-adipogenic effects - Tae Kyung Lee; Gihyun Hur; Jong Hun Kim; Jung Han Yoon Park; Hee Yang; Ki Won Lee (Food Chemistry, 2023)

TRAF family member-associated NF-κB activator (TANK) regulates the antiviral function and NF-κB activation in red-spotted grouper (Epinephelus akaara) - Ji Hun Lee; H.M.V. Udayantha; Qiang Wan; Jehee Lee (Fish & Shellfish Immunology, 2023)

Metal-organic framework-based composites for biogas and natural gas uptake: An overview of adsorption and storage mechanisms of gaseous fuels - Mohammed Yusuf; Ramesh Kumar; Moonis Ali Khan; M.J. Ahmed; Marta Otero; Subbaiah Muthu Prabhu; Moon Son; Jae-Hoon Hwang; Woo Hyoung Lee; Byong-Hun Jeon (Chemical Engineering Journal, 2023)

Production and characterization of a biodegradable polymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), using the type II methanotroph, Methylocystis sp. MJC1 - Ok Kyung Lee; Seung Gi Kang; Tae-Rim Choi; Yung-Hun Yang; Eun Yeol Lee (Bioresource Technology, 2023)

Screening for Lactic Acid Bacterial Strains as Probiotics Exhibiting Anti-inflammatory and Antioxidative Characteristic Via Immune Modulation in HaCaT Cell - Min Jae Shin; Chul Sang Lee; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2023)

Comparison of photosynthetic efficiency and growth characteristics of paprika in semi-closed vs. conventional greenhouses - Eun ji Kim; Beom Seon Lee; Yong Hwan Jeon; Se Hun Ju; Yoon Go; Jin Sub Park; Joonwoo Lee; Huijun Yang; Haeyoung Na (Horticulture, Environment, and Biotechnology, 2023)

Correction: Recent advancement in enhanced soil flushing for remediation of petroleum hydrocarbon‑contaminated soil: a state‑of‑the‑art review - Ju-Hyeok Kwon; Min-Kyu Ji; Ramesh Kumar; Md. Monjurul Islam; Moonis Ali Khan; Young-Kwon Park; Krishna Kumar Yadav; Roozbeh Vaziri; Jae-Hoon Hwang; Woo Hyoung Lee; Yong-Tae Ahn; Byong-Hun Jeon (Reviews in Environmental Science and Bio/Technology, 2023)

Personal exposure of PM2.5 and metabolic syndrome markers of pregnant women in South Korea: APPO study - Yeonseong Jeong; Sunwha Park; Eunjin Kwon; Young Min Hur; Young-Ah You; Soo Min Kim; Gain Lee; Kyung A. Lee; Soo Jung Kim; Geum Joon Cho; Min-Jeong Oh; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2023)
We examined the association between exposure to PM 2.5 , focused on individual exposure level, and metabolic dysfunction during pregnancy. APPO study (Air Pollution on Pregnancy Outcome) was a prospective, multicenter, observational cohort study conducted from January 2021 to March 2023. Individual PM 2.5 concentrations were calculated using a time-weighted average model. Metabolic dysfunction during pregnancy was assessed based on a modified definition of metabolic syndrome and its components, accounting for pregnancy-specific criteria. Exposure to PM 2.5 during pregnancy was associated with worsened metabolic parameters especially glucose metabolism. In comparison to participants exposed to the low PM 2.5 group, those exposed to high PM 2.5 levels exhibited increased odds of gestational diabetes mellitus (GDM) after adjusting for confounding variables in different adjusted models. Specifically, in model 1, the adjusted odds ratio (aOR) was 3.117 with a 95% confidence interval (CI) of 1.234–7.870; in model 2, the aOR was 3.855 with a 95% CI of 1.255–11.844; in model 3, the aOR was 3.404 with a 95% CI of 1.206–9.607; and in model 4, the aOR was 2.741 with a 95% CI of 0.712–10.547. Exposure to higher levels of PM 2.5 during pregnancy was associated with a tendency to worsen metabolic dysfunction markers specifically in glucose homeostasis. Further research is needed to investigate the mechanisms underlying the effects of ambient PM 2.5 on metabolic dysfunction during pregnancy.

Assessment of effectiveness in stabilization/solidification of arsenic-contaminated soil: long-term leaching test and geophysical measurement - Sun-Jae Lee; Man ho Han; Yong-Tae Ahn; Byong-Hun Jeon; Jaeyoung Choi (Environmental Science and Pollution Research, 2023)

Biofloc Application Using Aquaponics and Vertical Aquaculture Technology in Aquaculture: Review - Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; A-Hyun Jo; Sung Won Han; Song-Hun Han; Hee Jae Choi; Cheol Young Choi; Ju-Chan Kang; EunYoung Min; Jun-Hwan Kim (Fishes, 2023)
Some aspects of traditional aquaculture have negative impacts on the aquatic environment, leading to pollution and disease outbreaks in farmed organisms. Biofloc technology (BFT) is a closed aquaculture system that utilizes specific microbial communities to remove ammonia emitted from aquaculture organisms or adds carbon to the aquaculture system to improve water quality. BFT has benefits, such as increasing production and improving water quality, and reducing disease spread and pollution, without the need for water exchange. However, there are disadvantages, such as rapid changes in water quality due to accumulation of dissolved nutrients and total suspended soils (TSS) and the requirement for expensive aeration equipment to maintain dissolved oxygen. BFT can be enhanced in value and efficiency by combining it with other aquaculture technologies, such as aquaponics and vertical aquaculture to overcome the disadvantages. The integration of biofloc with technologies from the fourth industrial revolution holds potential for further development, while aquaponics and vertical farming can eliminate geographical limitations and accelerate the urbanization of aquaculture. The integration of aquaponics and vertical aquaculture with BFT has potential for development, accelerating the urbanization of aquaculture and removing geographic limitations.

Inter-individual exposure variability interpretation through reflection of biological age algorithm in physiologically based toxicokinetic model: Application to human risk assessment of di-isobutyl-phthalate - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (Environmental Pollution, 2023)

Extremely high selective Si1−xGex-film wet etchant generating highly dissolved oxygen via peracetic acid oxidant for lateral gate-all-around FETs with a logic node of less than 3-nm - Seung-Jae Lee; Ji-Eun Lee; Chang-Jin Lee; Ji-Hoon Kim; Ji-Hun Kim; Min-Won Kim; Ji-Ho Choi; Ui-Hyun Jeong; Jea-Gun Park (Chemical Engineering Journal, 2023)

Comparative performance and machine learning-based optimization of TSA configurations for NH3 removal from NH3 cracking gas - Dat-Nguyen Vo; Jae Hun Chang; Suk-Hoon Hong; Chang-Ha Lee (Chemical Engineering Journal, 2023)

A population pharmacokinetic model for individualized regimens of finasteride according to CYP3A5 genotype and liver function - Ji-Hun Jang; Seung-Hyun Jeong; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2023)

Review of technology and materials for the development of cultured meat - Da Young Lee; Seung Yun Lee; Jae Won Jung; Jae Hyun Kim; Dong Hun Oh; Hyun Woo Kim; Ji Hyeop Kang; Jung Seok Choi; Gap-Don Kim; Seon-Tea Joo; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2023)

Real-time morphological detection of label-free submicron-sized plastics using flow-channeled differential interference contrast microscopy - Jiyun Han; Subeen Park; Mingizem Gashaw Seid; Byeongho Park; Soo Hyun Lee; Hyung Min Kim; Changha Lee; Jaesang Lee; Jae Hun Kim; Seok Won Hong (Journal of Hazardous Materials, 2023)

Identifying the origin and fate of dissolved U in the Boeun aquifer based on microbial signatures and C, O, Fe, S, and U isotopes - YeoJin Ju; Min Hoon Baik; Seung Yeop Lee; Kang-Kun Lee; Dugin Kaown; Dongbok Shin; Ji-Hun Ryu (Journal of Hazardous Materials, 2023)

Vibration detection of stay-cable from low-quality CCTV images using deep-learning-based dehazing and semantic segmentation algorithms - Hun Lee; Hyungchul Yoon; Sunjoong Kim (Engineering Structures, 2023)

Machine learning based simultaneous control of air handling unit discharge air and condenser water temperatures set-point for minimized cooling energy in an office building - Hyeon Jin Jee; Sang Hun Yeon; Jiwon Park; Yeobeom Yoon; Kwang Ho Lee (Energy and Buildings, 2023)

Antioxidant-Coated multifunctional whitlockite scaffold for the treatment of Steroid-Induced osteonecrosis of the femoral head - Jung Hun Kim; QuanZhe Liu; Uk-Jae Lee; Arun Kumar Rajendran; MinJoon Cho; Sivashanmugam Amirthalingam; Tae Hoon Kang; Beom Seok Kim; Gyeong-Guk Park; Byung-Gee Kim; Jae Hyup Lee; Nathaniel S. Hwang (Chemical Engineering Journal, 2023)

Structural Analysis Procedure and Applicability Review of Spudcan Considering Soil Types - Joo-Shin Park; Dong-Hun Lee; Myung-Su Yi (Journal of Marine Science and Engineering, 2023)
As interest in eco-friendly energy development continues to rise, the offshore wind turbine market is growing at a high rate of increase every year. In line with this, the demand for installation vessels with large capacity is also increasing rapidly. WTIVs (Wind Turbine Installation Vessels) employ spudcans in the seabed for the installation of wind turbines. Currently, the assessment of spudcans is an important issue in ensuring structural safety in the entire structure system. This study examines the current procedure suggested by classification societies and a new procedure that accounts for the new loading scenarios based on realistic operating conditions. This new procedure is further validated through an FEA (Finite Element Analysis). The current procedure yields maximum stress values below the allowable criteria because it does not consider the effect of the seabed slope, the leg bending moment, and the spudcan shape. However, the results of some load conditions as defined in the new procedure confirm the need for reinforcement under actual preload conditions. Therefore, the new procedure considers a broader range of real-world operating conditions, and the possible problems were verified through a detailed FEA.

Coastal warming heightens direct impacts of seawater temperature on nutrients near aquaculture farms in Korea - Yoonja Kang; Dong-Hun Lee (Science of The Total Environment, 2023)

Internal carbon loop strategy for methanol production from natural gas: Multi-objective optimization and process evaluation - Sung-Jong Jo; Tae-Ha Kang; Beom-Ju Shin; Ji-Hun Mun; Sijan Devkota; Jin-Young Cha; Shaukat Ali Mazari; Kyung-Min Kim; Ung Lee; Chae-Ho Shin; Jong-Ho Moon (Journal of Cleaner Production, 2023)

Integrative taxonomy of coastal Adota Casey (Coleoptera: Staphylinidae: Aleocharinae) with descriptions of two new species in Korea - Jong-Keun Jung; Seung-Gyu Lee; Jeong-Hun Song; Kee-Jeong Ahn (Journal of Asia-Pacific Entomology, 2023)

Intensified intrusion and retention of saltwater in the Sumjin River Estuary, South Korea - Hoi Soo Jung; Dhongil Lim; Ji Hun Kim; Jun-Ho Lee; Joo Bong Jeong; Han Jun Woo (Estuarine, Coastal and Shelf Science, 2023)

Fabrication of a Liquid Scintillator based on 7-Diethylamino-4-Methylcoumarin for Radiation Detection - Su Jung Min; Yong Dae Park; Seon Kwang Yoon; Chae Hun Lee; Bum Kyoung Seo; Jae Hak Cheong; Changhyun Roh; Sang Bum Hong (Journal of Fluorescence, 2023)

Recent advancement in enhanced soil flushing for remediation of petroleum hydrocarbon-contaminated soil: a state-of-the-art review - Ju-Hyeok Kwon; Min-Kyu Ji; Ramesh Kumar; Md. Monjurul Islam; Moonis Ali Khan; Young-Kwon Park; Krishna Kumar Yadav; Roozbeh Vaziri; Jae-Hoon Hwang; Woo Hyoung Lee; Yong-Tae Ahn; Byong-Hun Jeon (Reviews in Environmental Science and Bio/Technology, 2023)

Frequency Shift Keying-Based Long-Range Underwater Communication for Consecutive Channel Estimation and Compensation Using Chirp Waveform Symbol Signals - Jongmin Ahn; Dong-Hun Lee; Sangkug Lee; Wanjin Kim (Journal of Marine Science and Engineering, 2023)
Currently, the demand for long-range underwater communication (UWC) is increasing. Conventional long-range UWC studies utilize vertical line array (VLA) and equalization techniques such as TRM and DFE to mitigate the long multi-path delay. However, recently developed underwater platforms such as unmanned underwater vehicles (UUVs) utilize a single hydrophone, and it is hard to apply the conventional long-range UWC system to these platforms. This paper proposes frequency shifting-based modulation to overcome the large multi-path delay without any optimization or training symbol. Unlike FSK, the proposed modulation method transmits the data using linear frequency modulation (LFM). The proposed demodulation method estimates the multi-path delay using data-modulated LFM and utilizes the estimated multi-path to compensate for the subsequent data signal. Therefore, the proposed method has better BER performance than FSK, and it is demonstrated through a simulation and ocean experiment with a single hydrophone.

Enhanced oxidation of urea by pH swing during chlorination: pH-dependent reaction mechanism - Ji Won Lee; Donghyun Lee; Hye-Jin Lee; Soojin Shim; Je Hun Kim; Changha Lee (Water Research, 2023)

A versatile hybrid catalyst platform of Na/ZnFe2O4 and zeolite for selective hydrocarbon production from CO2 hydrogenation - Eun Cheol Ra; Sejin Jang; Dong Gun Oh; Ju Hyeong Lee; Hyo Eun Kim; Eun Hyup Kim; Kwang Young Kim; Min Hee Lee; Kwang Hyun Kim; Ja Hun Kwak; Jae Sung Lee (Chemical Engineering Journal, 2023)

Investigating the effect of blending of diamine and alkanolamine for CO2 capture: Experiment and thermodynamic modeling of CO2-AEEA-DEA-H2O system - Shaukat Ali Mazari; Tae-Ha Kang; Sijan Devkota; Jin-Young Cha; Beom-Ju Shin; Ji-Hun Mun; Kyung-Min Kim; Ung Lee; Jong-Ho Moon (Chemical Engineering Journal, 2023)

Investigating the impact of relative humidity and air tightness on PM sedimentation and concentration reduction - Minju Kim; Su-Gwang Jeong; Jongil Park; Sumin Kim; Jeong-Hun Lee (Building and Environment, 2023)

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

A stable isotopic approach for quantifying aquaculture-derived organic matter deposition dynamics in the sediment of a coastal fish farm - Young-Shin Go; Chung-Sook Kim; Won Chan Lee; Dong-Hun Lee (Marine Pollution Bulletin, 2023)

Multi-organ metastases of primary chondrosarcoma of the mammary gland of a spayed Toy Poodle - Seung-Won Yi; A-Ra Cho; Yoon Jung Do; Young-Hun Jung; Han Gyu Lee; Eun-Yeong Bok; Tai-Young Hur; Sung-Lim Lee; Eunju Kim (Journal of Comparative Pathology, 2023)

Wintertime sea surface temperature variability modulated by Arctic Oscillation in the northwestern part of the East/Japan Sea and its relationship with marine heatwaves - Se-Yong Song; Yoo-Jun Kim; Eun-Joo Lee; Sang-Wook Yeh; Jae-Hun Park; Young-Gyu Park (Frontiers in Marine Science, 2023)
The northwestern part of the East/Japan Sea (EJS) is a region with large sea surface temperature (SST) variability and is known as a hotspot of marine heatwaves (MHW) stress for marine environments that peaked in boreal winter (January-February-March). This could have profound impacts on the marine ecosystems over the EJS. Here, we used a set of high-resolution satellite and reanalysis products to systematically analyze the spatiotemporal SST variations and examine their linkage to a large-scale mode of climate variability, such as the Arctic Oscillation (AO). The results show that AO-related wind forcing modulates the SST variability over the EJS via the oceanic dynamic adjustment processes. In particular, the abnormally warm SSTs in the northwestern part of the EJS are driven by the anomalous anticyclonic eddy-like circulation and Ekman downwelling during a positive AO phase. This physical linkage between a positive AO and the abnormally warm SST could be conducive to MHW occurrences in the EJS as in the extremely positive AO event during the winter of 2020. These results have implications that the MHW occurrences in the EJS could be amplified by natural climate variability along with long-term SST warming.

Seasonal Variability of the Deep Western Boundary Current in the Philippine Sea - Hajin Song; Xiao-Hua Zhu; Ze-Nan Zhu; Jeong-Yeob Chae; Chanhyung Jeon; Dong-Guk Kim; Hong-Sik Min; Jae-Hak Lee; Jae-Hun Park (Journal of Marine Science and Engineering, 2023)
The deep western boundary current (DWBC) in the Philippine Sea has been expected to play a crucial role in transporting lower circumpolar deep water and to contribute to regional and global climate regulation. Two-year-long near-bottom current measurements reveal a southward-flowing DWBC with a mean velocity of 5 cm/s and seasonal variations—weaker in summer and stronger in winter. Seasonal variability in the DWBC is hypothesized to be induced by changes in the North Equatorial Current bifurcation latitude (NECBL) and upper pycnocline depth through potential vorticity conservation. Data-assimilated reanalysis model (GLORYS12V1) outputs, which reproduce the seasonal variability of DWBC similarly to the observation, are used for further analysis. During the seasonal period, the NECBL displays significant coherence (>0.9) with the first-mode empirical orthogonal function principal component of the simulated along-slope DWBC. The upper pycnocline depth, varying seasonally within a range of approximately 27 m, induces seasonal variability in a deep anticyclonic eddy trapped by topography. In summer, the intensified deep anticyclonic eddy obstructs the adjacent southward-flowing DWBC, weakening its strength, whereas in winter, the southward flow of the DWBC is enhanced due to the weakening of the deep anticyclonic eddy.

Application of the CPFD method to analyze the effects of bed material density on gas-particle hydrodynamics and wall erosion in a CFB boiler - Byoung-Hwa Lee; Yoon-Ho Bae; Kang-Min Kim; Yu Jiang; Young-Hun Ahn; Chung-Hwan Jeon (Fuel, 2023)

Purification of phenoloxidase from Haliotis discus hannai and its anti-inflammatory activity in vitro - Seung-Yub Song; Dae-Hun Park; Sung-Ho Lee; Han-Kyu Lim; Jin-Woo Park; Chae-Rim Jeong; Soo-Jung Kim; Seung-Sik Cho (Fish & Shellfish Immunology, 2023)

Multiscale strategy to predict the fracture toughness and crack extension behavior of ozone-functionalized carbon nanotube/epoxy nanocomposites - Haolin Wang; Jihun Lee; Jae Hun Kim; Hyunseong Shin (Chemical Engineering Journal, 2023)

True self-reinforced composites enabled by tuning of molecular structure for lightweight structural materials in future mobility - Hyeseong Lee; Ji-un Jang; Jaewoo Kim; Yoon Sang Kim; Jaehyun Cho; Mi Na Kim; Jung Tae Lee; Woo Hyuk Choi; Jong Man Song; Won June Song; Dong Hui Won; Deok Woo Yun; et al. (Chemical Engineering Journal, 2023)

Systematic tracing of nitrate sources in a complex river catchment: An integrated approach using stable isotopes and hydrological models - Seung-Hee Kim; Dong-Hun Lee; Min-Seob Kim; Han-Pil Rhee; Jin Hur; Kyung-Hoon Shin (Water Research, 2023)

Establishment of a fexofenadine population pharmacokinetic (PK)–pharmacodynamic (PD) model and exploration of dosing regimens through simulation - Ji-Hun Jang; Seung-Hyun Jeong; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2023)

Numerical and Experimental Study on NOx Reduction According to the Load in the SCR System of a Marine Boiler - Jeong-Uk Lee; Sung-Chul Hwang; Seung-Hun Han (Journal of Marine Science and Engineering, 2023)
Numerical analysis and experimental studies were conducted to evaluate the performance of a selective catalytic reduction (SCR) system according to the load of a 1.5-ton marine boiler. There are post-treatment methods for reducing the exhaust gas emitted from ships, such as low-sulfur oil, scrubber, a desulfurization device to remove sulfur oxides (SOx) and particulate matter, an exhaust gas recirculation system, and SCR agents to reduce nitrogen oxides (NOx). Furthermore, there are methods of using eco-friendly natural gas fuels, such as liquefied natural gas (LNG), methanol, liquefied petroleum gas, and ammonia. In the case of LNG, SOx and particulate matter are hardly emitted, and only a small amount of NOx is emitted compared to an internal combustion engine. Therefore, SCR system technology that can remove NOx needs to be applied. As a result of this study, the boiler load increased, and the flow velocity through the outlet decreased. In addition, the NOx emissions of diesel fuel and LNG fuel were reduced by 100% to 0 ppm when the boiler load ratio was 50%. When the load ratio was 75%, the NOx emissions of diesel fuel were reduced by 77.4% to 40 ppm, and those of LNG fuel were reduced by 64.1% to 24 ppm. When the load ratio was 100%, the NOx emissions of diesel fuel were reduced by 66.1% to 60 ppm, and those of LNG fuel were reduced by 47.8% to 24 ppm. In addition, the results of the numerical analysis according to boiler load were almost identical to the experimental results. Finally, this study could design an optimal SCR system through numerical analysis, according to the important parameters of the SCR system.

Ni-B-P micro spheres for superior water splitting OER electrocatalyst satisfying industrial operational requirement - Md Ahasan Habib; Rutuja Mandavkar; Shusen Lin; Shalmali Burse; Tasmia Khalid; Mehedi Hasan Joni; Jae-Hun Jeong; Jihoon Lee (Chemical Engineering Journal, 2023)

ATF4-activated parkin induction contributes to deferasirox-mediated cytoprotection in Parkinson’s disease - Sangwoo Ham; Ji Hun Kim; Heejeong Kim; Jeong-Yong Shin; Yunjong Lee (Toxicological Research, 2023)

First report of pitaya virus X infecting dragon fruit (Selenicereus undatus) in Korea - Nam-Yeon Kim; Yong Hun Jo; Young Min Bae; Kyung-Pyo Lee; Rae-Dong Jeong; Yeon Soo Han; KiBeom Park (Journal of Plant Pathology, 2023)

MOF-derived carbon/ZnS nanoparticle composite interwoven with structural and conductive CNT scaffolds for ultradurable K-ion storage - Song-Gue Choi; Young Hwan Kim; Geon-Woo Lee; Hun Seok Choi; Kwang-Bum Kim (Chemical Engineering Journal, 2023)

Recycling of minerals with acetate separation in biological syngas fermentation with an electrodialysis system - Jae-Hun Kim; Mungyu Lee; Hoyoung Jeong; Songju Ko; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2023)

Evaluation of biogenic emissions from three different vegetation distributions in South Korea - Jinhyeok Yu; Kyung M. Han; Chul H. Song; Kyunghwa Lee; Sojin Lee; Younha Kim; Jung-Hun Woo; Saewung Kim; Armin Wisthaler (Atmospheric Environment, 2023)

The trend of ammonia levels in patients with glufosinate ammonium poisoning with respect to neurotoxicity - Joochan Kim; Yong Soo Cho; Byeong Jo Chun; Jeong Mi Moon; Dong Ki Kim; Byung Kook Lee; Dong Hun Lee; Seok Jin Ryu; Eujene Jung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Semi-mechanistic analysis of emergency planning zones for 20 MWe lead-cooled fast reactor by hypothetical accidents during Korea's arctic exploration - Chanki Lee; Seung Hun Shin; Hee Reyoung Kim; Il Soon Hwang (Journal of Environmental Radioactivity, 2023)

Molecular characterization, immune expression, and functional delineation of peroxiredoxin 1 in Epinephelus akaara - Subothini Ganeshalingam; Kishanthini Nadarajapillai; Sarithaa Sellaththurai; Gaeun Kim; Jeongeun Kim; Ji Hun Lee; Taehyug Jeong; Qiang Wan; Jehee Lee (Fish & Shellfish Immunology, 2023)

Conversion of toxic chemicals into flammable gases through the thermolysis of polyurethane foam using CO2 - Taewoo Lee; Jung-Hun Kim; Yiu Fai Tsang; Wei-Hsin Chen; Doyeon Lee; Min-Woong Jung; Sungyup Jung; Eilhann E. Kwon (Chemical Engineering Journal, 2023)

Li reaction pathways in Ge and high-performance Ge nanocomposite anodes for Li-ion batteries - Dong-Hun Lee; Do-Hyeon Kim; Heechul Jung; Cheol-Min Park (Chemical Engineering Journal, 2023)

Hydrophobic sulfur core–shell layered metallic iron for nitrate reduction with nearly 100% dinitrogen selectivity: Mechanism and field studies - Choe Earn Choong; So Yeon Yoon; Kien Tiek Wong; Minhee Kim; Gooyong Lee; Sang-Hyoun Kim; Byong-Hun Jeon; Jaeyoung Choi; Yeomin Yoon; Eun Ha Choi; Min Jang (Chemical Engineering Journal, 2023)

Anti-Osteoarthritic Effects of Cartilage-Derived Extracellular Matrix in a Rat Osteoarthritis Model - Sang-Hun Lee; Sung-Han Jo; Seon-Hwa Kim; Chang-Su Kim; Sang-Hyug Park (Tissue Engineering and Regenerative Medicine, 2023)

Transmission of antibiotic resistance genes through mobile genetic elements in Acinetobacter baumannii and gene-transfer prevention - Jeong Ho Jeon; Kyung-Min Jang; Jung Hun Lee; Lin-Woo Kang; Sang Hee Lee (Science of The Total Environment, 2023)

Evaluation of pyrite/sodium hypochlorite for activating purification of arsenic from fractured-bedrock groundwater - Da-won Lee; Yongtae Ahn; Dong-Wan Cho; Bikram Basak; Byong-Hun Jeon; Jaeyoung Choi (Environmental Pollution, 2023)

Protective effect of 7-hydroxyl-1-methylindole-3-acetonitrile on the intestinal mucosal damage response to inflammation in mice with DSS-induced colitis - Kyung-Sook Chung; Sang-Eun Park; Jung-Hun Lee; Su-Yeon Kim; Hee-Soo Han; Yong Sup Lee; Seang-Hwan Jung; Eungyeong Jang; Sangmin Lee; Kyung-Tae Lee (Chemico-Biological Interactions, 2023)

Modular design for constructing narrowband deep-blue multiresonant thermally activated delayed fluorescent emitters for efficient organic light emitting diodes - Kenkera Rayappa Naveen; Hyuna Lee; Lee Hyun Seung; Young Hun Jung; C.P. Keshavananda Prabhu; Subramanian Muruganantham; Jang Hyuk Kwon (Chemical Engineering Journal, 2023)

Drug delivery to the brain via the nasal route of administration: exploration of key targets and major consideration factors - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2023)

Bone Regeneration with 3D-Printed Hybrid Bone Scaffolds in a Canine Radial Bone Defect Model - Yoon Jae Lee; Yeon Hee Ryu; Su Jin Lee; Suk-Ho Moon; Ki Joo Kim; Byeong Ju Jin; Kyoung-Don Lee; Jung Kyu Park; Jin Woo Lee; Seung-Jae Lee; Hun-Jin Jeong; Jong Won Rhie (Tissue Engineering and Regenerative Medicine, 2022)

Correction to: Interpreting complex geochemistry of groundwater in a coastal paddy field near a mine using isotopic signatures of sulfate and water - Duk-Min Kim; Oh-Hun Kwon; Youn Soo Oh; Jin-Soo Lee (Environmental Geochemistry and Health, 2022)

New parameterization of air-sea exchange coefficients and its impact on intensity prediction under major tropical cyclones - Woojeong Lee; Sung-Hun Kim; Il-Ju Moon; Michael M. Bell; Isaac Ginis (Frontiers in Marine Science, 2022)
Understanding and quantifying air-sea exchanges of enthalpy and momentum fluxes are crucial for the advanced prediction of tropical cyclone (TC) intensity. Here, we present a new parameterization of air-sea fluxes at extreme wind speeds from 40 m s −1 to 75 m s −1 , which covers the range of major TCs. Our approach assumes that the TC can reach its maximum potential intensity (MPI) if there are no influences of external forces such as vertical wind shear or other environmental constraints.This method can estimate the ratio of the enthalpy and momentum exchange coefficient ( C k / C d ) under the most intense TCs without direct flux measurements. The estimation showed that C k / C d increases with wind speed at extreme winds above 40 m s −1 . Two types of surface layer schemes of the Hurricane Weather and Research Forecast (HWRF) were designed based on the wind speed dependency of the C k / C d found at high winds: (i) an increase of C k / C d based on decreasing C d (Cd_DC) and (ii) an increase of C k / C d based on increasing C k (Ck_IC). The modified surface layer schemes were compared to the original HWRF scheme (using nearly fixed C d and C k at extreme winds; CTRL) through idealized experiments and real-case predictions. The idealized experiments showed that Cd_DC reduced frictional dissipation in the air-sea interface as well as significantly reduced sea surface cooling, making the TC stronger than other schemes. As a result, Cd_DC reduced the mean absolute error and negative bias by 15.0% (21.0%) and 19.1% (32.0%), respectively, for all lead times of Hurricane Irma in 2017 (Typhoon Mangkhut in 2018) compared to CTRL. This result suggests that new parameterization of C k / C d with decreasing C d at high winds can help improve TC intensity prediction, which currently suffers from underestimating the intensity of the strongest TCs.

Effects of isoflurane anesthesia on addictive behaviors in rats - Seong Shoon Yoon; Bong Hyo Lee; Seong Ho Lee; Seong Hun Choi; Seon-Ju Jeong; Sang Chan Kim; Chae Ha Yang (Psychopharmacology, 2022)

Reconstruction of long-term sea-level data gaps of tide gauge records using a neural network operator - Eun-Joo Lee; Kiduk Kim; Jae-Hun Park (Frontiers in Marine Science, 2022)
The coastal sea level is an important factor in understanding and clarifying the physical processes in coastal seas. However, missing values and outliers of the sea level that occur for various reasons often disrupt the continuity of its time series. General-purpose time-series analysis and prediction methods are not tolerant of missing values, which is why researchers have attempted to fill these gaps. The disadvantage of conventional time-series reconstruction techniques is the low accuracy when missed sea-level records are longer than the timescales of coastal processes. To solve this problem, we used an artificial neural network, which is a novel tool for creating multivariate and nonlinear regression equations. The trained neural network weight set was designed to enable long-term reconstruction of sea level by acting as a one-step prediction operator. In addition, a data assimilation technique was developed and adapted to ensure seamless continuity between predicted and observed sea-level records. The application of our newly developed method to 3-day gaps of seal level records at 16 tide gauge stations around the Korean peninsula confirms that it can successfully reconstruct missing values with root-mean-squared errors of 0.5–1.1 cm on average.

Effect of water filtration infrared-A (wIRA) sauna on inorganic ions excreted through sweat from the human body - Kang-hee Cho; Sung-hun Jung; Min-sun Choi; Yong-jin Jung; Chang-Gu Lee; Nag-choul Choi (Environmental Science and Pollution Research, 2022)

Motion Control System Design for Barge-Type Surface Ships Using Tugboats - Dong-Hun Lee; Thinh Huynh; Young-Bok Kim; Jung-Suk Park (Journal of Marine Science and Engineering, 2022)
Barge ships are designed to transport and assemble heavy and massive pieces of equipment at sea. Active propulsion systems are not installed in this type of ship, so the desirable motion and positioning of these ships can only be achieved with the assistance of several tugboats. In this study, the dynamical characteristics of barge conveying systems were formulated and robust control systems were designed to ensure efficient barge operation. To achieve these objectives, we first developed a mathematical model of a barge ship, which incorporated a novel conveying system configuration using tugboats. We then designed a robust controller for the tugboats that used the sliding mode law to deliver the desired barge motion performance. Finally, the usefulness of the proposed configuration and controller was verified via simulation studies using another system with an H∞ controller. The proposed sliding mode controller showed superiority, especially in terms of robustness against disturbances.

Geochemical signatures of organic matter associated with gas generation in the Pohang Basin, South Korea - Dong-Hun Lee; Seung-Hee Kim; Jiyoung Choi; Nyeon-Keon Kang; In Gul Hwang; Kyung-Hoon Shin (Geosciences Journal, 2022)

Human risk assessment of 4-n-nonylphenol (4-n-NP) using physiologically based pharmacokinetic (PBPK) modeling: analysis of gender exposure differences and application to exposure analysis related to large exposure variability in population - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Archives of Toxicology, 2022)

Biotransformation of C20- and C22-polyunsaturated fatty acids to 11S- and 13S-hydroxy fatty acids by Escherichia coli expressing 11S-lipoxygenase from Enhygromyxa salina - Jin Lee; Tae-Hun Kim; Kyung-Chul Shin; Tae-Eui Lee; Min-Ju Kim; Deok-Kun Oh (Biotechnology Letters, 2022)

Comparative study of spatiotemporal variation in the urban heat island core in coastal and inland basin cities - Ji-Hun Moon; Soon-Young Park; Soon-Hwan Lee (Air Quality, Atmosphere & Health, 2022)

Impact of High Methane Flux on the Properties of Pore Fluid and Methane-Derived Authigenic Carbonate in the ARAON Mounds, Chukchi Sea - Ji-Hoon Kim; Myong-Ho Park; Dong-Hun Lee; Hirotsugu Minami; Young-Keun Jin; Akihiro Hachikubo; Jin Hur; Jong-Sik Ryu; Moo-Hee Kang; Kwangchul Jang; Masato Kida; Yongwon Seo; et al. (Frontiers in Marine Science, 2022)
We investigated the pore fluid and methane-derived authigenic carbonate (MDAC) chemistry from the ARAON Mounds in the Chukchi Sea to reveal how methane (CH 4 ) seepage impacts their compositional and isotopic properties. During the ARA07C and ARA09C Expeditions, many in situ gas hydrates (GHs) and MDACs were found near the seafloor. The fluid chemistry has been considerably modified in association with the high CH 4 flux and its related byproducts (GHs and MDACs). Compared to Site ARA09C-St 08 (reference site), which displays a linear SO 4 2- downcore profile, the other sites (e.g., ARA07C-St 13, ARA07C-St 14, ARA09C-St 04, ARA09C-St 07, and ARA09C-St 12) that are found byproducts exhibit concave-up and/or kink type SO 4 2- profiles. The physical properties and fluid pathways in sediment columns have been altered by these byproducts, which prevents the steady state condition of the dissolved species through them. Consequently, chemical zones are separated between bearing and non-bearing byproducts intervals under non-steady state condition from the seafloor to the sulfate-methane transition (SMT). GH dissociation also significantly impacts pore fluid properties (e.g., low Cl - , enriched δD and δ 18 O). The upward CH 4 with depleted δ 13 C from the thermogenic origin affects the chemical signatures of MDACs. The enriched δ 18 O fluid from GH dissociation also influences the properties of MDACs. Thus, in the ARAON Mounds, the chemistry of the fluid and MDAC has significantly changed, most likely responding to the CH 4 flux and GH dissociation through geological time. Overall, our findings will improve the understanding and prediction of the pore fluid and MDAC chemistry in the Arctic Ocean related to CH 4 seepage by global climate change.

Construction of Reliable Flow Simulation Domain and Estimation of Permeability Based on Nuclear Magnetic Resonance and 3D X-ray Computed Tomography for Reservoir Carbonate Rocks - Eomzi Yang; Dong Hun Kang; Taewoong Ahn; Joo Yong Lee; Tae Sup Yun (Transport in Porous Media, 2022)

Universal Stress Protein (USP) Enhances Plant Growth and Development by Promoting Cell Expansion - Eun Seon Lee; Kieu Anh Thi Phan; Sang Eun Jun; Joung Hun Park; Seol Ki Paeng; Ho Byoung Chae; Seong Dong Wi; Su Bin Bae; Kee Ryeon Kang; Gyung-Tae Kim; Sang Yeol Lee (Journal of Plant Biology, 2022)

Geochemical characteristics and origins of hydrocarbon gases in the shallow gas field in the Pohang Basin, Korea - Jiyoung Choi; Nyeon-Keon Kang; In Gul Hwang; Dong-Hun Lee (Geosciences Journal, 2022)

Sacubitril/valsartan reduces endoplasmic reticulum stress in a rat model of doxorubicin-induced cardiotoxicity - Byung Sik Kim; In-Hwa Park; A-Hyeon Lee; Hyun-Jin Kim; Young-Hyo Lim; Jeong-Hun Shin (Archives of Toxicology, 2022)

Molecular cloning, sequence characterization, and expression analysis of C-type lectin (CTL) and ER-Golgi intermediate compartment 53-kDa protein (ERGIC-53) homologs from the freshwater prawn, Macrobrachium rosenbergii - Snigdha Baliarsingh; Sonalina Sahoo; Yong Hun Jo; Yeon Soo Han; Arup Sarkar; Yong Seok Lee; Jyotirmaya Mohanty; Bharat Bhusan Patnaik (Aquaculture International, 2022)

Selection and Characterization of Probiotic Bacteria Exhibiting Antiadipogenic Potential in 3T3-L1 Preadipocytes - Chul Sang Lee; Mi Hyun Park; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2022)

Physicochemical and isotopic properties of ambient aerosols and precipitation particles during winter in Seoul, South Korea - Hanna Choi; Heejo Lee; Dong-Hun Kim; Kang-Kun Lee; Yongcheol Kim (Environmental Science and Pollution Research, 2022)

Seed-Specifically Overexpressed Arabidopsis Cytochrome P450 85A2 Promotes Vegetative and Reproductive Growth and Development of Arabidopsis thaliana - Myeong Hun Yeon; Chan-Ho Park; Ye Eun Lee; Jeehee Roh; Seong-Ki Kim (Journal of Plant Biology, 2022)

Evaluation of washing solutions to remove particulate matter attached to greenhouse covering material - Byung-hun Seo; Eunmi Hong; Won Choi; Jong-hyuk Lee; Young-joon Jeong; Ye-jin Seo; Jae-han Lee (Paddy and Water Environment, 2022)

Population pharmacokinetic analysis of lornoxicam in healthy Korean males considering creatinine clearance and CYP2C9 genetic polymorphism - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2022)

Dietary supplementations of Bacillus probiotic improve digestibility, growth performance, innate immunity, and water ammonia level for Pacific white shrimp, Litopenaeus vannamei - Chorong Lee; Soohwan Kim; Jaehyeong Shin; Min-Gi Kim; Buddhi E. Gunathilaka; Sung Hun Kim; Ji Eun Kim; Seung-Cheol Ji; Jee Eun Han; Kyeong-Jun Lee (Aquaculture International, 2021)

Long-lasting reversible monocular visual loss of retinal migraine - Sang-Hun Lee; Ji Hye Shin; Jung Won Hwang (Acta Neurologica Belgica, 2021)

High-resolution magnetic resonance imaging for the follow-up of intracranial arterial dissections - Sang-Hun Lee; Keon-Yeup Kim; Jin-Man Jung (Acta Neurologica Belgica, 2021)

Toxicokinetics of di-isodecyl phthalate and its major metabolites in rats through the application of a developed and validated UHPLC-ESI-MS/MS method - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Archives of Toxicology, 2021)

Interpreting complex geochemistry of groundwater in a coastal paddy field near a mine using isotopic signatures of sulfate and water - Duk-Min Kim; Oh-Hun Kwon; Youn Soo Oh; Jin-Soo Lee (Environmental Geochemistry and Health, 2021)

Determination of soil contamination sources in mining area using Zn/Cd ratios with mobile Cd - Duk-Min Kim; Oh-Hun Kwon; Youn Soo Oh; Jin-Soo Lee (Environmental Geochemistry and Health, 2021)

Downregulation of PyHRG1, encoding a novel secretory protein in the red alga Pyropia yezoensis, enhances heat tolerance - Narae Han; Jiwoong Wi; Sungoh Im; Ka-Min Lim; Hun-Dong Lee; Won-Joong Jeong; Geun-Joong Kim; Chan Song Kim; Eun-Jeong Park; Mi Sook Hwang; Dong-Woog Choi (Algae, 2021)
An increase in seawater temperature owing to global warming is expected to substantially limit the growth of marine algae, including Pyropia yezoensis, a commercially valuable red alga. To improve our knowledge of the genes involved in the acquisition of heat tolerance in P. yezoensis, transcriptomes sequences were obtained from both the wild-type SG104 P. yezoensis and heat-tolerant mutant Gy500. We selected 1,251 differentially expressed genes that were up- or downregulated in response to the heat stress condition and in the heat-tolerant mutant Gy500, based on fragment per million reads expression values. Among them, PyHRG1 was downregulated under heat stress in SG104 and expressed at a low level in Gy500. PyHRG1 encodes a secretory protein of 26.5 kDa. PyHRG1 shows no significant sequence homology with any known genes deposited in public databases to date. However, PyHRG1 homologs were found in other red algae, including other Pyropia species. When PyHRG1 was introduced into the single-cell green alga Chlamydomonas reinhardtii, transformed cells overexpressing PyHRG1 showed severely retarded growth. These results demonstrate that PyHRG1 encodes a novel red algae-specific protein and plays a role in heat tolerance in algae. The transcriptome sequences obtained in this study, which include PyHRG1, will facilitate future studies to understand the molecular mechanisms involved in heat tolerance in red algae.

Improved conditions of a whole testis organ culture system in terms of spermatogonial proliferation levels in marine medaka (Oryzias dancena) - Ji Hun Lee; Jae Hoon Choi; Jung Kyu Choi; Seung Pyo Gong (In Vitro Cellular & Developmental Biology - Animal, 2021)

Assessment of soil washing for heavy metal contaminated paddy soil using FeCl3 washing solutions - Deok Hyun Moon; Yoon-Young Chang; Minho Lee; Agamemnon Koutsospyros; Il-Ha Koh; Won Hyun Ji; Jeong-Hun Park (Environmental Geochemistry and Health, 2021)

Novel Method for the Estimation of Vertical Temperature Profiles Using a Coastal Acoustic Tomography System - Yeongbin Park; Chanhyung Jeon; Hajin Song; Youngseok Choi; Jeong-Yeob Chae; Eun-Joo Lee; Jin Sung Kim; Jae-Hun Park (Frontiers in Marine Science, 2021)
Systems based on remote sensing technology, which use reciprocal acoustic signals to continuously monitor changes in the coastal oceanic environment, are referred to as coastal acoustic tomography (CAT) systems. These systems have been applied in regions in which heavy ship traffics, fishing and marine aquaculture activities make it difficult to establish in situ oceanic sensor moorings. Conventionally, CAT measurements were used to successfully produce horizontal maps of the depth-averaged current velocity and temperature in these coastal regions without attempting to produce a vertical temperature profile. This prompted us to propose a new method for vertical temperature profile estimation (VTPE) from CAT data using the available sea surface temperature (SST), near-bottom temperature (NBT), and water depth. The VTPE method was validated using data-assimilated and tide-included high-resolution ocean model outputs, including tide data, by comparing the estimated and simulated temperatures. Measurements were performed in the southern coastal region of Korea, where two CAT stations were moored to establish a continuous coastal ocean monitoring system. The validation results revealed that the algorithm performed well across all seasons. Sensitivity tests of the VTPE method with reasonable realistic random errors in the SST, NBT, and acoustic travel time measurements demonstrate that the method is applicable to CAT observation data because the monthly mean root-mean-squared difference (RMSD) for the vertical profiles for February, May, August, and November were 0.23, 0.30, 0.50, and 0.24°C, respectively. The VTPE method was applied to the CAT observation datasets acquired in February and August. The transceivers at the CAT stations were at depths 11 and 6 m on average. The RMSD between the estimated and observed temperatures in the middle layer (∼3 m depth) between two stations in February and August were 0.08 and 0.60°C, respectively, the accuracy of which is sufficient in largely time-varying coastal environments. We provide a novel method for continuous coastal subsurface environmental monitoring without interrupting maritime traffic, fishing, and marine aquaculture activities.

Antiobesity Effect of Novel Probiotic Strains in a Mouse Model of High-Fat Diet–Induced Obesity - Chul Sang Lee; Mi Hyun Park; Byoung Kook Kim; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2021)

Challenges in Monitoring Atmospheric CO2 Concentrations in Seoul Using Low-Cost Sensors - Chaerin Park; Sujong Jeong; Hoonyoung Park; Jung-Hun Woo; Sojung Sim; Jongho Kim; Junghoon Son; Hayoung Park; Yongseung Shin; Jin-ho Shin; Seung-Mi Kwon; Won-young Lee (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Atmospheric Structure for Convective Development in the Events of Cloud Clusters over the Korean Peninsula - Tae-Young Lee; Uju Shin; Sang-Hun Park (Asia-Pacific Journal of Atmospheric Sciences, 2021)
This study examines atmospheric structures causing convective development in the events of cloud cluster (CC) over the Korean peninsula using the analysis and forecast data of National Centers for Environmental Prediction (NCEP) climate forecast system reanalysis (CFSR) and observation data. Two CC types—CCs associated with meso-α-scale lows (CCMLs) and mesoscale troughs (CCMTs)—were investigated. The common atmospheric structure for convective development in CC events is comprised of i) a strong southwesterly band (SWB; a region with southwesterly wind speeds >12.5 m s −1 ) in the lower troposphere upstream of CCs with a mesoscale convergence zone in its exit area, ii) a layer of high-θ e air in the lower troposphere near the surface extending from the southwest to SWB exit, iii) elevated height of maximum θ e in the lower troposphere near and over the convergence zone, above which a convectively unstable layer exists. Generality of the above-described structure has been demonstrated via examination of composite fields. SWB plays a major role in producing the structure for convective development in CC events over the Korean peninsula mainly through i) advection of high-θ e air from the southwest, and ii) significant horizontal convergence in the exit area, which can facilitate convection initiation. The two types of CC show notable differences in atmospheric structure across the boundary between high-θ e air from the southwest and low-θ e air in the northeast and in the mode of high-θ e air transport to the region of convective development. The boundary is generally tilted northeastward with height for CCML cases, whereas it is nearly vertical for the majority of CCMT cases. This study indicates that, despite the above-mentioned differences, convective developments in both CC types can be considered as elevated convection that occurs as air parcels in an elevated layer of convective instability are lifted by upward motion in the convergence zone. For both types of CC, differential θ e advection plays the key role for the occurrence of elevated layer of convective instability. And θ e front in CCML events indicates the presence of elevated convective instability above it and the possibility of elevated convection provided that a lifting mechanism is available.

Spatiotemporal analysis of temperature data trends in Peninsular Malaysia - Hun Vui Woo; Jing Lin Ng; Yuk Feng Huang; Celine Chong; Jin Chai Lee (Arabian Journal of Geosciences, 2021)

Advanced Remote Data Acquisition Using a Pop-Up Data Shuttle (PDS) to Report Data From Current- and Pressure-Recording Inverted Echo Sounders (CPIES) - Chanhyung Jeon; Jae-Hun Park; Maureen Kennelly; Erran Sousa; D. Randolph Watts; Eun-Joo Lee; Taewook Park; Thomas Peacock (Frontiers in Marine Science, 2021)
A current- and pressure-recording inverted echo sounder (CPIES) placed on the sea floor monitors aspects of the physical ocean environment for periods of months to years. Until recently, acoustic telemetry of daily-processed data was the existing method for data acquisition from CPIES without full instrument recovery. However, this approach, which requires positioning a ship at the mooring site and operator time, is expensive and time-consuming. Here, we introduce a new method of obtaining data remotely from CPIES using a popup-data-shuttle (PDS), which enables straightforward data acquisition without a ship. The PDS data subsampled from CPIES has 30–60 min temporal resolution. The PDS has a scheduled pop-up-type release system, so each data pod floats to the sea surface at a user-specified date and relays the recorded data via the Iridium satellite system. We demonstrated the capability of an array of PDS-CPIES via two successful field experiments in the Arctic Ocean. The data acquired through the PDS were in agreement with the fully recovered datasets. An example of the data retrieved from the PDS shows that time-varying signals of tides and high-frequency internal waves were well captured. GPS-tracked trajectories of the PDS floating free at the sea surface can provide insights into ice drift or ocean surface currents. This PDS technology provides an alternative method for remote deep-ocean mooring data acquisition.

Human risk assessment of di-isobutyl phthalate through the application of a developed physiologically based pharmacokinetic model of di-isobutyl phthalate and its major metabolite mono-isobutyl phthalate - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Archives of Toxicology, 2021)

Geochemical and Microbial Signatures of Siboglinid Tubeworm Habitats at an Active Mud Volcano in the Canadian Beaufort Sea - Dong-Hun Lee; Jung-Hyun Kim; Yung Mi Lee; Ji-Hoon Kim; Young Keun Jin; Charles Paull; Jong-Sik Ryu; Kyung-Hoon Shin (Frontiers in Marine Science, 2021)
During the ARA08C expedition in 2017, sediment push cores were collected at an active mud volcano (420 m water depth) in the Canadian Beaufort Sea from two visually discriminative siboglinid tubeworm (ST) habitats that were colonized densely and less densely (ST1 and ST2, respectively). In this study, we investigated the biogeochemical and microbial community characteristics at ST1 by analyzing the geochemical properties, microbial lipids, and nucleic acid signatures, and comparing them with the data previously reported from ST2. The two ST sites showed distinct differences in vertical geochemical gradients [methane, sulfate, dissolved inorganic carbon (DIC), total organic carbon, and total sulfur], with a higher methane flux recorded at ST1 (0.05 mmol cm –2 y –1 ) than at ST2 (0.01 mmol cm –2 y –1 ). Notably, the δ 13 C values of DIC were more depleted at ST1 than at ST2, resulting in a higher proportion of DIC derived from the anaerobic oxidation of methane (AOM) at ST1 than at ST2. Moreover, both the ST1 and ST2 sites revealed the dominance of AOM-related lipid biomarkers (especially sn -2-hydroxyarchaeol), showing highly 13 C-depleted values. The 16S rRNA analyses showed the presence of AOM-related archaea, predominantly anaerobic methanotrophic archaea (ANME)-3 at ST1 and ST2. Our results suggest that AOM-related byproducts (sulfide and DIC) potentially derived from ANME-3 were more abundant at ST1 than at ST2. This variation was attributed to the intensity and persistence of ascending methane. Therefore, our study suggests that AOM-derived byproducts are possibly an essential energy source for tubeworms during chemosynthetic metabolism, shaping different colony types on the seafloor.

The Effect of High Glass Fiber Content and Reinforcement Combination on Pulse-Echo Ultrasonic Measurement of Composite Ship Structures - Sang-Gyu Lee; Daekyun Oh; Jong Hun Woo (Journal of Marine Science and Engineering, 2021)
Ship structures made of glass fiber-reinforced polymer (GFRP) composite laminates are considerably thicker than aircraft and automobile structures and more likely to contain voids. The production characteristics of such composite laminates were investigated in this study by ultrasonic nondestructive evaluation (NDE). The laminate samples were produced from E-glass chopped strand mat (CSM) and woven roving (WR) fabrics with different glass fiber contents of 30–70%. Approximately 300 pulse-echo ultrasonic A-scans were performed on each sample. The laminate samples produced from only CSM tended to contain more voids compared with those produced from a combination of CSM and WR, resulting in the relative density of the former being lower than the design value, particularly for high glass fiber contents of ≥50%. The velocity of the ultrasonic waves through the CSM-only laminates was also lower for higher glass fiber contents, whereas it steadily increased for combined CSM–WR laminates. Burn-off tests of the laminates further revealed that the fabric configuration of the combined CSM–WR laminates was of higher quality, prevented the formation of voids, and improved inter-layer bonding. These findings indicate that combined CSM–WR laminates should be used to achieve more accurate ultrasonic NDE of GFRP composite structures.

Application of Column Chromatography for Accurate Determination of the Carbon Isotopic Compositions of n-alkanes in Diverse Environmental Samples - Dong-Hun Lee; Jung-Hyun Kim; Kyung-Hoon Shin (Ocean Science Journal, 2021)

Bone Generation Following Repeated Administration of Recombinant Bone Morphogenetic Protein 2 - Hye-Ju Son; Mi Nam Lee; Yuri Kim; Hyuck Choi; Byung-Chul Jeong; Sin-Hye Oh; Jung-Woo Kim; Seung-Hee Kwon; Sun-Hun Kim; Soo-Chang Song; Shee Eun Lee; Jeong-Tae Koh (Tissue Engineering and Regenerative Medicine, 2021)

Regulatory role of insulin-like growth factor-binding proteins in odontogenic mineralization in rats - Jung-Sun Moon; Yoo-Sung Nam; Jee-Hae Kang; Dong-Wook Yang; Dae-Yoon Kim; Su-Young Lee; Hyun-Mi Ko; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2021)

The pine wood nematode Bursaphelenchus xylophilus and molecular diagnostic methods - Jin-Pyo Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2021)

Application of Jerusalem artichoke and lipid-extracted algae hydrolysate for docosahexaenoic acid production by Aurantiochytrium sp. KRS101 - Sung-Woon Heo; Young Taek Oh; Z-Hun Kim; Yong Keun Chang; Bongsoo Lee (Journal of Applied Phycology, 2020)

Nucleoredoxin2 (NRX2) Promotes Jasmonate-Mediated Trichome Formation in Arabidopsis - Eun Seon Lee; Joung Hun Park; Gwang Yong Hwang; Yong Hun Chi; Chang Ho Kang; Ho Byoung Chae; Seol Ki Paeng; Seong Dong Wi; Su Bin Bae; Kieu Anh Thi Phan; Sang Yeol Lee (Journal of Plant Biology, 2020)

Scheelite geochemistry of the Sangdong W-Mo deposit and W prospects in the southern Taebaeksan metallogenic region, Korea - Jung Hun Seo; Bong Chul Yoo; Yun-Seok Yang; Jun Hee Lee; Jaeho Jang; Dongbok Shin (Geosciences Journal, 2020)

PoC (Proof of Concept) for Performance Monitoring Platform of Container Terminals - Nam Kyu Park; Jung Hun Lee (Journal of Marine Science and Engineering, 2020)
The purpose of this study is to prove the concept of the performance monitoring system of container terminals. PoC (Proof of Concept) is a realization of a certain method or idea in order to demonstrate its feasibility. The port authorities, such as government or local authority, are continually checking the performance of the terminals they invested in and want to reflect it in the development policy. They also want to increase competitiveness by checking performance levels, such as port handling volume, calling ships, resource utilization, and congestion. PPI (Port performance indicators) are classified into four categories: output (production), productivity, utilization, and service. In this study, 15 monitoring indicators for each stage by dividing the process from the ship’s entry to departure are defined. Four indicators, such as ship waiting ratio at anchorage, berth occupancy, storage occupancy, and truck turnaround time, are selected as PoC of monitoring platform. In addition, a method of collecting, processing, and expressing data on these four indicators in real time is presented. There are three steps to create PPI on monitoring platform. The information required for PPI is to be collected from the Port-MIS (Management Information System) and TOS (Terminal Operating System) databases. Second, the collected data from external entities are stored into the database after verification and classification. Third, descriptive PPI, predictive PPI are generated based on the input data. This study provides a 4-tier framework from the conceptual platform with the key elements of data presentation, data process and data interface and middleware. As a result of the study, it is proved to select monitoring indicators, define external entities, define internal elements of the system, develop systems, and present indicator results. However, in the process of collecting data outside the system, we have found there is confidential data of individual terminals. To this end, it is important to establish a mutual cooperation system for data collection.

Application of the anion-exchange resin as a complementary technique to remove residual cyanide complexes in industrial plating wastewater after conventional treatment - Jae-Hun Chu; Jin-Kyu Kang; Seong-Jik Park; Chang-Gu Lee (Environmental Science and Pollution Research, 2020)

Evaluation of genetic toxicity, acute and sub-chronic oral toxicity and systemic safety of Agrimonia pilosa and Rhus gall 50% ethanolic extract mixture (APRG64) in vitro and in vivo (rodent and non-rodent animal models) - Jong-Hun Park; Jong-Sung Ra; Jeong Eun Kwon; Yang-Mi Her; Tae Hwan Choe; Yoon-Seo Lee; Hee Ju Suh; Seung-Yeon Shin; Dae Won Park; Ho-Hyun Kwak; Heung-Myong Woo; Hyelin Jeon; et al. (Toxicological Research, 2020)

Ecotourism development and the heterogeneity of tourists - Joung Hun Lee; Yoh Iwasa (Theoretical Ecology, 2020)
Ecotourism is potentially capable of making biodiversity conservation and ecosystem management economically feasible. Here, we propose a simple model for ecotourism development considering the heterogeneity of tourists, motivated by the case of Jeju Island, South Korea. We analyze the optimal investment in accommodation capacity (i.e., hotels, restaurants, and transportation) and in improving the quality of the environment (i.e., biodiversity, landscape, and cultural activities). “General tourists” are abundant but will not return to the focal site, and their future number is unpredictable, while “loyal tourists” may return to the site if they are attracted by its environmental and/or cultural assets. The analysis shows that the economically profitable policy is either the one with a large investment in accommodation capacity targeting general tourists or the one with a large investment to environmental quality targeting loyal tourists, but an intermediate mixture of these extremes cannot be the optimal. We also discuss “zoning,” in which a site is separated to two areas, and many visitors stay in the first area and visit the second area to enjoy the high-quality environment.

Molecular Detection and Assessment of Risk Factors for Tick-Borne Diseases in Sheep and Goats from Turkey - Byamukama Benedicto; Onur Ceylan; Paul Frank Adjou Moumouni; Seung-Hun Lee; Maria Agnes Tumwebaze; Jixu Li; Eloiza May Galon; Mingming Liu; Yongchang Li; Shengwei Ji; Aaron Ringo; Mohamed Rizk; et al. (Acta Parasitologica, 2020)

Characterization of genetic variation and antioxidant properties in strawberry (Fragaria × ananassa Duch.) mutant genotypes - Jaihyunk Ryu; Woon Ji Kim; Sang Hun Kim; Kang-Seop Lee; Han-Jig Jo; Ee-Youb Kim; Sang Hoon Kim; Si-Yong Kang; Jeong-Hee Lee; Bo-Keun Ha (Genetic Resources and Crop Evolution, 2020)

Aptamer-linked immobilized sorbent assay for detecting GMO marker, phosphinothricin acetyltransferase (PAT) - Woo-Ri Shin; Mun-Jong Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2020)

Wax-printed well pads and colorimetric LAMP detection of ApxIA toxin gene - SeonHyung Lee; Ji Hun Kim; Beom-Ku Han; Won-Il Kim; Byung-Kwan Cho; Sung Min Woo; Yang-Hoon Kim; Ji-Young Ahn (Molecular & Cellular Toxicology, 2020)

Association between the IL-6, IL-10, and TNFα gene polymorphisms and preterm-birth in Korean women - Seung Hun Han; Noo Ri Lee; Hyung Jun Kim; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Genes & Genomics, 2020)

Risk assessment for humans using physiologically based pharmacokinetic model of diethyl phthalate and its major metabolite, monoethyl phthalate - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Archives of Toxicology, 2020)

Anti-inflammatory and Anti-osteoporotic Potential of Lactobacillus plantarum A41 and L. fermentum SRK414 as Probiotics - Chul Sang Lee; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Improvements of 6S Look-Up-Table Based Surface Reflectance Employing Minimum Curvature Surface Method - Kyeong-Sang Lee; Chang Suk Lee; Minji Seo; Sungwon Choi; Noh-Hun Seong; Donghyun Jin; Jong-Min Yeom; Kyung-Soo Han (Asia-Pacific Journal of Atmospheric Sciences, 2020)
We propose a methodology employing an interpolation technique on the Second Simulation of a Satellite Signal (6S) look-up table (LUT) to improve surface reflectance retrieval using Himawari-8/Advanced Himawari Imager (AHI). A minimum curvature surface (MCS) technique was used to refine the 6S LUT, and the solar zenith angle (SZA) and viewing zenith angle (VZA) increments were narrowed by 0.5°. The interpolation processing time was relatively short, about 3172 s per channel, and the interpolated xa and xb were well represented by the changes in SZA and VZA. An evaluation of the interpolated xa and xb for six cases revealed a relative mean absolute error of less than 5% for all channels and cases; however, a slight difference was evident for higher values of SZA and VZA. To evaluate the surface reflectance, we compared the surface reflectance derived using 6S LUT with that calculated using 6S only. Application of the interpolated 6S LUT showed a lower relative root mean square error (RRMSE) of 0.65% to 9.29% for all channels, than before interpolation. The improvement in surface reflectance measurements increased with the SZA. For a SZA above 75°, the RRMSE improved significantly for all channels (by 11.33–45.1%). In addition, when the MCS method was applied, the surface reflectance measurements improved without spatial discontinuity and showed good agreement with 6S results in a linear profile analyses. Thus, the method proposed can improve LUT based surface reflectance measurements in less time and increase the availability of surface reflectance data based on geostationary satellites.

Protective effect of Lactobacillus casei HY2782 against particulate matter toxicity in human intestinal CCD-18Co cells and Caenorhabditis elegans - Joo Yeon Kim; So Young Lee; Seung-Hee Jung; Mi Ri Kim; Il-Dong Choi; Jung-Lyoul Lee; Jae-Hun Sim; Cheol-Ho Pan; Kyungsu Kang (Biotechnology Letters, 2020)

Chaperone function of Arabidopsis NPR1 - Seol Ki Paeng; Yong Hun Chi; Chang Ho Kang; Ho Byoung Chae; Eun Seon Lee; Joung Hun Park; Seong Dong Wi; Su Bin Bae; Kieu Anh Thi Phan; Sang Yeol Lee (Plant Biotechnology Reports, 2020)

Vaginal plug formation and release in female hibernating Korean greater horseshoe bat, Rhinolophus ferrumequinum korai (Chiroptera: Rhinolophidae) during the annual reproductive cycle - Jung-Hun Lee (Zoomorphology, 2020)

Emerging trends in municipal solid waste incineration ashes research: a bibliometric analysis from 1994 to 2018 - Syieluing Wong; Angel Xin Yee Mah; Abu Hassan Nordin; Bemgba Bevan Nyakuma; Norzita Ngadi; Ramli Mat; Nor Aishah Saidina Amin; Wai Shin Ho; Ting Hun Lee (Environmental Science and Pollution Research, 2020)

A sensitive UPLC–ESI–MS/MS method for the quantification of cinnamic acid in vivo and in vitro: application to pharmacokinetic and protein binding study in human plasma - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; In-Joon Oh; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2020)

Estimation of the Motion Performance of a Light Buoy Adopting Ecofriendly and Lightweight Materials in Waves - Se-Min Jeong; Bo-Hun Son; Chang-Yull Lee (Journal of Marine Science and Engineering, 2020)
In this study, the methods and results of numerical simulations to estimate the motion performance of a newly developed lightweight light buoy in waves and to check the effect of conceptually developed appendages on that performance were introduced. The results from a potential-based motion analysis with viscous damping coefficients obtained from free decay tests using computational fluid dynamics (CFD) and those obtained from wave motion simulation using CFD were compared. From these results, it was confirmed that viscous damping should be considered when the frequency of an incoming wave is close to the natural frequency of the buoy. It was estimated that the pitch and heave motions of the light buoy became smaller when the developed appendages were adopted. Although the quantitative superiority of the appendages was different, the qualitative superiority was similar between both results.

Anti-inflammatory effect of bee venom in phthalic anhydride-induced atopic dermatitis animal model - Yu Jin Lee; Myung Jin Oh; Dong Hun Lee; Yong Sun Lee; Jiin Lee; Deok-Hyun Kim; Cheol-Hoon Choi; Min Jong Song; Ho Sueb Song; Jin Tae Hong (Inflammopharmacology, 2020)

Improvement China Point Source for Improving Bottom-Up Emission Inventory - Youjung Jang; Yungu Lee; Jinseok Kim; Younha Kim; Jung-Hun Woo (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Correction to: M1 macrophage dependent-p53 regulates the intracellular survival of mycobacteria - Yun-Ji Lim; Junghwan Lee; Ji-Ae Choi; Soo-Na Cho; Sang-Hun Son; Sun-Jung Kwon; Ji-Woong Son; Chang-Hwa Song (Apoptosis, 2020)
The original version of this article unfortunately contains an error in the acknowledgement section. The text “Brain Korea 21 PLUS Project for Medical Science, Chungnam National University” was omitted by mistake. The correct and complete acknowledgment is given below: Acknowledgments This work was supported by the research fund of Chungnam National University and the Brain Korea 21 PLUS Project for Medical Science, Chungnam National University. The funders had no role in study design, data collection and analysis decision to publish, or preparation of the manuscript.

M1 macrophage dependent-p53 regulates the intracellular survival of mycobacteria - Yun-Ji Lim; Junghwan Lee; Ji-Ae Choi; Soo-Na Cho; Sang-Hun Son; Sun-Jung Kwon; Ji-Woong Son; Chang-Hwa Song (Apoptosis, 2020)
Tumor suppressor p53 is not only affects immune responses but also contributes to antibacterial activity. However, its bactericidal function during mycobacterial infection remains unclear. In this study, we found that the p53-deficient macrophages failed to control Mycobacterium tuberculosis (Mtb), manifested as a lower apoptotic cell death rate and enhanced intracellular survival. The expression levels of p53 during Mtb infection were stronger in M1 macrophages than in M2 macrophages. The TLR2/JNK signaling pathway plays an essential role in the modulation of M1 macrophage polarization upon Mtb infection. It facilitates p53-mediated apoptosis through the production of reactive oxygen species, nitric oxide and inflammatory cytokines in Mtb-infected M1 macrophages. In addition, nutlin-3 effectively abrogated the intracellular survival of mycobacteria in both TB patients and healthy controls after H37Ra infection for 24 h, indicating that the enhancement of p53 production effectively suppressed the intracellular survival of Mtb in hosts. These results suggest that p53 can be a new therapeutic target for TB therapy.

Bacterial endosymbiont of Oligobrachia sp. (Frenulata) from an active mud volcano in the Canadian Beaufort Sea - Yung Mi Lee; Hyun-Ju Noh; Dong-Hun Lee; Jung-Hyun Kim; Young Keun Jin; Charles Paull (Polar Biology, 2019)

Synthesis and anti-endoplasmic reticulum stress activity of N-substituted-2-arylcarbonylhydrazinecarbothioamides - Hoon Choi; Wheesahng Yun; Jung-hun Lee; Seoul Jang; Sang Won Park; Dong Hwan Kim; Kyoung Pyo Seon; Jung-mi Hyun; Kwiwan Jeong; Jin-mo Ku; Tae-gyu Nam (Medicinal Chemistry Research, 2019)

Downregulated UCHL1 Accelerates Gentamicin-Induced Auditory Cell Death via Autophagy - Yeon Ju Kim; Kyung Kim; Yun Yeong Lee; Oak-Sung Choo; Jeong Hun Jang; Yun-Hoon Choung (Molecular Neurobiology, 2019)

Comparison of UPLC-MS/MS and HPLC-UV methods for the determination of zaltoprofen in human plasma - Ji-Hun Jang; Seung-Hyun Jeong; Hea-Young Cho; Yong-Bok Lee (Journal of Pharmaceutical Investigation, 2019)

Gender differences in pharmacokinetics and tissue distribution of 4-n-nonylphenol in rats - Seung-Hyun Jeong; Ji-Hun Jang; Hea-Young Cho; Yong-Bok Lee (Archives of Toxicology, 2019)

The relationship among meteorological, agricultural, and in situ news-generated big data on droughts - Ji-Wan Lee; Chung-Gil Jung; Jee-Hun Chung; Seong-Joon Kim (Natural Hazards, 2019)

Alteration of microRNA 340-5p and Arginase-1 Expression in Peripheral Blood Cells during Acute Ischemic Stroke - Hanna Yoo; Jinkwon Kim; Ae-Ri Lee; Ji-Min Lee; Ok-Joon Kim; Jin-Kyeoung Kim; Seung-Hun Oh (Molecular Neurobiology, 2019)

Genetic risk score combining six genetic variants associated with the cellular NRF2 expression levels correlates with Type 2 diabetes in the human population - Jae Hun Shin; Kyung-Mi Lee; Jimin Shin; Kui Dong Kang; Chu Won Nho; Yoon Shin Cho (Genes & Genomics, 2019)

Independent origins of coastal colonization in the tribe Athetini (Coleoptera, Staphylinidae) - Jeong‐Hun Song; Seung‐Gyu Lee; Jae‐Seok Lee; Kee‐Jeong Ahn (Zoologica Scripta, 2019)
Less than 1% of Staphylinidae are known to be confined to coastal habitats. To explore the origins of coastal colonization within the tribe Athetini Casey, we present a revised molecular phylogeny. The dataset comprised partial mitochondrial COI , COII , 16S rDNA, NADH1 , partial nuclear 18S rDNA and 28S rDNA. We chose a total of 95 species in 51 genera, including 14 coastal species in eight genera and 21 outgroup species from other aleocharine tribes. The concatenated dataset was analysed simultaneously by both parsimony‐ and model‐based (Bayesian and maximum likelihood) methods. The tribe Athetini was not supported as a monophyletic group, but together with the tribes Tachyusini, Ecitocharini and Hygronomini did form a monophylum. The ecological association of species with a coastal habitat was mapped onto a phylogeny to assess the evolution of habitat specialization in the Athetini lineage. The results reveal that five independent origins of coastal colonization have occurred throughout the tribe Athetini: (a) Osakatheta + Adota minuta + coastal Atheta ( Badura ) (clade A); (b) Adota (clade B); (c) Pontomalota + Tarphiota + Thinusa (clade C); (d) Iotarphia (clade D); and (e) Psammostiba (clade E). The low species number of the coastal Athetini compared with the entire Athetini lineage indicates that coastal habitats are harsh environments and so only a few species were able to colonize this habitat. The following changes in classification are proposed: (a) Ad. minuta Lee and Ahn is removed from the genus Adota and tentatively included in Atheta ( Badura ); (b) The genus Saphocallus Sharp is transferred from Athetini to Geostibini.

A 90-Day Repeated Oral Dose Toxicity Study of Alismatis Rhizoma Aqueous Extract in Rats - Mu-Jin Lee; Ho-Kyung Jung; Ki-Ho Lee; Ji-Hun Jang; Mi-Ok Sim; Tea-Gyeong Seong; Byung-Kwan Ahn; Jin-Han Shon; Seong-Ho Ham; Hyun-Woo Cho; Yong-Min Kim; Sung-Jin Park; et al. (Toxicological Research, 2019)

The associations of TAC1 gene polymorphisms with major depressive disorder - Eunsoo Won; Kyu-Man Han; Aram Kim; Min-Soo Lee; Yong-Ku Kim; Hun Soo Chang; Byung-Joo Ham (Molecular & Cellular Toxicology, 2019)

Prolonged shedding of type 55 human adenovirus in immunocompetent adults with adenoviral respiratory infections - Kyungmin Huh; Inseon Kim; Jaehun Jung; Ji Eun Lee; Byung Woo Jhun; Se Hun Gu; Dong Hyun Song; Eun Young Lee; Ho Jung Jeong; Hongseok Yoo (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Concentrations of particulate matter, carbon dioxide, VOCs and risk assessment inside Korean taxis and ships - Ho-Hyun Kim; Gee-Young Park; Jeong-Hun Lee (Environmental Science and Pollution Research, 2019)

Gene delivery into Siberian sturgeon cell lines by commercial transfection reagents - Ji Hun Lee; Seung Tae Lee; Yoon Kwon Nam; Seung Pyo Gong (In Vitro Cellular & Developmental Biology - Animal, 2019)

Sonophotocatalytic degradation of bisphenol A and its intermediates with graphitic carbon nitride - Sharmini Sunasee; Kah Hon Leong; Kien Tiek Wong; Gooyong Lee; Saravanan Pichiah; InWook Nah; Byong-Hun Jeon; Yeomin Yoon; Min Jang (Environmental Science and Pollution Research, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Association of glutathione S-transferase M1 and T1 null/present polymorphism with physical performance in the Korean population - In Wook Hwang; Kicheol Kim; Bit Na Kwon; Hyung Jun Kim; Seung Hun Han; Noo Ri Lee; Eun Ji Choi; Hyun Ik Cho; Han Jun Jin (Genes & Genomics, 2019)

Determination of Mycoplasma hyopneumoniae-Specific IgG, IgG1, and IgG2a Titers in BALB/c Mice Induced by Mineral Oil-Based Oil-in-Water Emulsion Adjuvants Prepared Using a Self-Emulsifying Drug Delivery System - Rakesh Bastola; Jo-Eun Seo; Gyubin Noh; Taekwang Keum; Ju Hun Kim; Jong Il Shin; Sooyeun Lee; Sangkil Lee (AAPS PharmSciTech, 2019)

Profit sharing and agroforestry: a theoretical study of potential conflicts in managing illegal logging risk in tropical forests - Yuki Kubo; Joung-Hun Lee; Takahiro Fujiwara; Ratih Madya Septiana; Yoh Iwasa (Theoretical Ecology, 2018)

Physiological Characteristics and Related Biochemical Parameters of Snow Algae from King George Island, Antarctica - Bo Kyung Kim; HyoungMin Joo; Boyeon Lee; Dong-Hun Lee; In-Young Ahn; Sun-Yong Ha (Ocean Science Journal, 2018)

Complete mitochondrial genome of the invasive semi-aquatic mammal, nutria Myocastor coypus (Rodentia; Myocastoridae) - Do-Hun Lee; Moo-Seung Lee; Young-Chae Kim; Il Ryong Kim; Hye Kwon Kim; Dae Gwin Jeong; Jung Ro Lee; Ji Hyung Kim (Conservation Genetics Resources, 2018)

Calibration of the Pyranometer Sensitivity Using the Integrating Sphere - Bu-Yo Kim; Kyu-Tae Lee; Il-Sung Zo; Sang-Ho Lee; Hyun-Seok Jung; Se-Hun Rim; Jeong-Pil Jang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Ferulate, an Active Component of Wheat Germ, Ameliorates Oxidative Stress-Induced PTK/PTP Imbalance and PP2A Inactivation - Eun Mi Koh; Eun Kyeong Lee; Chi Hun Song; Jeongah Song; Hae Young Chung; Chang Hoon Chae; Kyung Jin Jung (Toxicological Research, 2018)

Molecular characterization of proton beam-induced mutations in soybean using genotyping-by-sequencing - Woon Ji Kim; Jaihyunk Ryu; Juhyun Im; Sang Hun Kim; Si-Yong Kang; Jeong-Hee Lee; Sung-Hwan Jo; Bo-Keun Ha (Molecular Genetics and Genomics, 2018)

Improvement of biomass and fatty acid productivity in ocean cultivation of Tetraselmis sp. using hypersaline medium - Hanwool Park; Daewoo Jung; Jongchan Lee; Philhan Kim; Yonghee Cho; Injae Jung; Z-Hun Kim; Sang-Min Lim; Choul-Gyun Lee (Journal of Applied Phycology, 2018)

Efficient spoofing identification using baseline vector information of multiple receivers - Seong-Hun Seo; Byung-Hyun Lee; Sung-Hyuck Im; Gyu-In Jee; Kwan-Sung Kim (GPS Solutions, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

SHRIMP U–Pb ages of detrital zircons from the Early Cretaceous Nakdong Formation, South East Korea: Timing of initiation of the Gyeongsang Basin and its provenance - Tae‐Ho Lee; Kye‐Hun Park; Keewook Yi (Island Arc, 2018)
To constrain the depositional age of the lowermost Nakdong Formation in the Early Cretaceous Gyeongsang Basin, SHRIMP U–Pb age determination was carried out on zircon separates. The U–Pb compositions of detrital zircons from the Nakdong Formation yield a wide range of ages from the Archean to the Cretaceous but show a marked contrast in age distribution according to the geographical locations within the basin. The provenance of the southern Nakdong Formation is dominantly the surrounding Yeongnam Massif, which is composed of Paleoproterozoic metamorphic rocks and Triassic to Jurassic plutonic rocks, whereas the central to northern Nakdong Formation records significant sediment derivation from the Okcheon Metamorphic Belt, which is distributed to the northwest, in addition to the contribution from the Yeongnam Massif. It is suggested that the maximum depositional age of the Nakdong Formation is ca 127 Ma, based on its youngest detrital zircon age population. The onset of its deposition at 127 Ma coincided with the tectonic inversion in East Asia from a compressional to an extensional geodynamic setting, probably due to the contemporaneous change in the drift direction of the Izanagi Plate and its subsequent oblique subduction.

Thermoresponsive and Biodegradable Amphiphilic Block Copolymers with Pendant Functional Groups - Bo Keun Lee; Jung Hyun Noh; Ji Hoon Park; Seung Hun Park; Jae Ho Kim; Se Heang Oh; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2018)

Correction to: Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Impact of Shewanella oneidensis on heavy metals remobilization under reductive conditions in soil of Guilan Province, Iran - Nasrin Ghorbanzadeh; Rahul Kumar; Sang-hun Lee; Hyun-Sung Park; Byong-Hun Jeon (Geosciences Journal, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Preparation and in vivo characterization of dual release tablet containing sarpogrelate hydrochloride - Hun Jun; Hyo-Jung Lee; Beom-Soo Shin; Chun-Woong Park (Journal of Pharmaceutical Investigation, 2018)

Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Retrieval Algorithm for Broadband Albedo at the Top of the Atmosphere - Sang-Ho Lee; Kyu-Tae Lee; Bu-Yo Kim; ll-Sung Zo; Hyun-Seok Jung; Se-Hun Rim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Isolation and genomic characterization of a novel avian orthoreovirus strain in Korea, 2014 - Jin-Yong Noh; Dong-Hun Lee; Tae-Hyun Lim; Ji-ho Lee; J. Michael Day; Chang-Seon Song (Archives of Virology, 2018)

Beneficial Effects of Cynaroside on Cisplatin-Induced Kidney Injury In Vitro and In Vivo - Jong-Hyun Nho; Ho-Kyung Jung; Mu-Jin Lee; Ji-Hun Jang; Mi-Ok Sim; Da-Eun Jeong; Hyun-Woo Cho; Jong-Choon Kim (Toxicological Research, 2018)

Variation of temperature-dependent sound velocity in unconsolidated marine sediments: Laboratory measurements - Sora Kim; Gwang Soo Lee; Daechoul Kim; Jooyoung Hahn; Woo-Hun Ryang (Marine Georesources & Geotechnology, 2018)

Ascorbic Acid Ameliorates Gestational Lead Exposure-Induced Developmental Alteration in GAD67 and c-Kit Expression in the Rat Cerebellar Cortex - Sung Min Nam; Sung Chuel Ahn; Tae-Hun Go; Jin Seok Seo; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2018)

Transcriptome analysis of the threatened snail Ellobium chinense reveals candidate genes for adaptation and identifies SSRs for conservation genetics - Se Won Kang; Bharat Bhusan Patnaik; So Young Park; Hee-Ju Hwang; Jong Min Chung; Min Kyu Sang; Hye Rin Min; Jie Eun Park; Jiyeon Seong; Yong Hun Jo; Mi Young Noh; Jong Dae Lee; et al. (Genes & Genomics, 2018)

Interannual Variation of Surface Circulation in the Japan/East Sea due to External Forcings and Intrinsic Variability - Byoung-Ju Choi; Seong Hun Cho; Hee Seok Jung; Sang-Ho Lee; Do-Seong Byun; Kyungman Kwon (Ocean Science Journal, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Multi-locus phylogenetic analyses support the monophyly and the Miocene diversification of Iksookimia (Teleostei: Cypriniformes: Cobitidae) - Ye-Seul Kwan; Daemin Kim; Myeong-Hun Ko; Wan-Ok Lee; Yong-Jin Won (Systematics and Biodiversity, 2018)

Interfacial Reaction Between Ultra Low C Steel and Gas Generated from Refractory Material Used for Submerged Entry Nozzle for Continuous Casting - Joo-Hyeok Lee; Sung-Kwang Kim; Myeong-Hun Kang; Youn-Bae Kang (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Effect of Drug Carrier Melting Points on Drug Release of Dexamethasone-Loaded Microspheres - Ji Hoon Park; Doo Yeon Kwon; Ji Yeon Heo; Seung Hun Park; Joon Yeong Park; Bong Lee; Jae Ho Kim; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2017)

Accuracy evaluation of the crop-weather yield predictive models of Italian ryegrass and forage rye using cross-validation - Jing-Lun Peng; Moon-Ju Kim; Mu-Hwan Jo; Doo-Hong Min; Kyung-Dae Kim; Bae-Hun Lee; Byong-Wan Kim; Kyung-Il Sung (Journal of Crop Science and Biotechnology, 2017)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Geochemical studies of banded iron formations (BIFs) in the North China Craton: a review - Inkyeong Moon; Insung Lee; Jung Hun Seo; Xiaoyong Yang (Geosciences Journal, 2017)

Novel reassortant clade 2.3.4.4 avian influenza A (H5N8) virus in a grey heron in South Korea in 2017 - Chanjin Woo; Jung-Hoon Kwon; Dong-Hun Lee; Youngsik Kim; Kwanghee Lee; Seong-Deok Jo; Ki dong Son; Jae-Ku Oem; Seung-Jun Wang; Yongkwan Kim; Jeonghwa Shin; Chang-Seon Song; et al. (Archives of Virology, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Neuronal nitric oxide synthase modulation of intracellular Ca2+ handling overrides fatty acid potentiation of cardiac inotropy in hypertensive rats - Chun Li Jin; Ming Zhe Yin; Jin Chul Paeng; Seunggyun Ha; Jeong Hoon Lee; Peng Jin; Chun Zi Jin; Zai Hao Zhao; Yue Wang; Keon Wook Kang; Chae Hun Leem; Jong-Wan Park; et al. (Pflügers Archiv - European Journal of Physiology, 2017)

Phytochemical profile and angiotensin I converting enzyme (ACE) inhibitory activity of Limonium michelsonii Lincz - Janar Jenis; Jeong Yoon Kim; Zia Uddin; Yeong Hun Song; Hyeong-Hwan Lee; Ki Hun Park (Journal of Natural Medicines, 2017)

Effects of microwaves on the reduction of Aspergillus flavus and Aspergillus parasiticus on brown rice ( Oryza sativa L.) and barley ( Hordeum vulgare L.) - Seung-Hun Lee; Shin Young Park; Kye-Hwan Byun; Hyang Sook Chun; Sang-Do Ha (Food Additives & Contaminants: Part A, 2017)

A comparative study on generating simulated Landsat NDVI images using data fusion and regression method—the case of the Korean Peninsula - Mi Hee Lee; Soo Bong Lee; Yang Dam Eo; Sun Woong Kim; Jung-Hun Woo; Soo Hee Han (Environmental Monitoring and Assessment, 2017)

Neurophysiology of space travel: energetic solar particles cause cell type-specific plasticity of neurotransmission - Sang-Hun Lee; Barna Dudok; Vipan K. Parihar; Kwang-Mook Jung; Miklós Zöldi; Young-Jin Kang; Mattia Maroso; Allyson L. Alexander; Gregory A. Nelson; Daniele Piomelli; István Katona; Charles L. Limoli; et al. (Brain Structure and Function, 2017)

Functional characterization of cytochrome P450 monooxygenases in the cereal head blight fungus F usarium graminearum - Ji Young Shin; Duc‐Cuong Bui; Yoonji Lee; Hyejin Nam; Soyun Jung; Miao Fang; Jin‐Cheol Kim; Theresa Lee; Hun Kim; Gyung Ja Choi; Hokyoung Son; Yin‐Won Lee (Environmental Microbiology, 2017)
Summary Fusarium graminearum is a prominent plant pathogenic fungus causing Fusarium head blight in major cereal crops worldwide. To understand the molecular mechanisms underlying fungal development and virulence, large collections of F. graminearum mutants have been constructed. Cytochrome P450 monooxygenases (P450s) are widely distributed in organisms and are involved in a diverse array of molecular/metabolic processes; however, no systematic functional analysis of P450s has been attempted in filamentous fungi. In this study, we constructed a genome‐wide deletion mutant set covering 102 P450s and analyzed these mutants for changes in 38 phenotypic categories, including fungal development, stress responses and responses to several xenobiotics, to build a comprehensive phenotypic dataset. Most P450 mutants showing defective phenotypes were impaired in a single phenotypic trait, demonstrating that our mutant library is a good genetic resource for further fungal genetic studies. In particular, we identified novel P450s specifically involved in virulence (5) and both asexual (1) and sexual development (2). Most P450s seem to play redundant roles in the degradation of xenobiotics in F. graminearum . This study is the first phenome‐based functional analysis of P450s, and it provides a valuable genetic resource for further basic and applied biological research in filamentous fungi and other plant pathogens.

Autophagic flux analysis of Arabidopsis seedlings exposed to salt stress - Hyera Jung; Jeong Hun Kim; Kwang Deok Shin; Jimi Kim; Han Nim Lee; Taijoon Chung (Journal of Plant Biology, 2017)

Transcriptome analysis of non-small cell lung cancer and genetically matched adjacent normal tissues identifies novel prognostic marker genes - Man Seok Bang; Keunsoo Kang; Jung-ju Lee; Yea-Jin Lee; Jin Eun Choi; Ju Yeon Ban; Chung-Hun Oh (Genes & Genomics, 2017)

In silico study on Arabidopsis BAG gene expression in response to environmental stresses - Ganesh M. Nawkar; Punyakishore Maibam; Joung Hun Park; Su Gyeong Woo; Cha Young Kim; Sang Yeol Lee; Chang Ho Kang (Protoplasma, 2017)

Three-Dimensional Printing of Tissue/Organ Analogues Containing Living Cells - Jeong Hun Park; Jinah Jang; Jung-Seob Lee; Dong-Woo Cho (Annals of Biomedical Engineering, 2017)

Current advances in three-dimensional tissue/organ printing - Jeong Hun Park; Jinah Jang; Jung-Seob Lee; Dong-Woo Cho (Tissue Engineering and Regenerative Medicine, 2016)

Distinguishing tendon and ligament fibroblasts based on 1H nuclear magnetic resonance spectroscopy - Hun Yeong Ban; Ji Won Shin; Song-I Chun; Yun Gyeong Kang; Yanru Wu; Ji Eun Kim; Eun Jin Lee; Mi Jin Kim; Chi-Woong Mun; Jung-Woog Shin (Tissue Engineering and Regenerative Medicine, 2016)

Human chorionic gonadotropin (hCG) sub-chronic administration mediated MMP-9 activities and cytokine association deteriorate experimental autoimmune encephalomyelitis (EAE) condition in mice model - Joon-Seung Han; Khandoker Asiqur Rahaman; Ji-Eun Seo; Mahbub Hasan; Kyung-Tae Lee; Hophil Min; Kang Mi Lee; Ju-Hyung Park; Ho Jun Kim; Ki Hun Kim; Junghyun Son; Jaeick Lee; et al. (Journal of Pharmaceutical Investigation, 2016)

Geophysical evidence and inferred triggering factors of submarine landslides on the western continental margin of the Ulleung Basin, East Sea - Deniz Cukur; Seong-Pil Kim; Gee-Soo Kong; Jang-Jun Bahk; Senay Horozal; In-Kwon Um; Gwang-Soo Lee; Tae-Soo Chang; Hun-Jun Ha; David Völker; Jung-Ki Kim (Geo-Marine Letters, 2016)

Cardiac inotropy, lusitropy, and Ca2+ handling with major metabolic substrates in rat heart - Zai Hao Zhao; Jae Boum Youm; Yue Wang; Jeong Hoon Lee; Jae Hwi Sung; Joon-Chul Kim; Sun Hee Woo; Chae Hun Leem; Sung Joon Kim; Lan Cui; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2016)

Genomic structure, expression and association study of the porcine FSD2 - Kyu-Sang Lim; Kyung-Tai Lee; Si-Woo Lee; Han-Ha Chai; Gulwon Jang; Ki-Chang Hong; Tae-Hun Kim (Molecular Biology Reports, 2016)

Mitochondria-targeted DsRed2 protein expression during the early stage of bovine somatic cell nuclear transfer embryo development - Hyo-Jin Park; Sung-Hun Min; Hoonsung Choi; Junghyung Park; Sun-Uk Kim; Seunghoon Lee; Sang-Rae Lee; Il-Keun Kong; Kyu-Tae Chang; Deog-Bon Koo; Dong-Seok Lee (In Vitro Cellular & Developmental Biology - Animal, 2016)

RNAi-mediated Soybean mosaic virus (SMV) resistance of a Korean Soybean cultivar - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Hyun Hee Im; Dong Hee Lee; Kook-Hyung Kim; Jai-Heon Lee; Doh-Hoon Kim; Hong Kyu Choi; Ho Won Jung; Young-Soo Chung (Plant Biotechnology Reports, 2016)

The application of catalyst-recovered SnO2 as an anode material for lithium secondary batteries - Da-Jeong Ryu; Hee-Won Jung; Sung-Hun Lee; Da-Jeong Park; Kwang-Sun Ryu (Environmental Science and Pollution Research, 2016)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

CCR5 deficiency increased susceptibility to lipopolysaccharide-induced acute renal injury - Dong Hun Lee; Mi Hee Park; Chul Ju Hwang; Jae Yeon Hwang; Hae Suk Yoon; Do Young Yoon; Jin Tae Hong (Archives of Toxicology, 2016)

Policy framework for geospatial technology based on the open source GIS SW in South Korea - Byong Nam Choe; Sang Hee Shin; Ji Hun Lee (Spatial Information Research, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Insecticides induced biochemical changes in freshwater microalga Chlamydomonas mexicana - Muthukannan Satheesh Kumar; Akhil N. Kabra; Booki Min; Marwa M. El-Dalatony; Jiuqiang Xiong; Nooruddin Thajuddin; Dae Sung Lee; Byong-Hun Jeon (Environmental Science and Pollution Research, 2016)

Effects of cultivar and harvest time on the contents of antioxidant phytochemicals in strawberry fruits - Venti Winardiantika; Young Hun Lee; Nam Il Park; Young-Rog Yeoung (Horticulture, Environment, and Biotechnology, 2015)

Perchlorate reduction from a highly concentrated aqueous solution by bacterium Rhodococcus sp. YSPW03 - Sang-Hoon Lee; Jae-Hoon Hwang; Akhil N. Kabra; Reda A. I. Abou-Shanab; Mayur B. Kurade; Booki Min; Byong-Hun Jeon (Environmental Science and Pollution Research, 2015)

Influence of clay minerals on sorption and bioreduction of arsenic under anoxic conditions - Nasrin Ghorbanzadeh; Amir Lakzian; Akram Halajnia; Akhil N. Kabra; Mayur B. Kurade; Dae S. Lee; Byong-Hun Jeon (Environmental Geochemistry and Health, 2015)

Development of liquid chromatography tandem mass spectrometry method for determination of spironolactone in human plasma: application to a bioequivalence study of Daewon Spiracton tablet® (spironolactone 50 mg) - Jeong-Hun Lee; Tae-Gil An; Su Jung Kim; Wang-Seob Shim; Kyung-Tae Lee (Journal of Pharmaceutical Investigation, 2015)

Erratum to: Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Distribution and long-term trends in various fog types over South Korea - Miloslav Belorid; Chong Bum Lee; Jea-Chul Kim; Tae-Hun Cheon (Theoretical and Applied Climatology, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Algal biomass and biodiesel production by utilizing the nutrients dissolved in seawater using semi-permeable membrane photobioreactors - Z-Hun Kim; Hanwool Park; Young-Jin Ryu; Dong-Woo Shin; Seong-Joo Hong; Hai-Linh Tran; Sang-Min Lim; Choul-Gyun Lee (Journal of Applied Phycology, 2015)

Comparison of the toxicity of aluminum oxide nanorods with different aspect ratio - Eun-Jung Park; Gwang-Hee Lee; Jae-hun Shim; Myung-Haing Cho; Byoung-Seok Lee; Yong-Bum Kim; Jae-Ho Kim; Younghun Kim; Dong-Wan Kim (Archives of Toxicology, 2015)

Raloxifene inhibits cloned Kv4.3 channels in an estrogen receptor-independent manner - Yun Ju Chae; Dae Hun Kim; Hong Joon Lee; Ki-Wug Sung; Oh-Joo Kwon; Sang June Hahn (Pflügers Archiv - European Journal of Physiology, 2015)

Genetic diversity and population structure in cultivated and weedy types of Perilla in East Asia and other countries as revealed by SSR markers - Kyu Jin Sa; Seung Hun Choi; Mariko Ueno; Ju Kyong Lee (Horticulture, Environment, and Biotechnology, 2015)

Influence of various nutrient concentrations on the growth and yield of summer strawberry cultivars cultivated in a hydroponic system - Young Hun Lee; Cheol Soo Yoon; Nam Il Park; Young Rog Yeoung (Horticulture, Environment, and Biotechnology, 2015)

Toxic metal content in 52 frequently prescribed herbal medicines on the Korean market - Donggyu Kim; Kwang-Ho Hwang; Mokyoung Lee; Jung-Hun Kim; Kweon Jung; Seung-Kook Park (Food Additives & Contaminants Part B-Surveillance, 2015)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Fine structural traits of Crocidura shantungensis caudal epididymal spermatozoa - Yong-Pil Cheon; Sung-Ho Lee; Jung-Hun Lee (Zoomorphology, 2015)

Effects of reduced vertical mixing under sea ice on Atlantic meridional overturning circulation (AMOC) in a global ice-ocean model - Sang Yeob Kim; Ho Jin Lee; Jae-Hun Park; Young Ho Kim (Ocean Science Journal, 2015)

Development of the Operational Oceanographic System of Korea - Kwang-Soon Park; Ki-Young Heo; Kicheon Jun; Jae-Il Kwon; Jinah Kim; Jin-Yong Choi; Kyoung-Ho Cho; Byoung-Ju Choi; Seung-Nam Seo; Young Ho Kim; Sung-Dae Kim; Chan-Su Yang; et al. (Ocean Science Journal, 2015)

Alternaria species associated with araliaceous plants in Korea - Jian Xin Deng; Mei Jia Li; Narayan Chandra Paul; Ji Hye Lee; Hye Sun Cho; Hyang Burm Lee; Seung Hun Yu (Mycological Progress, 2015)

SHRIMP U-Pb ages and Hf isotopic composition of the detrital zircons from the Myogok Formation, SE Korea: development of terrestrial basin and igneous activity during the early Cretaceous - Tae-Ho Lee; Kye-Hun Park; Keewook Yi; Jian-zhen Geng; Huai-kun Li (Geosciences Journal, 2015)

Analysis of cytokine production in a newly developed canine tracheal epithelial cell line infected with H3N2 canine influenza virus - Woo-Jung Park; Byung-Joo Park; Young-Jo Song; Dong-Hun Lee; Seong-Su Yuk; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Archives of Virology, 2015)

Prognostic value of hepatoma-derived growth factor-related protein 3 (HRP-3) methylation in non-small cell lung cancer - Young Hun Kim; Won Kee Lee; Jae Yong Park; Dong Sun Kim (Genes & Genomics, 2015)

Serology and clinical relevance of Corynebacterium pseudotuberculosis in native Korean goats (Capra hircus coreanae) - Byeong Yeal Jung; Seung-Hun Lee; Ha-Young Kim; Jae-Won Byun; Dong-Ho Shin; Daekeun Kim; Dongmi Kwak (Tropical Animal Health and Production, 2015)

Reducing Effect of IL-32α in the Development of Stroke Through Blocking of NF-κB, but Enhancement of STAT3 Pathways - Chul Ju Hwang; Hyung-Mun Yun; Yu Yeon Jung; Dong Hun Lee; Na Young Yoon; Hyun Ok Seo; Jin-Yi Han; Ki-Wan Oh; Dong Young Choi; Sang-Bae Han; Do Young Yoon; Jin Tae Hong (Molecular Neurobiology, 2015)

Genetic characterization of porcine epidemic diarrhea virus in Korea from 1998 to 2013 - Seong-Hee Kim; Jung-Min Lee; Jongsun Jung; In-Joong Kim; Bang-Hun Hyun; Hyun-Il Kim; Choi-Kyu Park; Jae-Ku Oem; Yeon-Hee Kim; Myoung-Heon Lee; Kyoung-Ki Lee (Archives of Virology, 2015)

The AtLRK10L1.2, Arabidopsis ortholog of wheat LRK10, is involved in ABA-mediated signaling and drought resistance - Chae Woo Lim; Seung Hwan Yang; Ki Hun Shin; Sung Chul Lee; Sang Hyon Kim (Plant Cell Reports, 2015)

Alternative splicing of mini-exons in the Arabidopsis leaf rust receptor-like kinase LRK10 genes affects subcellular localisation - Ki Hun Shin; Seung Hwan Yang; Jun Yong Lee; Che Woo Lim; Sung Chul Lee; John W. S. Brown; Sang Hyon Kim (Plant Cell Reports, 2015)

Simultaneous Production of Antifungal and Keratinolytic Activities by Feather-Degrading Bacillus subtilis S8 - Tae-Hun Go; Kwang-Sik Cho; Sang-Mee Lee; O-Mi Lee; Hong-Joo Son (Indian Journal of Microbiology, 2015)

Recognition of the Phanerozoic “Young granite gneiss” in the central Yeongnam massif - Yong-Sun Song; Ho-Sun Lee; Kye-Hun Park; Ian C. W. Fitzsimons; Peter A. Cawood (Geosciences Journal, 2015)

Polymorphism analysis of tyrosine hydroxylase gene variable number of tandem repeats in various Korean dogs - Hee-Eun Lee; Bong-Hwan Choi; Dong-Hoon Lee; Yun-Jeong Kwon; Jungwoo Eo; Yuri Choi; Hoim Jeong; Jeong-An Gim; Tae-Hun Kim; Ji-Hong Ha; Kook-Il Han; Heui-Soo Kim (Genes & Genomics, 2015)

Deinococcus radioresistens sp. nov., a UV and gamma radiation-resistant bacterium isolated from mountain soil - Sathiyaraj Srinivasan; Jae-Jin Lee; Sang-Yong Lim; Min-Ho Joe; Seong-Hun Im; Myung Kyum Kim (Antonie van Leeuwenhoek, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Menopause and Blood Mercury Levels: The Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2011 - Jin-Sung Yuk; Jung Hun Lee; Jin-Dong Jeon; Tai June Kim; Myung-Hwa Lee; Won I. Park (Biological Trace Element Research, 2014)

Statistical analysis and genetic diversity of three dog breeds using simple sequence repeats - Hoim Jeong; Bong-Hwan Choi; Jungwoo Eo; Yun-Jeong Kwon; Hee-Eun Lee; Yuri Choi; Jeong-An Gim; Tae-Hun Kim; Hwan-Hoo Seong; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; et al. (Genes & Genomics, 2014)

Hypoxia-mediated retinal neovascularization and vascular leakage in diabetic retina is suppressed by HIF-1α destabilization by SH-1242 and SH-1280, novel hsp90 inhibitors - Dong Hyun Jo; Hongchan An; Dong-Jo Chang; Yi-Yong Baek; Chang Sik Cho; Hyoung Oh Jun; So-Jung Park; Jin Hyoung Kim; Ho-Young Lee; Kyu-Won Kim; Jeewoo Lee; Hyun-Ju Park; et al. (Journal of Molecular Medicine, 2014)

Peroxisome-localized hepatitis Bx protein increases the invasion property of hepatocellular carcinoma cells - Jae-Min Han; Jung-Ah Kang; Min-Hee Han; Kyung-Hun Chung; Cho-Rong Lee; Woo-Keun Song; Youngsoo Jun; Sung-Gyoo Park (Archives of Virology, 2014)

Inhibition of lewis lung cancer cell growth and migration by fucoidan - Yong-seok Han; Jun Hee Lee; Hun Soo Chang; Sang Hun Lee (Molecular & Cellular Toxicology, 2014)

Stemphylium platycodontis sp. nov., isolated from Platycodon grandiflorus in Korea - Jian Xin Deng; Narayan Chandra Paul; Mei Jia Li; Hye Sun Cho; Hyang Burm Lee; Seung Hun Yu (Mycological Progress, 2014)

Blood levels of cadmium and lead in residents near abandoned metal mine areas in Korea - Dong-UK Park; Dae-Seon Kim; Seung-Do Yu; Kyeong-Min Lee; Seung-Hun Ryu; Soo-Geun Kim; Won-Ho Yang; Doo-Yong. Park; Yeong-Seoub Hong; Jung-Duck Park; Byung-Kook Lee; Jai-Dong Moon; et al. (Environmental Monitoring and Assessment, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

CD39-mediated effect of human bone marrow-derived mesenchymal stem cells on the human Th17 cell function - Jong Joo Lee; Hyun Jeong Jeong; Mee Kum Kim; Won Ryang Wee; Won Woo Lee; Seung U. Kim; Changmin Sung; Yung Hun Yang (Purinergic Signalling, 2014)

Physiological mechanism of drought tolerance in transgenic rice plants expressing Capsicum annuum methionine sulfoxide reductase B2 (CaMsrB2) gene - Zamin Shaheed Siddiqui; Jung-Il Cho; Taek-Ryoun Kwon; Byung-Ok Ahn; Kang-Seob Lee; Mi-Jeong Jeong; Tae-Hun Ryu; Seong-Kon Lee; Soo-Chul Park; Sung-Han Park (Acta Physiologiae Plantarum, 2014)

Genetic structure and variability of the working dog inferred from microsatellite marker analysis - Yun-Jeong Kwon; Bong-Hwan Choi; Jungwoo Eo; Choongrak Kim; Yi-Deun Jung; Ja-Rang Lee; Yuri Choi; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Dae-Soo Kim; Jae-Won Huh; et al. (Genes & Genomics, 2014)

Development and characterization of polymorphic microsatellite marker for an endangered freshwater fish in Korea, Gobiobotia brevibarba - Keun-Sik Kim; Hyo-Ryeon Lee; Sang-Yong Park; Myeong Hun Ko; In-Chul Bang (Conservation Genetics Resources, 2014)

Distribution patterns and introduction pathways of the cosmopolitan brown alga Colpomenia peregrina using mt cox3 and atp6 sequences - Kyung Min Lee; Ga Hun Boo; James A. Coyer; Wendy A. Nelson; Kathy Ann Miller; Sung Min Boo (Journal of Applied Phycology, 2014)

Does size difference in allogeneic cancellous bone granules loaded with differentiated autologous cultured osteoblasts affect osteogenic potential? - Sang-Uk Lee; Yang-Guk Chung; Seok-Jung Kim; Il-Hoan Oh; Yong-Sik Kim; Sung-Hun Ju (Cell and Tissue Research, 2014)

The effects of functionalized titanium with alendronate and bone morphogenic protein-2 for improving osteoblast activity - Sung Eun Kim; Young-Pil Yun; Kyeongsoon Park; Hak-Jun Kim; Deok-Won Lee; Jung Wook Kim; Dae Hyeok Yang; Dong Hun Suh (Tissue Engineering and Regenerative Medicine, 2013)

Immobilization of lead in contaminated firing range soil using biochar - Deok Hyun Moon; Jae-Woo Park; Yoon-Young Chang; Yong Sik Ok; Sang Soo Lee; Mahtab Ahmad; Agamemnon Koutsospyros; Jeong-Hun Park; Kitae Baek (Environmental Science and Pollution Research, 2013)

Erratum to: Rice cell wall polysaccharides: Structure and biosynthesis - Chang-Sik Oh; Hun Kim; Chanhui Lee (Journal of Plant Biology, 2013)

The oil production performance analysis using discrete fracture network model with simulated annealing inverse method - Young Ho Jang; Tae Hun Lee; Ji Hun Jung; Sun Il Kwon; Won Mo Sung (Geosciences Journal, 2013)

Monitoring by LC-MS/MS of 48 compounds of sildenafil, tadalafil, vardenafil and their analogues in illicit health food products in the Korean market advertised as enhancing male sexual performance - Ji Hyune Lee; Nam Sook Kim; Kyoung Moon Han; Sung Hun Kim; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants: Part A, 2013)

A monotonic limiter and flux-corrected transport approach for high-order time integration schemes - Sang-Hun Park; Tae-Young Lee (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Retinyl retinoate, a retinoid derivative improves acne vulgaris in double-blind, vehicle-controlled clinical study - Bora Kim; Hyunjung Kim; Jin Eun Kim; Seung Hun Lee (Tissue Engineering and Regenerative Medicine, 2013)

Normative data for neuromuscular assessment of the hand–arm vibration syndrome and its retrospective applications in Korean male workers - Ryeok Ahn; Cheol-In Yoo; Hun Lee; Chang-Sun Sim; Joo Hyun Sung; Jae-Kook Yoon; Song-Woo Shin (International Archives of Occupational and Environmental Health, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Rice cell wall polysaccharides: Structure and biosynthesis - Chang-Sik Oh; Hun Kim; Chanhui Lee (Journal of Plant Biology, 2013)

Identification of genetic variations of cultivated and weedy types of Perilla species in Korea and Japan using morphological and SSR markers - Kyu Jin Sa; Seung Hun Choi; Mariko Ueno; Kyong-Cheul Park; Young Jin Park; Kyoung Ho Ma; Ju Kyong Lee (Genes & Genomics, 2013)

Paleomagnetism on the Quaternary marine sediment at the DH-1 long-core site in the Korean continental margin of the East Sea - Byungju Lee; Woo-Hun Ryang; Seong-Jae Doh (Geosciences Journal, 2013)

Animal models of axon regeneration after spinal cord injury - Do-Hun Lee; Jae K. Lee (Neuroscience Bulletin, 2013)

Molecular and immunohistochemical characterization of the chitinase gene from Pieris rapae granulovirus - Seunghan Oh; Dong Hyun Kim; Bharat Bhusan Patnaik; Yong Hun Jo; Mi Young Noh; Hyo Jeong Lee; Kwang Ho Lee; Kwang Ho Yoon; Wan-Jong Kim; Ju Young Noh; Heon Cheon Jeong; Yong Seok Lee; et al. (Archives of Virology, 2013)

CoCl2 induces apoptosis through the mitochondria- and death receptor-mediated pathway in the mouse embryonic stem cells - Jin-Ha Lee; Seong-Ho Choi; Min-Woo Baek; Mi-Hwa Kim; Heong-Jun Kim; Sun-Hun Kim; Sang-Jin Oh; Hong-Ju Park; Won-Jae Kim; Ji-Yeon Jung (Molecular and Cellular Biochemistry, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Sugar and organic acid contents of day-neutral and ever-bearing strawberry cultivars in high-elevation for summer and autumn fruit production in Korea - Jiwei Ruan; Young Hun Lee; Sae Jin Hong; Young Rog Yeoung (Horticulture, Environment, and Biotechnology, 2013)

Carpesium abrotanoides extract inhibits cyclooxygenase-2 expression induced by toll-like receptor agonists - Do-Won Jeong; Eun-Kyeong Lee; Chung-Ho Lee; Se Jin Lim; Gyo-Jeong Gu; Ji Hun Paek; Songmun Kim; Soon Sung Lim; Hyung-Sun Youn (Toxicology and Environmental Health Sciences, 2013)

Genome-wide copy number variation in Hanwoo, Black Angus, and Holstein cattle - Jung-Woo Choi; Kyung-Tai Lee; Xiaoping Liao; Paul Stothard; Hyeon-Seung An; Sungmin Ahn; Seunghwan Lee; Sung-Yeoun Lee; Stephen S. Moore; Tae-Hun Kim (Mammalian Genome, 2013)

Flowering and fruiting of day-neutral and ever-bearing strawberry cultivars in high-elevation for summer and autumn fruit production in Korea - Jiwei Ruan; Young Hun Lee; Young Rog Yeoung (Horticulture, Environment, and Biotechnology, 2013)

Cerebellar Atrophy in Patients with Subcortical-Type Vascular Cognitive Impairment - Cindy W. Yoon; Sang Won Seo; Jun-Sung Park; Ki-Chang Kwak; Uicheul Yoon; Mee Kyung Suh; Geon Ha Kim; Ji Soo Shin; Chi Hun Kim; Young Noh; Hanna Cho; Min-Jeong Kim; et al. (The Cerebellum, 2013)

Saponins from soy bean and mung bean inhibit the antigen specific activation of helper T cells by blocking cell cycle progression - Suk Jun Lee; Joonbeom Bae; Sunhee Kim; Seonah Jeong; Chang-Yong Choi; Sang-Pil Choi; Hyun-Sook Kim; Woon-Won Jung; Jee-Young Imm; Sae Hun Kim; Taehoon Chun (Biotechnology Letters, 2013)

Phylogenetic analysis of porcine astrovirus in domestic pigs and wild boars in South Korea - Meong-Hun Lee; Hye-Young Jeoung; Hye-Ran Park; Ji-Ae Lim; Jae-Young Song; Dong-Jun An (Virus Genes, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Celastrol inhibits growth and induces apoptotic cell death in melanoma cells via the activation ROS-dependent mitochondrial pathway and the suppression of PI3K/AKT signaling - Ju-Hye Lee; Yeong-Seon Won; Ki-Hun Park; Mi-Kyung Lee; Hirofumi Tachibana; Koji Yamada; Kwon-Il Seo (Apoptosis, 2012)

Geochemistry and S r – N d – P b isotopic constraints on the petrogenesis of C enozoic lavas from the P ali A ike and M orro C hico area (52° S ), southern P atagonia, S outh A merica - Mi Kyung Choo; Mi Jung Lee; Jong Ik Lee; Kyu Han Kim; Kye‐Hun Park (Island Arc, 2012)
Geochemical and isotopic analyses ( S r – N d – P b ) of late M iocene to Q uaternary plateau lavas from the P ali A ike and M orro C hico areas (52° S ) were undertaken to constrain the melting processes and mantle sources that contributed to magma generation and the geodynamic evolution of southernmost P atagonia, S outh A merica. The P ali A ike and M orro C hico lavas are alkaline ( P ali A ike, 45–49 wt.% S i O 2 ; 4.3–5.9 wt.% Na 2 O + K 2 O ) and subalkaline ( M orro C hico, 50.5–50.8 wt.% SiO 2 ; 4.0–4.4 wt.% Na 2 O + K 2 O ), relatively primitive ( P ali A ike, 9.5–13.7 wt.% M g O ; M orro C hico, 7.6–8.8 wt.% M g O ) mafic volcanic rocks that have typical intraplate ocean island basalt‐like signatures. Incompatible trace element ratios and isotopic ratios of the P ali A ike and M orro C hico lavas differ from those of the majority of N eogene southern P atagonian slab window lavas in showing more enriched characteristics and are similar to high‐μ ( HIMU )‐like basalts. The rare earth element ( REE ) modeling to constrain mantle melting percentages suggests that these lavas were produced by low degrees of partial melting (1.0–2.0% for P ali A ike lavas and about 2.6–2.7% for M orro C hico lavas) of a garnet lherzolite mantle source. The major systematic variations of S r– N d– P b isotopes in southern P atagonian lavas are related to geographic location. The P ali A ike and M orro C hico lavas from the southernmost part of P atagonia have lower 87 Sr / 86 Sr and higher 143 Nd / 144 Nd and 206 P b/ 204 P b ratios, relative to most of the southern P atagonian lavas erupted north of 49.5° S , pointing to a HIMU ‐like signature. An isotopically depleted and HIMU ‐like asthenospheric domain may have been the main source of magmas in the southernmost part of P atagonia (e.g. P ali A ike, M orro C hico, and C amusu A ike volcanic field), suggesting the presence of a major discontinuity in the isotopic composition of the asthenosphere in southern P atagonia. On the basis of geochemical and isotope data and the available geological and geotectonic reconstructions, a link between the HIMU asthenospheric mantle domain beneath southernmost Patagonia and the HIMU mega‐province of the southwestern P acific O cean is proposed.

Ecological responses and remediation ability of water fern (Azolla japonica) to water pollution - Uhram Song; Hun Park; Eun Ju Lee (Journal of Plant Biology, 2012)

mRNA sequence analysis and quantitative expression of the ADAMTS4 gene in the thoroughbred horse - Jae-Woo Moon; Kung Ahn; Jin-Han Bae; Gyu-Hwi Nam; Byung-Wook Cho; Kyung-Do Park; Hak-Kyo Lee; Young-Mok Yang; Tae-Hun Kim; Hwan-Hoo Seong; Kyudong Han; Heui-Soo Kim (Genes & Genomics, 2012)

Linear Delivery of Verapamil via Nanofibrous Sheet-Based System - Ji Eun Lee; Chun Gwon Park; Byeong Moo An; Myung Hun Kim; Min Park; Seung Ho Lee; Young Bin Choy (Pharmaceutical Research, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Nanomaterial-Based Biosensor as an Emerging Tool for Biomedical Applications - Sang Hun Lee; Jong Hwan Sung; Tai Hyun Park (Annals of Biomedical Engineering, 2012)

In vitro CpG methylation and garcinol reduce PERV LTR promoter activity - Hong-Seok Ha; Young-Choon Lee; Sang-Je Park; Yi-Deun Jung; Kung Ahn; Jae-Woo Moon; Kyudong Han; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

Determination of PDE-5 inhibitors and appetite suppressants in adulterated dietary supplements using LC/PDA and LC/MS - So-ra Park; Jin Gyun Lee; Si Hun Roh; Gyudong Kim; Chan Hyeok Kwon; Hee Ra Park; Ki Sung Kwon; Deukjoon Kim; Sung Won Kwon (Food Additives & Contaminants Part B-Surveillance, 2012)

Abnormal effects of unpurified and purified multi-walled carbon nanotubes in A549, Jurkat and THP-1 cell lines - Young Hun Kim; Hyeoung Woo Park; Zae Young Ryoo; Hyun-Shik Lee; Do-Hyung Kim; Sanggyu Lee (Molecular & Cellular Toxicology, 2012)

mRNA-centric semantic modeling for finding molecular signature of trace chemical in human blood - Ga-Hee Shin; Yeon-Kyung Kang; Seung-Hun Lee; Seung Jun Kim; Seung Yong Hwang; Suk-Woo Nam; Jae-Chun Ryu; Byeong-Chul Kang (Molecular & Cellular Toxicology, 2012)

Anti-inflammatory effect of sweetfish-derived protein and its enzymatic hydrolysate on LPS-induced RAW264.7 cells via inhibition of NF-κB transcription - Nak-Yun Sung; Pil-Moon Jung; Minchul Yoon; Jeong-Soo Kim; Jong-il Choi; Hye Gwang Jeong; Ju-Woon Lee; Jae-Hun Kim (Fisheries Science, 2012)

Musculoskeletal tissue engineering by endogenous stem/progenitor cells - Hemin Nie; Chang Hun Lee; Jiali Tan; Chuanyong Lu; Avital Mendelson; Mo Chen; Mildred C. Embree; Kimi Kong; Bhranti Shah; Shuang Wang; Shoko Cho; Jeremy J. Mao (Cell and Tissue Research, 2012)

A novel function of Streptomyces integration host factor (sIHF) in the control of antibiotic production and sporulation in Streptomyces coelicolor - Yung-Hun Yang; Eunjung Song; Joost Willemse; Sung-Hee Park; Woo-Seong Kim; Eun-jung Kim; Bo-Rahm Lee; Ji-Nu Kim; Gilles P. van Wezel; Byung-Gee Kim (Antonie van Leeuwenhoek, 2012)

Performance of a conical jellyfish exclusion device installed in a trawl net - Chang-Doo Park; Kyounghoon Lee; Seong-Hun Kim; Yasuzumi Fujimori (Fisheries Science, 2012)

Epigenetic CpG Demethylation of the Promoter and Reactivation of the Expression of Neurog1 by Curcumin in Prostate LNCaP Cells - Limin Shu; Tin Oo Khor; Jong-Hun Lee; Sarandeep S. S. Boyanapalli; Ying Huang; Tien-Yuan Wu; Constance L.-L. Saw; Ka-Lung Cheung; Ah-Ng Tony Kong (The AAPS Journal, 2011)

Novel PPARγ partial agonists with weak activity and no cytotoxicity; identified by a simple PPARγ ligand screening system - Min-Chul Cho; Dong-Hun Lee; Eun Jin Kim; Jee-young Lee; Jeong-Woo Kang; Jong Hwan Song; Youhoon Chong; Yangmi Kim; Jin-Tae Hong; Do-Young Yoon (Molecular and Cellular Biochemistry, 2011)

Cellular imaging assay for early evaluation of an apoptosis inducer - Sang Youn Hwang; Seung Hun Cho; Byung Heon Lee; Yoon-Jae Song; E. K. Lee (Apoptosis, 2011)

Oxidized phosphatidylcholine induces migration of bone marrow-derived mesenchymal stem cells through Krüppel-like factor 4-dependent mechanism - Sang Hun Shin; Hae Young Song; Min Young Kim; Eun Kyung Do; Jung Sub Lee; Jae Ho Kim (Molecular and Cellular Biochemistry, 2011)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Influence of short day treatment on autumn fruit production of June-bearing strawberry cultivars - Jiwei Ruan; Young Hun Lee; Young Rog Yeoung; Kirk D. Larson (Horticulture, Environment, and Biotechnology, 2011)

Expression of the human cancer/testis antigen NY-SAR-35 is activated by CpG island hypomethylation - Jin-Hyung Park; Myung-Ha Song; Chang-Hun Lee; Min-Ki Lee; Young-Min Park; Lloyd Old; Sang-Yull Lee (Biotechnology Letters, 2011)

Stability of Fe- and Mn-(oxyhydr)oxides in Common Soil Dispersion Solutions - Phung N. Manh; Moonis Ali Khan; Byong-Hun Jeon; Jae Gon Kim; Giehyeon Lee (Water, Air, & Soil Pollution, 2011)

Caffeic acid and quercitrin purified from Houttuynia cordata inhibit DNA topoisomerase I activity - Seok-Young Jang†; Jeen-Soo Bae†; Yun Ho Lee; Kyeong Yeol Oh; Ki-Hun Park; Young-Seuk Bae (Natural Product Research, 2011)

Genetic characterization of H1 avian influenza viruses isolated from migratory birds and domestic ducks in Korea - Ok-Mi Jeong; Yong-Joo Kim; Jun-Gu Choi; Hyun-Mi Kang; Min-Chul Kim; Jun-Hun Kwon; Youn-Jeong Lee (Virus Genes, 2011)

Abiotic subsurface behaviors of As(V) with Fe(II) - Sang-Hun Lee; Woosik Jung; Byong-Hun Jeon; Jae-Young Choi; Sunjoon Kim (Environmental Geochemistry and Health, 2011)

Differences in bird communities in postfire silvicultural practices stands within pine forest of South Korea - Eun-Jae Lee; Woo-Shin Lee; Seung Hun Son; Shin-Jae Rhim (Landscape and Ecological Engineering, 2011)

Investigation of porcine FABP3 and LEPR gene polymorphisms and mRNA expression for variation in intramuscular fat content - Xiaoping Li; Sang-Wook Kim; Jung-Suck Choi; Yoon-Mi Lee; Cheol-Koo Lee; Bong-Hwan Choi; Tae-Hun Kim; Yang-Il Choi; Jong-Joo Kim; Kwan-Suk Kim (Molecular Biology Reports, 2010)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)

A cytological observation of the fluid in the primo-nodes and vessels on the surfaces of mammalian internal organs - Baeckkyoung Sung; Min Su Kim; Byung-Cheon Lee; Seong-Hun Ahn; Sung-Yeoun Hwang; Kwang-Sup Soh (Biologia, 2010)

Regulation of bone formation using rapamycin-induced BMP2 expression system: influence of implanted cell number - Dong-Jin Lim; Bae Keun Park; Won Gu Jang; Kkot-Nim Lee; Renny Franceschi; Sun-Hun Kim; Shee-Eun Lee; Jeong-Tae Koh (Molecular & Cellular Toxicology, 2010)

Iron deficiency in children with mitochondrial disease - Hye Eun Kwon; Jung Hun Lee; Young Mock Lee; Hoon Chul Kang; Joon Soo Lee; Heung Dong Kim (Metabolic Brain Disease, 2010)

Technical issues in modeling surface-drifter behavior on the East China Sea shelf - Shin’ichiro Kako; Atsuhiko Isobe; Shun Yoshioka; Pil-Hun Chang; Takeshi Matsuno; Sang-Hyun Kim; Joon-Soo Lee (Journal of Oceanography, 2010)

The bZIP transcription factor OsABF1 is an ABA responsive element binding factor that enhances abiotic stress signaling in rice - Md. Amir Hossain; Yongjoo Lee; Jung-Il Cho; Chul-Hyun Ahn; Sang-Kyu Lee; Jong-Seong Jeon; Hun Kang; Choon-Hwan Lee; Gynheung An; Phun Bum Park (Plant Molecular Biology, 2010)

The effects of various antioxidants on the development of parthenogenetic porcine embryos - Hyung Soo Yuh; Dong Hun Yu; Mi Jung Shin; Hei Jung Kim; Ki Beom Bae; Dong Seok Lee; Hwi Cheul Lee; Won Kyong Chang; Soo Bong Park; Sang Gyu Lee; Hum Dai Park; Ji Hong Ha; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

1,3-Dichloro-2-propanol induces apoptosis via both calcium and ROS in mouse melanoma cells - Sun Young Park; Young Hun Kim; Young Hee Kim; Sang-Joon Lee (Biotechnology Letters, 2010)

Molecular epizootiology of infectious bursal disease (IBD) in Korea - Woo-Jin Jeon; Kang-Seuk Choi; Dong-Woo Lee; Eun-Kyoung Lee; Sang-Ho Cha; Sun-Hee Cho; Jun-Hun Kwon; Yeo-sung Yoon; Sun-Joong Kim; Jae-Hong Kim; Hyuk-Joon Kwon (Virus Genes, 2009)

Detection of low-abundant novel transcripts in mouse hematopoietic stem cells - Hyeng-Soo Kim; Junmo Hwang; Young-Hun Kim; Seonggon Kim; Jae-Woong Lee; Hyung-Sik Kang; Kil Soo Kim; Ji-Hong Ha; Jin Woong Chung; Kyu-Tae Chang; Zae Young Ryoo; Sanggyu Lee (Molecular Genetics and Genomics, 2009)

Expression, Solubilization and Purification of a Human Olfactory Receptor from Escherichia coli - Hyun Seok Song; Sang Hun Lee; Eun Hae Oh; Tai Hyun Park (Current Microbiology, 2009)

A volumetric study of the corpus callosum in 20s and 40s Korean people - Beob-Yi Lee; Jin-Hun Sohn; Mi-Hyun Choi; Su-Jeong Lee; Hyo-Seong Kim; Jae-Woong Yang; Jin-Seung Choi; Hyung-Sik Kim; Jeong-Han Yi; Gye-Rae Tack; Soon-Cheol Chung (Brain Structure and Function, 2009)

Apoptotic cell death of human leukaemia U937 cells by ubiquinone-9 purified from Pleurotus eryngii - Jeen-Soo Bae; Jin Wook Park; So Hyun Park; Jung Bin Park; Yoon-Hwa Rho; Young Bae Ryu; Kun-Sik Lee; Ki-Hun Park; Young-Seuk Bae (Natural Product Research, 2009)

Determinants of urinary 1-hydroxypyrene glucuronide in South Korean children - Kyoung-Ho Lee; Roel Vermeulen; Virissa Lenters; Soo-Hun Cho; Paul T. Strickland; Daehee Kang (International Archives of Occupational and Environmental Health, 2009)

Red and Blue Photons Can Enhance the Production of Astaxanthin from Haematococcus pluviatis - Z-Hun Kim; Ho-Sang Lee; Choul-Gyun Lee (Algae, 2009)

Enhanced fungal resistance in Arabidopsis expressing wild rice PR-3 (OgChitIVa) encoding chitinase class IV - Jung-Hun Pak; Eun-Sook Chung; Sang-Hyun Shin; Eun-Hee Jeon; Mi-Jin Kim; Hye-Young Lee; Ji-Ung Jeung; Nam-In Hyung; Jai-Heon Lee; Young-Soo Chung (Plant Biotechnology Reports, 2009)

Vertical structure of low-frequency currents in the southwestern East Sea (Sea of Japan) - Yun-Bae Kim; Kyung-Il Chang; Kuh Kim; Jae-Hun Park; Jae-Hak Lee (Journal of Oceanography, 2009)

Tropical Malaysians and temperate Koreans exhibit significant differences in sweating sensitivity in response to iontophoretically administered acetylcholine - Jeong-Beom Lee; Jun-Sang Bae; Takaaki Matsumoto; Hun-Mo Yang; Young-Ki Min (International Journal of Biometeorology, 2009)

Kinetic and regulatory properties of plant ADP-glucose pyrophosphorylase genetically modified by heterologous expression of potato upreg mutants in vitro and in vivo - Si-Myung Lee; Tae-Hun Ryu; Su-Il Kim; Thomas Okita; Donghern Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Association analysis of v-AKT murine thymoma viral oncogene homolog 1 (AKT1) polymorphisms and type 2 diabetes mellitus in the Korean population - Hyun-Seok Jin; Kyung-Won Hong; Ji-Eun Lim; Gi-Ja Lee; Jong Ho Han; Min-Jin Go; Jong-Young Lee; Jeong-Taek Woo; Hun Kuk Park; Bermseok Oh (Genes & Genomics, 2009)

Temporal Variations in Seaweed Biomass in Korean Coasts: Woejodo and Jusamdo, Jeonbuk - Han-Gil Choi; Ki-Hun Lee; Xiao Qin Wan; Hyun-Il Yoo; Hyang-Ha Park; Jeong-Ha Kim; Ik-Kyo Chung (Algae, 2008)

Purification and partial characterization of antifungal metabolite from Paenibacillus lentimorbus WJ5 - Young-Keun Lee; M. Senthilkumar; Jung-Hun Kim; K. Swarnalakshmi; K. Annapurna (World Journal of Microbiology and Biotechnology, 2008)

Real-time hydro-environmental modeling and visualization system for public engagement - Joseph Hun-wei Lee; K. W. Choi (Environmental Fluid Mechanics, 2008)

Full-length genome sequence of avian paramyxovirus type 4 isolated from a mallard duck - Woo-Jin Jeon; Eun-Kyoung Lee; Jun-Hun Kwon; Kang-Seuk Choi (Virus Genes, 2008)

Overexpression of OgPAE1 from wild rice confers fungal resistance against Botrytis cinerea - Eun Hee Jeon; Eun Sook Chung; Jung Hun Pak; Jae Sung Nam; Sung Ki Cho; Sang Hyun Shin; Doh Hoon Kim; Gyung Tae Kim; Jai Heon Lee; Kyung Ho Kang; Young Soo Chung (Journal of Plant Research, 2008)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Beneficial effects of cardiac rehabilitation and exercise after percutaneous coronary intervention on hsCRP and inflammatory cytokines in CAD patients - Young-Joo Kim; Young-Oh Shin; Jun-Sang Bae; Jeong-Beom Lee; Joo-Hyun Ham; Youn-Jung Son; Jung-Kyu Kim; Chul Kim; Byoung-Kwon Lee; Jae-Keun Oh; Timothy Othman; Young-Ki Min; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Seasonal Community Structure and Vertical Distribution of Medicinal Seaweeds at Kkotji in Taean Peninsula, Korea - Ki-Hun Lee; Hyun-Il Yoo; Han-Gil Choi (Algae, 2007)

Heavy water labeling method for measuring the effect of genistein on mammary gland carcinogenesis - Hyeon-A Kim; Kyu-Shik Jeong; Dae-Hun Park; Jeong-Ae Lee; Won-Il Jeong; Yoo Kyeong Kim (Molecular and Cellular Biochemistry, 2007)

2′,5,7-Trihydroxy-4′,5′-(2,2-dimethylchromeno)-8-(3-hydroxy-3-methylbutyl) flavanone purified from Cudrania tricuspidata induces apoptotic cell death of human leukemia U937 cells - Yoon-Hwa Rho; Soo-Hyun Yoon; Eun-Kyung Kim; Ji-Young Kang; Byong-Won Lee; Ki-Hun Park; Young-Seuk Bae (Natural Product Research, 2007)

DNMT3b 39179G‎T Polymorphism and the Risk of Adenocarcinoma of the Colon in Koreans - Young-Seoub Hong; Hye-Jung Lee; Chang-Hun You; Mee-Sook Roh; Jong-Young Kwak; Myeong-Jin Lee; Joon-Youn Kim (Biochemical Genetics, 2007)

Larger numbers of immature dendritic cells augment an anti-tumor effect against established murine melanoma cells - Tae-Hyung Lee; Young-Hun Cho; Min-Geol Lee (Biotechnology Letters, 2007)

Alpha-tocopheryl succinate sensitizes human colon cancer cells to exisulind-induced apoptosis - Soo-Jeong Lim; Young-Ju Lee; Dae-Hun Park; Eunmyong Lee; Moon-Kyung Choi; Wanseo Park; Kyung-Hee Chun; Han-Gon Choi; Jung Sik Cho (Apoptosis, 2007)

Sulindac-derived reactive oxygen species induce apoptosis of human multiple myeloma cells via p38 mitogen activated protein kinase-induced mitochondrial dysfunction - Sung-Keum Seo; Hyung-Chahn Lee; Sang-Hyeok Woo; Hyeon-Ok Jin; Doo-Hyun Yoo; Su-Jae Lee; Sungkwan An; Tae-Boo Choe; Myung-Jin Park; Seok-Il Hong; In-Chul Park; Chang-Hun Rhee (Apoptosis, 2007)

Expression of an Arabidopsis CAX2 variant in potato tubers increases calcium levels with no accumulation of manganese - Chang Kil Kim; Jeung-Sul Han; Hyun-Suk Lee; Joung-Youl Oh; Thoshiro Shigaki; Sung Hun Park; Kendal Hirschi (Plant Cell Reports, 2006)

Prolonged residence of temperate natives in the tropics produces a suppression of sweating - Jun-Sang Bae; Jeong-Beom Lee; Takaaki Matsumoto; Timothy Othman; Young-Ki Min; Hun-Mo Yang (Pflügers Archiv - European Journal of Physiology, 2006)

Proapoptotic activity of NAG-1 is cell type specific and not related to COX-2 expression - Tae Jung Jang; Nam II Kim; Chang Hun Lee (Apoptosis, 2006)

The Phytoplankton Compositions and Trophic States at Several Lakes ofSuwon-si, Korea - Jung-Hun Park; Byeong-Ryeol Moon; Ok-Min Lee (Algae, 2006)

Insight into Types I and II nonhost resistance using expression patterns of defense-related genes in tobacco - Sang-Keun Oh; Sanghyeob Lee; Eunsook Chung; Jeong Mee Park; Seung Hun Yu; Choong-Min Ryu; Doil Choi (Planta, 2006)

Characterization of pbpA and pbp2 Encoding Penicillin-binding Proteins Located on the Downstream of Clavulanic Acid Gene Cluster in Streptomyces clavuligerus - Kenji Ishida; Trinh Viet Hung; Kwangkyoung Liou; Hei Chan Lee; Chang-Hun Shin; Jae Kyung Sohng (Biotechnology Letters, 2006)

Expression of a novel NAC domain-containing transcription factor (CaNAC1) is preferentially associated with incompatible interactions between chili pepper and pathogens - Sang-Keun Oh; Sanghyeob Lee; Seung Hun Yu; Doil Choi (Planta, 2005)

Comparing the inverse parameter estimation approach with pedo-transfer function method for estimating soil hydraulic conductivity - Do-Hun Lee (Geosciences Journal, 2005)

Fractal Stochastic Modeling of Spiking Activity in Suprachiasmatic Nucleus Neurons - Sung-IL Kim; Jaeseung Jeong; Yongho Kwak; Yang In Kim; Seung Hun Jung; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

Occupational hand–arm vibration syndrome in Korea - Cheolin Yoo; Ji-Ho Lee; Choong-Ryeol Lee; Yangho Kim; Hun Lee; Younghee Choi; Young Wook Kim; Chang Ho Chae; Hyokyoung Kim; Sang Baek Koh; Euna Kim; Lu Jin Lee; et al. (International Archives of Occupational and Environmental Health, 2005)

The suggestive association of eotaxin-2 and eotaxin-3 gene polymorphisms in Korean population with allergic rhinitis - Soo-Cheon Chae; Young-Ran Park; Gyung-Jae Oh; Jae-Hoon Lee; Hun-Taeg Chung (Immunogenetics, 2005)

Antiviral Effects of Sulfated Exopolysaccharide from the Marine Microalga Gyrodinium impudicum Strain KG03 - Joung Han Yim; Sung Jin Kim; Se Hun Ahn; Chong Kyo Lee; Ki Tae Rhie; Hong Kum Lee (Marine Biotechnology, 2004)

Possible involvement of both endoplasmic reticulum– and mitochondria-dependent pathways in MoMuLV- ts 1–induced apoptosis in astrocytes - Na Liu; Xianghong Kuang; Hun-Taek Kim; George Stoica; Wenan Qiang; Virginia Lee Scofield; Paul KY Wong (Journal of NeuroVirology, 2004)

Isolation and Characterization of Bacteria Capable of Degrading Phenol and Reducing Nitrate Under Low-Oxygen Conditions - Seung-Hun Baek; Kyoung-Ho Kim; Cheng-Ri Yin; Che Ok Jeon; Wan-Taek Im; Kwang-Kyu Kim; Sung-Taik Lee (Current Microbiology, 2003)

A High-Throughput Combinatorial Approach for the Discovery of a Cremophor EL-Free Paclitaxel Formulation - Hongming Chen; Zhong Zhang; Chris McNulty; Cameron Olbert; Hye Jeong Yoon; Jang Won Lee; Sung Chul Kim; Min Hyo Seo; Hun Seung Oh; Anthony V. Lemmo; Stephen J. Ellis; Ken Heimlich (Pharmaceutical Research, 2003)

UV-B Effects on Growth and Nitrate Dynamics in Antarctic Marine Diatoms Chaetoceros neogracile and Stellarima microtrias - Jae Sin Gang; Seong Ho Gang; Yun Ho Lee; Jeong Hui Sim; Sang Hun Lee (Algae, 2003)

Stereochemical control in diastereoselective reduction of α-substituted-β-ketoesters using a reductase purified from Kluyveromyces marxianus - Joo Hwan Cha; Ae Nim Pae; Kyung Il Choi; Yong Seo Cho; Wook Hyun Kim; Ye Sun Han; Hong-Chul Yun; Jongsoo Lee; Hun Yeong Koh; Eun Lee (Biotechnology Letters, 2002)

Phylogenetic Relationship of Microcystis (Cyanophyceae) Based on Partial 16S rRNA Gene Sequences in Korea - Jong-In Kim; Jong-Hun Lim; Jae-Wan Lee; Hae-Bok Lee (Algae, 2002)

Inhibitory effect of chlorinated guaiacols on methanogenic activity of anaerobic digester sludge - Cheng-Ri Yin; Dong-Il Seo; Seung-Hun Baek; Ken Ohlen; Sung-Taik Lee (Biotechnology Letters, 2001)

Aerobic nitrate respiration by a newly isolated phenol-degrading bacterium, Alcaligenes strain P5 - Seung-Hun Baek; Cheng-Ri Yin; Sung-Taik Lee (Biotechnology Letters, 2001)

Molecular cloning, expression, and functional characterization of a 2Cys-peroxiredoxin in Chinese cabbage - Na Eun Cheong; Yeon Ok Choi; Kyun Oh Lee; Woe Yeon Kim; Bae Gyo Jung; Yong Hun Chi; Jin Sook Jeong; Kanghwa Kim; Moo Je Cho; Sang Yeol Lee (Plant Molecular Biology, 1999)

Improvements in shoot apex regeneration of two fiber crops: cotton and kenaf - Cecilia Zapata; Metinee Srivatanakul; Sung-Hun Park; Byung-Moo Lee; Maria G. Salas; Roberta H. Smith (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Continuous Wavelet Analysis as an Aid in the Representation and Interpretation of Electrogastrographic Signals - Wenwei Qiao; Hun H. Sun; William Y. Chey; K. Y. Lee (Annals of Biomedical Engineering, 1998)

A new homeodomain-leucine zipper gene from Arabidopsis thaliana induced by water stress and abscisic acid treatment - Yong-Hun Lee; Jong-Yoon Chun (Plant Molecular Biology, 1998)

An early Proterozoic Sm−Nd age of mafic granulite from the Hwacheon area, South Korea - Seung Ryeol Lee; Moonsup Cho; Chang-Sik Cheong; Kye-Hun Park (Geosciences Journal, 1997)

A preliminary sulfur and lead isotopic study of lead-zinc deposits in the Meixian area, Fujian Province, China - Insung Lee; Kye-Hun Park (Geosciences Journal, 1997)

Separation of physiological factors influencing glucose insulin kinetics in diabetic patients - Byoung G. Min; Eung J. Woo; Hong K. Lee; Hun K. Min (Annals of Biomedical Engineering, 1985)